Fluorine-containing cyclic sulfonylimide salt, and method for producing same, non-aqueous electrolyte, non-aqueous secondary battery

JP2025001013APending Publication Date: 2025-01-07ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024176033
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-10
Filing Date
2024-10-07
Publication Date
2025-01-07

AI Technical Summary

Benefits of technology

【0016】 本発明に係る含フッ素環状スルホニルイミド塩は、耐熱性が高く、広い温度領域で使用可能であり、金属腐食性が低い。また、本発明によれば、金属腐食性が低く、優れた初回充放電効率とサイクル性能を備えた非水系電解液を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001013000001_ABST
    Figure 2025001013000001_ABST
Patent Text Reader

Abstract

To provide a fluorine-containing cyclic sulfonylimide salt and non-aqueous electrolyte having excellent heat resistance and a reduced metallic corrosion property.SOLUTION: The present invention provides a fluorine-containing cyclic sulfonylimide salt composition containing a fluorine-containing cyclic sulfonylimide salt represented by general formula (1A) {in the formula, R may be the same or different, and each represent a fluorine atom or a trifluoromethyl group, n is an integer number of 1 to 4, and M1 is Li, Na, K, or NH4}. The fluorine-containing cyclic sulfonylimide salt composition is characterized in that a mass reduction ratio thereof reaches 2 mass% is 385°C or higher when heated at a temperature increase speed of 10°C / min from 100°C under a nitrogen air stream.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fluorine-containing cyclic sulfonylimide salt which is useful as an antistatic agent, an ion-conducting material such as an organic electrolyte, or a flame retardant, and to a method for producing the same, a nonaqueous electrolyte, and a nonaqueous secondary battery. [Background technology]

[0002] Lithium ion batteries and other non-aqueous secondary batteries are characterized by their light weight, high energy and long life, and are widely used as power sources for various portable electronic devices. In recent years, non-aqueous electrolytes have been widely used for industrial applications, such as power tools, and for in-vehicle applications, such as electric vehicles and electric bicycles, and are also attracting attention in the field of power storage, such as residential power storage systems.

[0003] A typical example of a non-aqueous electrolyte for a lithium ion battery is a combination of a highly dielectric solvent such as a cyclic carbonate ester and a low viscosity solvent such as a chain carbonate ester. In addition, it is desirable to add an electrode protection additive such as vinylene carbonate to form a solid electrolyte interface (SEI) on the negative electrode surface and thereby suppress the reductive decomposition of the non-aqueous solvent.

[0004] In recent years, fluorine-containing cyclic sulfonylimide salts have been attracting attention as materials for non-aqueous electrolyte solutions.

[0005] For example, Patent Document 1 reports a non-aqueous electrolyte that maintains high ionic conductivity without causing electrode corrosion by using a fluorine-containing cyclic sulfonylimide salt.

[0006] Patent Document 2 reports a nonaqueous secondary battery that combines a nonaqueous electrolyte solution containing a fluorine-containing cyclic sulfonylimide salt with a positive electrode in which the amount of cobalt used is reduced.

[0007] Fluorine-containing sulfonylimide salts such as N,N-bis(trifluoromethanesulfonyl)imide and bis(fluorosulfonyl)imide, and their derivatives are known to be useful compounds as ion-conducting materials and flame retardants (for example, see Non-Patent Document 1 below). Incidentally, a method for producing compound (1A) is known in which FO2SCF2CF2SO2F, synthesized by the electrolytic coupling reaction of FSO2CF2COOH, is reacted with ammonia to obtain a fluorine-containing cyclic sulfonylimide ammonium salt (cyclization reaction), and then the salt is reacted with an alkali metal hydroxide or carbonate (cation exchange reaction) (see Patent Document 3 below). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2010 / 110388 [Patent Document 2] JP 2008-21517 A [Patent Document 3] International Publication No. 2006 / 106960 [Patent Document 4] International Publication No. 2009 / 025246 [Non-patent literature]

[0009] [Non-Patent Document 1] Asahi Glass Research Report, Vol. 60 (2010), pp. 13-21 Summary of the Invention [Problem to be solved by the invention]

[0010] Patent Document 3 describes that the crude reaction product containing FO2SCF2CF2SO2F synthesized by the electrolytic coupling reaction may be purified by post-treatment such as distillation, but does not describe or suggest any specific post-treatment for reducing the content of specific by-products contained in the final product, compound (1A), and improving the heat resistance properties (low mass loss rate at high temperatures). According to Patent Document 3, the general formula (1A): [ka] In the formula, R may be the same or different and each represents a fluorine atom or a trifluoromethyl group, n represents an integer of 1 to 4, and M 1 is Li, Na, K, or NH4.} (hereinafter, also referred to as compound (1A) in this specification) is produced, the compound represented by the following general formula (2): H(CR2) m -SO2NHM 2 (2) In the formula, R may be the same or different and is a fluorine atom or a trifluoromethyl group, m is 1 or 2, and M 2 is Li, Na, K, H or NH4.} is mixed into the final product as a by-product (impurity), and as a result, the desired heat resistance of compound (1A) cannot be obtained.

[0011] As an example of the limited existing technology relating to the crystallization of a fluorinated cyclic sulfonylimide salt, Patent Document 4 describes an example of crystallization purification of a lithium salt in a mixed solvent in which 1,4-dioxane is used as a poor solvent and acetonitrile is used as a good solvent.

[0012] Furthermore, the techniques described in Patent Documents 1 to 3 have problems in sufficiently suppressing metal corrosion of non-aqueous secondary battery components, and in terms of initial charge / discharge efficiency and cycle performance.

[0013] In view of the above circumstances, an object of the present invention is to provide a fluorine-containing cyclic sulfonylimide salt and a nonaqueous electrolyte solution which are excellent in heat resistance and have reduced metal corrosiveness. [Means for solving the problem]

[0014] Means for Solving the Problems The present inventors have conducted intensive research and repeated experiments to solve the above problems, and as a result have unexpectedly found that an alkali metal salt of a fluorinated cyclic sulfonimide having reduced amounts of specific impurities has excellent heat resistance properties and reduces metal corrosiveness, thereby completing the present invention.

[0015] That is, the present invention is as follows. <1> A non-aqueous electrolyte solution containing a non-aqueous electrolyte solvent and a lithium salt, The non-aqueous solvent comprises a carbonate solvent; The lithium salt is represented by the following general formula (1): [ka] {where, R f may be the same or different and each represents a fluorine atom or a perfluoro group having 4 or less carbon atoms. The present invention relates to a fluorine-containing cyclic sulfonylimide salt represented by the formula: The following general formula (2): H(CR2) m -SO2NHM 2 (2) In the formula, R may be the same or different and each represents a fluorine atom or a trifluoromethyl group; M 2 is Li, Na, K, H or NH4, and m is 1 or 2. The non-aqueous electrolyte solution contains a fluorine-containing sulfonamide compound represented by the following formula (1): <2> The fluorine-containing cyclic sulfonylimide salt represented by the general formula (1) is represented by the following formulas (1-1) to (1-5): [ka] 2. The nonaqueous electrolyte according to claim 1, <3> 3. The non-aqueous electrolyte solution according to item 1 or 2, containing the fluorine-containing sulfonamide compound represented by the general formula (2) in an amount of 0.1 ppm by mass or more based on the total amount of the non-aqueous electrolyte solution. <4> 4. The nonaqueous electrolyte solution according to any one of items 1 to 3, wherein the nonaqueous solvent contains acetonitrile in an amount of 3 vol% to 97 vol% based on the total amount of the nonaqueous solvent. <5> 5. The nonaqueous electrolyte solution according to item 4, wherein the content of the acetonitrile is 20% by volume or more and 95% by volume or less with respect to the total amount of the nonaqueous solvent. <6> 6. The non-aqueous electrolyte solution according to any one of items 1 to 5, comprising the fluorine-containing sulfonamide compound represented by the general formula (2) in an amount of 1 ppm by mass or more and 200 ppm by mass or less based on the total amount of the non-aqueous electrolyte solution. <7> 7. The nonaqueous electrolyte solution according to any one of items 1 to 6, wherein the content of the fluorine-containing cyclic sulfonylimide salt represented by the general formula (1) is 0.8 mol or more and 1.5 mol or less per 1 L of the nonaqueous solvent. <8> 8. The non-aqueous electrolyte solution according to any one of items 1 to 7, comprising the fluorine-containing sulfonamide compound represented by the general formula (2) in an amount of 80 ppm by mass or more and 120 ppm by mass or less based on the total amount of the non-aqueous electrolyte solution. <9> The lithium salt contains a fluorine-containing cyclic sulfonylimide salt represented by the general formula (1) and LiPF6, the non-aqueous solvent contains vinylene carbonate and / or fluoroethylene carbonate, The content of the fluorine-containing cyclic sulfonylimide salt represented by the general formula (1) is 2.5 or more in terms of molar ratio to the content of the LiPF6, and 9. The nonaqueous electrolyte solution according to any one of items 1 to 8, wherein the content of LiPF6 is in a molar ratio of 0.01 to 4 relative to the contents of vinylene carbonate and fluoroethylene carbonate. <10> 10. The nonaqueous electrolyte solution according to any one of items 1 to 9, wherein the content of the fluorine-containing cyclic sulfonylimide salt represented by the general formula (1) is greater than 10 in terms of molar ratio to the content of LiPF6. <11> A non-aqueous secondary battery comprising the non-aqueous electrolyte solution according to any one of items 1 to 10. <12> Item 12. The nonaqueous secondary battery according to item 11, wherein the nonaqueous secondary battery includes a battery exterior, and the battery exterior contains aluminum in at least a part of a layer on a positive electrode side that contacts the nonaqueous electrolyte. <13> The following general formula (3): MO2C-(CR2) m -SO2F (3) starting from a fluorosulfonyl group-containing carboxylic acid compound represented by the formula (1) {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, m is 1 or 2, and M is H, Li, Na, K, or NH4}, through an electrolytic coupling reaction step, a cyclization step, and a cation exchange step, a fluorine-containing cyclic sulfonylimide salt represented by the formula (1) is produced, The method includes a mixing step of mixing the fluorine-containing cyclic sulfonylimide salt represented by the general formula (1) with a non-aqueous solvent, After the electrolytic coupling reaction step, the compound represented by the following general formula (5): H-(CR2) m -SO2F (5) 11. The method for producing a nonaqueous electrolyte solution according to any one of items 1 to 10, further comprising a purification step of reducing a fluorosulfonyl group-containing compound represented by the formula: {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2} to 0.1 mass % or less in the reaction solution. <14> The following general formula (3): MO2C-(CR2) m -SO2F (3) starting from a fluorosulfonyl group-containing carboxylic acid compound represented by the formula (1) {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, m is 1 or 2, and M is H, Li, Na, K, or NH4}, through an electrolytic coupling reaction step, a cyclization step, and a cation exchange step, a fluorine-containing cyclic sulfonylimide salt represented by the formula (1) is produced, a crystallization step of dissolving the fluorine-containing cyclic sulfonylimide salt represented by the general formula (1) obtained after the cation exchange step in a monodentate chain ether solvent and then crystallizing the solution to obtain a purified fluorine-containing cyclic sulfonylimide salt; 11. A method for producing a non-aqueous electrolyte solution according to any one of items 1 to 10, comprising a mixing step of mixing the fluorine-containing cyclic sulfonylimide salt represented by general formula (1) obtained in the crystallization step with a non-aqueous solvent. <15> The following general formula (1A): [ka] In the formula, R may be the same or different and each represents a fluorine atom or a trifluoromethyl group, n represents an integer of 1 to 4, and M 1 is Li, Na, K, or NH}, A fluorine-containing cyclic sulfonylimide salt composition, characterized in that when heated in a nitrogen stream from 100°C at a heating rate of 10°C / min, the temperature at which a mass loss rate becomes 2% by mass is 385°C or higher. <16> The following general formula (2): H(CR2) m -SO2NHM 2 (2) In the formula, R may be the same or different and each represents a fluorine atom or a trifluoromethyl group; M 2is Li, Na, K, H or NH4, and m is 1 or 2. Item 16. The fluorine-containing cyclic sulfonylimide salt composition according to item 15, containing 5000 ppm by mass or less of a fluorine-containing sulfonamide compound represented by the following formula: <17> Item 17. The fluorine-containing cyclic sulfonylimide salt composition according to item 16, wherein in the general formula (1A), n is 2. <18> Item 18. The fluorine-containing cyclic sulfonylimide salt composition according to item 16 or 17, wherein in the general formulae (1A) and (2), R is a fluorine atom. <19> In the general formula (1A), M 1 is Li, and in the general formula (2), M 2 19. The fluorine-containing cyclic sulfonylimide salt composition according to any one of Items 16 to 18, wherein is Li. <20> The fluorine-containing cyclic sulfonylimide salt is represented by the following formula: [ka] 20. The fluorine-containing cyclic sulfonylimide salt composition according to any one of items 15 to 19, represented by the following formula: <21> The following general formula (3): MO2C-(CR2) m -SO2F (3) Starting from a fluorosulfonyl group-containing carboxylic acid compound represented by the formula (1A): {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, m is 1 or 2, and M is H, Li, Na, K, or NH4}, a compound represented by the following general formula (1A) is obtained through an electrolytic coupling reaction step, a cyclization step, and a cation exchange step: [ka] In the formula, R may be the same or different and each represents a fluorine atom or a trifluoromethyl group, n represents an integer of 1 to 4, and M 1is Li, Na or K}, in the method for producing a fluorine-containing cyclic sulfonylimide salt represented by the following general formula (5): H-(CR2) m -SO2F (5) {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2}, and the amount of the fluorosulfonyl group-containing compound in the reaction solution is reduced to 0.1 mass % or less. <22> The following general formula (3): MO2C-(CR2) m -SO2F (3) Starting from a fluorosulfonyl group-containing carboxylic acid compound represented by the formula (1A): {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, m is 1 or 2, and M is H, Li, Na, K, or NH4}, a compound represented by the following general formula (1A) is obtained through an electrolytic coupling reaction step, a cyclization step, and a cation exchange step: [ka] In the formula, R may be the same or different and each represents a fluorine atom or a trifluoromethyl group, n represents an integer of 1 to 4, and M 1 is Li, Na or K}, the method comprising a crystallization step of dissolving the fluorine-containing cyclic sulfonylimide salt obtained after the cation exchange step in a monodentate chain ether solvent and then crystallizing the solution to obtain a purified fluorine-containing cyclic sulfonylimide salt. <23> Item 23. The method according to Item 22, wherein the monodentate chain ether solvent used in the crystallization is at least one solvent selected from the group consisting of ethyl ether, propyl methyl ether, propyl ethyl ether, propyl ether, isopropyl methyl ether, isopropyl ethyl ether, isopropyl ether, butyl methyl ether, butyl ethyl ether, isobutyl methyl ether, isobutyl ethyl ether, sec-butyl methyl ether, sec-butyl ethyl ether, tert-butyl methyl ether, tert-butyl ethyl ether, pentyl methyl ether, isopentyl methyl ether, sec-pentyl methyl ether, tert-pentyl methyl ether, neopentyl methyl ether, and cyclopentyl methyl ether. <24> 24. The method according to item 22 or 23, wherein n in the general formula (1A) is 2. <25> 25. The method according to any one of Items 22 to 24, wherein R in the general formula (1A) is F. <26> 26. The method according to any one of items 22 to 25, wherein M in general formula (1A) is Li. <27> 27. The method according to any one of items 21 to 26, wherein in the electrolytic coupling reaction step, the fluorosulfonyl group-containing carboxylic acid compound represented by the general formula (3) is subjected to an electrolytic coupling reaction in the presence of a mixed solvent of water and a nitrile group-containing solvent, in which the ratio (β / α) of the mass of water (α) to the mass of the nitrile group-containing solvent (β) is 0.80 or less. <28> Item 28. The method according to item 27, wherein the ratio (β / α) of the mass (α) of water to the mass (β) of the nitrile group-containing solvent is 0.75 or less. <29> In the electrolytic coupling reaction step, the fluorosulfonyl group-containing carboxylic acid compound represented by the general formula (3) is subjected to an electrolytic coupling reaction in a reaction vessel in the presence of a mixed solvent of water and a nitrile group-containing solvent, 29. The method according to any one of Items 21 to 28, wherein during the reaction, a height (distance) TL from the bottom of the reaction vessel to the liquid level of the reaction liquid and a height (distance) TE from the bottom of the reaction vessel to the upper part (highest position) of the electrode satisfy a relationship of TL>TE, and after the reaction, a height (distance) TS from the bottom of the reaction vessel to the interface between the organic phase and the aqueous phase and a height (distance) TE' from the bottom of the reaction vessel to the lower part (lowest position) of the electrode satisfy a relationship of TE'>TS. <30> 30. The method according to item 29, wherein the relationship between TE' and TS is TE'×0.6>TS. <31> 31. The method according to any one of Items 27 to 30, wherein the content of alkali metal in the reaction solution in the electrolytic coupling reaction is 2000 ppm by mass or less. <32> In the electrolytic coupling reaction step, the production molar ratio of the compound represented by the above general formula (5) is the following general formula (4): FO2S-(CR2) m -SO2F (4) The method according to any one of items 27 to 31, wherein the amount of the fluorosulfonyl group is 0.01 or less relative to 1 mole of the produced amount of the bis(fluorosulfonyl) compound (4) represented by the formula: {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2}. <33> 33. The method according to any one of items 27 to 32, characterized in that in the electrolytic coupling reaction step, the fluorosulfonyl group-containing carboxylic acid compound represented by the general formula (3) is subjected to an electrolytic coupling reaction in the presence of a mixed solvent of water and a nitrile group-containing solvent, and the ratio (δ / γ) of the mass (γ) of the fluorosulfonyl group-containing carboxylic acid compound to the mass (δ) of the mixed solvent is 1.5 or less. <34> 34. The method according to any one of items 27 to 33, wherein in the electrolytic coupling reaction, the electrode plate distance between the anode and the cathode is 0.001 mm to 9.9 mm. <35> 35. The method according to item 33 or 34, wherein the yield of compound (4) in the electrolytic coupling reaction is 70% or more. <36> 36. The method according to any one of Items 27 to 35, wherein the nitrile group-containing solvent is at least one selected from the group consisting of acetonitrile, propionitrile, butyronitrile, and benzonitrile. <37> 37. The method of claim 36, wherein the nitrile group-containing solvent is acetonitrile. <38> 38. The method according to any one of items 27 to 37, wherein the electrolytic coupling reaction is carried out at a reaction temperature in the range of −35° C. or more and 10° C. or less. Effect of the Invention

[0016] The fluorine-containing cyclic sulfonylimide salt according to the present invention has high heat resistance, can be used in a wide temperature range, and has low metal corrosivity. Furthermore, according to the present invention, a nonaqueous electrolyte solution having low metal corrosivity, excellent initial charge-discharge efficiency, and excellent cycle performance can be provided. [Brief description of the drawings]

[0017] [Figure 1] 1 is a plan view illustrating a schematic example of a nonaqueous secondary battery according to an embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view taken along line AA of the nonaqueous secondary battery of FIG. 1. [Diagram 3] 1 is a scanning electron microscope (SEM) photograph (magnification 40x) of the surface of a positive electrode aluminum (Al) current collector of a coin-type nonaqueous secondary battery prepared using the nonaqueous electrolyte solution used in Example II-1 after a cycle test. [Figure 4] 1 is a SEM photograph (magnification 1000 times) of the surface of a positive electrode Al current collector of a coin-type nonaqueous secondary battery produced using the nonaqueous electrolyte solution used in Example II-1 after a cycle test. [Diagram 5] 1 is a SEM photograph (magnification 40 times) of the surface of a positive electrode Al current collector of a coin-type nonaqueous secondary battery produced with the nonaqueous electrolyte solution used in Comparative Example II-1 after a cycle test. [Figure 6] 1 is a SEM photograph (magnification 1000 times) of the surface of a positive electrode Al current collector of a coin-type nonaqueous secondary battery produced with the nonaqueous electrolyte solution used in Comparative Example II-1 after a cycle test. [Figure 7] 1 is a SEM photograph (magnification 40 times) of the surface of a positive electrode Al current collector of a coin-type nonaqueous secondary battery produced with the nonaqueous electrolyte solution used in Comparative Example II-3 after a cycle test. [Figure 8] 1 is a SEM photograph (magnification 1000 times) of the surface of a positive electrode Al current collector of a coin-type nonaqueous secondary battery produced with the nonaqueous electrolyte solution used in Comparative Example II-3 after a cycle test. [Figure 9] 1 is a SEM photograph (magnification 10,000 times) of the surface of a positive electrode Al current collector of a coin-type nonaqueous secondary battery produced with the nonaqueous electrolyte solution used in Comparative Example II-3 after a cycle test. [Figure 10] 1 is a diagram showing an example of the arrangement of a reaction solution, electrodes, etc. in a reaction vessel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. The present invention is not limited to the following embodiment, and various modifications are possible without departing from the gist of the present invention. In this specification, a numerical range described using "~" includes the numerical values ​​described before and after it.

[0019] One embodiment of the present invention is a compound represented by the following general formula (1A): [ka] In the formula, R may be the same or different and each represents a fluorine atom or a trifluoromethyl group, n represents an integer of 1 to 4, and M 1 is Li, Na, K or NH}, and is characterized in that when heated in a nitrogen stream from 100°C at a temperature increase rate of 10°C / min, the temperature at which a mass loss rate becomes 2% by mass is 385°C or higher. Compound (1A) will be described in detail below.

[0020] <Composition containing fluorine-containing cyclic sulfonylimide salt (compound (1A))> In general formula (1A), n is an integer of 1 to 4 from the viewpoints of ease of availability or production and excellent economy, and from the same viewpoints, n is preferably an integer of 1 to 3, more preferably 1 or 2, and most preferably 2. R may be the same or different, and from the viewpoints of ease of availability or production and excellent economy, is a fluorine atom or a trifluoromethyl group, and a fluorine atom is most preferable. M 1 is Li, Na, K or NH4 (that is, alkali metal ion, ammonium ion) from the viewpoint of ease of availability or production and excellent economy, preferably Li or Na, and most preferably Li. Specific examples of compound (1A) include those having the following structural formula: [ka] or [ka] Examples of the compound include compounds represented by the following formula: Among these are the following structural formulas: [ka] Preferred is a compound represented by the following formula:

[0021] When the composition containing the compound (1A) is heated under a nitrogen gas flow from 100°C at a heating rate of 10°C / min, the 2% mass loss temperature is preferably 385°C or higher, more preferably 390°C or higher, and most preferably 395°C or higher from the same viewpoint. The upper limit of the 2% mass loss temperature is not particularly limited, but may be 1000°C or lower, or 500°C or lower. Here, the 2% mass loss temperature is the temperature at which the mass loss rate relative to the initial mass is 2% when thermogravimetric analysis is performed under the above conditions. In other words, the higher the 2% mass loss temperature, the less likely decomposition products are generated and the higher the heat resistance.

[0022] The 2% mass loss temperature is measured by heating from 25°C at a heating rate of 10°C / min, holding at 100°C for 30 minutes to evaporate volatile components such as moisture, and then heating from 100°C at a heating rate of 10°C / min to measure the 2% mass loss temperature. The temperature at which the mass decreases by 2% is determined based on the mass at the start of the heating from 100°C. An example of an apparatus that can be used to measure the 2% mass loss temperature is a simultaneous differential thermal and thermogravimetric analyzer (for example, "DTG-60A" manufactured by Shimadzu Corporation).

[0023] In addition, when the measurement sample contains moisture or residual solvent, it is difficult to obtain accurate measurement results. Therefore, the composition of compound (1A) used in the above measurement has a total content of moisture and residual solvent of preferably 2000 mass ppm or less, more preferably 1500 mass ppm or less, further preferably 1000 mass ppm or less, and most preferably 600 mass ppm or less from the same viewpoint. The above moisture content can be measured by an analytical instrument such as a Karl Fischer moisture meter, gas chromatography, or liquid chromatography.

[0024] A fluorine-containing cyclic sulfonylimide salt composition having a 2% mass loss temperature in a desired range can be obtained, for example, by purifying the reaction solution obtained in the electrolytic coupling reaction step by distillation to remove compound (5) as described below, or by purifying compound (1A) by crystallization. This composition can also be obtained by carrying out both the distillation purification and crystallization. Furthermore, the composition can be obtained by adding compound (2) after distillation or crystallization.

[0025] The content (purity) of compound (1A) in the fluorine-containing cyclic sulfonylimide salt composition of this embodiment is preferably 98.0 mass% or more, more preferably 99.0 mass% or more, and even more preferably 99.5 mass% or more.

[0026] The composition containing the fluorine-containing cyclic sulfonylimide salt (1A) of the present embodiment is a compound represented by the following general formula (2): H(CR2) m -SO2NHM 2 (2) In the formula, R may be the same or different and is a fluorine atom or a trifluoromethyl group, m is 1 or 2, and M 2 is Li, Na, K, H or NH4. The content of the fluorine-containing sulfonamide compound represented by the formula { is preferably 10000 mass ppm (1 mass%) or less. When the content of the compound (2) is within the above range, the heat resistance of the composition containing the compound (1A) is further improved, and the metal corrosivity is reduced, and the increase in irreversible capacity during charging and discharging and the decrease in cycle performance due to corrosion of the positive electrode Al current collector can be suppressed. From the same viewpoint, the content of the compound (2) is more preferably 5000 mass ppm or less, and most preferably 1000 mass ppm or less, based on the total amount of the fluorine-containing cyclic sulfonylimide salt (1A). The lower limit of the content of the compound (2) is not particularly limited, and may be 0 mass ppm or more, 0.001 mass ppm or more, 10 mass ppm or more, or 100 mass ppm or more, based on the total amount of the fluorine-containing cyclic sulfonylimide salt (1A).

[0027] The content of compound (2) is 19 It is calculated from the integrated value of the peak value of F-NMR. The content of compound (2) is measured by the internal standard method (internal standard substance: benzotrifluoride). The content of compound (2) is calculated by the following formula. Content of compound (2) (mass%)=(Im×Ci×Cmw) / (Ii×Ia)×100 (In the formula, Im = moles of internal standard = mass of benzotrifluoride in measured sample / molecular weight of benzotrifluoride Ii = integral value per 1F of internal standard = integral value of benzotrifluoride / number of fluorine atoms in benzotrifluoride Ci = integral value per 1F of compound (2) = integral value of compound (2) / number of fluorine atoms in compound (2) Cmw = molecular weight of compound (2) Ia = total mass of the composition containing the fluorine-containing cyclic sulfonylimide salt in the measurement sample For example, when the content of compound (2) in the non-aqueous electrolyte is 10 mass ppm or less and detection by the above internal standard method is difficult, the content of compound (2) in the original non-aqueous electrolyte can be calculated by tentatively calculating the content of compound (2) using the above internal standard method for a sample obtained by distilling off the solvent from 100 mL of the non-aqueous electrolyte and redissolving the solid sample in 0.5 mL of solvent, and multiplying the value by 200. Alternatively, the content of compound (2) in compound (1A) used as a raw material for the non-aqueous electrolyte can be calculated by calculating the content of compound (2) using the above internal standard method, and dividing by the dilution factor when compound (1A) is diluted to the concentration of compound (1A) in the non-aqueous electrolyte. The structural formula of compound (2) can be identified by one or a combination of common analytical techniques, including mass spectrometry, nuclear magnetic resonance, infrared spectroscopy, elemental analysis, ion chromatography, and ICP atomic emission spectrometry.

[0028] The fluorine-containing cyclic sulfonylimide salt having a desired content of compound (2) can be obtained, for example, by distilling and purifying the reaction solution obtained in the electrolytic coupling reaction step to remove compound (5) as described below, or by purifying compound (1A) by crystallization. Crystallization purification is preferred because it is highly effective in reducing compound (2), and metal corrosivity is further reduced. In addition, a fluorine-containing cyclic sulfonylimide salt composition and a non-aqueous electrolyte solution having a content of compound (2) within a desired range can also be obtained by post-adding compound (2) to the fluorine-containing cyclic sulfonylimide salt composition and the non-aqueous electrolyte solution.

[0029] In the general formula (2), R is defined as R in the general formula (1A). R is most preferably a fluorine atom. m is most preferably 1. M 2 is Li, Na, K or NH4 (i.e., an alkali metal ion, an ammonium ion), with Li or Na being preferred and Li being most preferred. Specific examples of compound (2) include compounds represented by the following structural formulas: Among these, HCF2SO2NHLi (compound (2-1)) and HF2CSO2NHNH4 (compound (2-2)) are preferred, and HCF2SO2NHLi (compound (2-1)) is the most preferred. [ka]

[0030] <Method of producing fluorine-containing cyclic sulfonylimide salt (compound (1A))> As described above, the method for producing compound (1A) can be a conventionally known method, for example, the method described in Patent Document 3. The reaction scheme for compound (1A) is shown below, taking the case where R is a fluorine atom and n is 2 as an example. This method, as shown in the upper part of the reaction scheme below, comprises reacting a compound represented by the following general formula (3): HO2C-(CR2) m -SO2F (3) In this method, starting from a fluorosulfonyl group-containing carboxylic acid compound represented by the formula: {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2} (hereinafter also referred to as compound (3)), compound (4) is obtained through an electrolytic coupling reaction step, compound (1-N) is obtained through a cyclization step, and finally compound (1A) is produced through a cation exchange step. 1 If =NH4, the cation exchange step can be omitted. [ka] However, the conventional method reduces the content of compound (2), and compound (1A) having the desired heat resistance cannot be obtained. As shown in the lower part of the reaction scheme, compound (5) generated as a by-product in the electrolytic coupling reaction step generates compound (2-N) in the cyclization step, and then undergoes a reaction in the cation exchange step to generate compound (2). As a result of intensive research and repeated experiments, the inventors of the present application have found that in order to improve the heat resistance and reduce the metal corrosiveness of the final product, compound (1A) composition, it is sufficient to adjust the content of compound (2) in the compound (1A) composition to a predetermined value or less, as described above. Furthermore, in order to achieve this, as shown in the lower part of the above reaction scheme, it was found that the concentration of a fluorosulfonyl group-containing compound (compound (5)) generated as a by-product in the electrolytic coupling reaction step should be reduced to 0.1 mass% or less in the reaction solution obtained in the step, and this led to the completion of the present invention.

[0031] That is, another embodiment of the present invention is a compound represented by the following general formula (3): HO2C-(CR2) m -SO2F (3) {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2.}, and a fluorosulfonyl group-containing carboxylic acid compound represented by the following general formula (1A): [ka] In the formula, R may be the same or different and each represents a fluorine atom or a trifluoromethyl group, n represents an integer of 1 to 4, and M 1 is Li, Na or K. In the method for producing a fluorine-containing cyclic sulfonylimide salt represented by the following general formula (5): H-(CR2) m -SO2F (5) {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2.} to 0.1 mass % or less in the reaction solution. Compound (5) is a compound represented by the following general formula (4): FO2S-(CR2) m -SO2F (4) {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2.}

[0032] Furthermore, the present inventors have found that in order to adjust the content of compound (2) in the compound (1A) composition to a predetermined value or less, the fluorine-containing cyclic sulfonylimide salt (1A) obtained after the cation exchange step can be dissolved in a monodentate chain ether solvent and then purified by crystallization, thereby completing the present invention.

[0033] That is, another embodiment of the present invention is The method for producing a fluorine-containing cyclic sulfonylimide salt represented by the general formula (1A) starting from a fluorosulfonyl group-containing carboxylic acid compound represented by the general formula (3) through an electrolytic coupling reaction step, a cyclization step, and a cation exchange step, comprises a crystallization step of dissolving the fluorine-containing cyclic sulfonylimide salt obtained after the cation exchange step in a monodentate chain ether solvent and then crystallizing the solution to obtain a purified fluorine-containing cyclic sulfonylimide salt.

[0034] The manufacturing method will now be described in detail. <Electrolytic coupling reaction process> A bis(fluorosulfonyl) compound (compound (4)) can be produced by subjecting compound (3) to an electrolytic coupling reaction. Compound (3) may be a commercially available product, or a known method may be used, for example, a method in which SO3 is added to tetrafluoroethylene to obtain a sultone, a ring-opened sultone product is obtained in the presence of NEt3, and the ring-opened sultone product is hydrolyzed to obtain compound (3) as a sultone hydrolyzate.

[0035] In the general formula (3), R is defined as the same as R in the general formula (1A). R is most preferably a fluorine atom. m is most preferably 1. Specific examples of compound (3) include compounds represented by the following structural formulas: Among these, FO2SCF2CO2H (2,2-difluoro-2-(fluorosulfonyl)acetic acid, compound (3-1)) is preferred. [ka]

[0036] The reaction temperature of the electrolytic coupling reaction step is not particularly limited as long as it is within a generally used range, but is preferably -50°C or higher and 70°C or lower. When the reaction temperature is -50°C or higher, the electrical resistance decreases and heat generation can be suppressed, which makes it easier to control the temperature, which is preferable. From the same viewpoint, the reaction temperature is more preferably -40°C or higher, more preferably -35°C or higher, and most preferably -30°C or higher. When the reaction temperature is 70°C or lower, the decomposition of compound (3) and compound (4) can be suppressed, and the yield of compound (4) tends to be higher, which is preferable. From the same viewpoint, the reaction temperature is more preferably 50°C or lower, more preferably 40°C or lower, and most preferably 10°C or lower.

[0037] In the electrolytic coupling reaction step, a solvent may be used. The above-mentioned solvent is not particularly limited as long as it is a commonly used solvent. Specific examples thereof include aromatic solvents such as benzene, toluene, chlorobenzene, and 1,2-dichlorobenzene; ether group-containing solvents such as 1,2-dimethoxyethane, 1,2-diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 4-methyltetrahydropyran, cyclopentyl methyl ether, and anisole; nitrile group-containing solvents such as acetonitrile, propionitrile, butyronitrile, and benzonitrile; hydroxyl group-containing solvents such as water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and 2-butanol; and carbonate group-containing solvents such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and propylene carbonate. Among these, nitrile solvents such as acetonitrile, propionitrile, butyronitrile, and benzonitrile, hydroxyl group-containing solvents such as water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and 2-butanol, and carbonate group-containing solvents such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and propylene carbonate are preferred because they tend to increase the yield of compound (4). These solvents may be used alone or in combination, and since the yield of compound (4) tends to be higher, a mixed solvent of water and a nitrile group-containing solvent or a mixed solvent of water and a carbonate group-containing solvent is preferred, a mixed solvent of water and a nitrile group-containing solvent is more preferred, and a mixed solvent of water and acetonitrile is most preferred. The amount of acetonitrile in the solvent is preferably 0.5 to 90 mass%.

[0038] In this embodiment, it is preferable to produce a bis(fluorosulfonyl) compound represented by the above general formula (4) by subjecting a fluorosulfonyl group-containing carboxylic acid compound represented by the above general formula (3) to an electrolytic coupling reaction in the presence of a mixed solvent of water and a nitrile group-containing solvent in which the ratio (β / α) of the mass of water (α) to the mass of the nitrile group-containing solvent (β) is 0.80 or less. When β / α is 0.80 or less, the production of compound (5) can be suppressed. From the same viewpoint, β / α is more preferably 0.75 or less, even more preferably 0.5 or less, even more preferably 0.2 or less, and even more preferably 0.1 or less. The lower limit of β / α is not particularly limited, but may be 0.01 or more, 0.03 or more, 0.05 or more, or 0.18 or more.

[0039] Patent Document 3 discloses a method for producing a bis(fluorosulfonyl) compound (FO2SCF2CF2SO2F) in one step by electrolytic coupling reaction using FOSCF2CO2H as a starting material. However, when a bis(fluorosulfonyl) compound is produced according to Patent Document 3, a fluorosulfonyl group-containing compound represented by general formula (5) is mixed in as a by-product. As described above, bis(fluorosulfonyl) compounds are used as catalysts and electrolytes, but in these fields, performance such as catalytic activity and electrical conductivity may be significantly reduced due to impurities mixed in in small amounts. Therefore, when a bis(fluorosulfonyl) compound is produced according to Patent Document 3, it is necessary to separate and remove the fluorosulfonyl group-containing compound by a purification operation such as distillation, and a method for producing a bis(fluorosulfonyl) compound with a low content of the fluorosulfonyl group-containing compound has been demanded.

[0040] We have unexpectedly found that compound (4) having a low content of a fluorosulfonyl group-containing compound (compound (5)) as a by-product can be obtained by adjusting the ratio (β / α) of the mass of water (α) to the mass of the nitrile group-containing solvent to a specific value or less, and have completed the present invention.

[0041] In this embodiment, the fluorosulfonyl group-containing carboxylic acid compound represented by the above general formula (3) is subjected to an electrolytic coupling reaction in a reaction vessel in the presence of a mixed solvent of water and a nitrile group-containing solvent to produce a bis(fluorosulfonyl) compound represented by the above general formula (4). During the reaction, the height (distance) TL from the bottom of the reaction vessel to the liquid level of the reaction liquid and the height (distance) TE from the bottom of the reaction vessel to the top of the electrode (highest position) satisfy the relationship TL>TE, and after the reaction, the height (distance) TS from the bottom of the reaction vessel to the interface between the organic phase and the aqueous phase and the height (distance) TE' from the bottom of the reaction vessel to the bottom of the electrode (lowest position) satisfy the relationship TE'>TS. This is a method for producing the bis(fluorosulfonyl) compound (compound (4)).

[0042] As shown in Fig. 10, in this embodiment, during the reaction, the height (distance) TL from the bottom of the reaction vessel to the liquid level of the reaction solution and the height (distance) from the bottom of the reaction vessel to the top of the electrode (highest position) satisfy the relationship TL>TE, and after the reaction, the height (distance) TS from the bottom of the reaction vessel to the interface between the organic phase and the aqueous phase and the height (distance) TE' from the bottom of the reaction vessel to the bottom of the electrode (lowest position) preferably satisfy the relationship TE'>TS. By TL and TE, and TE' and TS respectively satisfying the above relationship, a sudden increase in voltage during the electrolytic coupling reaction is suppressed, and the manufacturing method tends to be safer. From the same viewpoint, it is more preferable that TE' and TS satisfy the relationship TE'×0.8>TS, and it is most preferable that TE'×0.6>TS be further satisfied.

[0043] Patent Document 3 discloses a method for producing a bis(fluorosulfonyl) compound (FO2SCF2CF2SO2F) in one step by electrolytic coupling reaction using FOSCF2CO2H as a starting material. However, when a bis(fluorosulfonyl) compound is produced according to Patent Document 3, hunting, such as a sudden increase in voltage during the electrolytic coupling reaction, is observed, and there is a need to improve the stability of the electrolytic coupling reaction.

[0044] We have found that when, during the reaction, the height (distance) TL from the bottom of the reaction vessel to the liquid level of the reaction liquid and the height (distance) TE from the bottom of the reaction vessel to the top of the electrode (highest position) satisfy the relationship TL>TE, and when, after the reaction, the height (distance) TS from the bottom of the reaction vessel to the interface between the organic phase and the aqueous phase and the height (distance) TE' from the bottom of the reaction vessel to the bottom of the electrode (lowest position) satisfy the relationship TE'>TS, the occurrence of hunting can be suppressed and the reactor has excellent operational stability, which has led to the present invention.

[0045] In this embodiment, in the electrolytic coupling reaction step in which the fluorosulfonyl group-containing carboxylic acid compound represented by the above general formula (3) is subjected to an electrolytic coupling reaction in the presence of a mixed solvent of water and a nitrile group-containing solvent, the ratio (δ / γ) of the mass (γ) of the compound (3) to the mass (δ) of the mixed solvent is preferably 1.5 or less. If δ / γ is 1.5 or less, the yield of the compound (2) tends to be higher, which is preferable. From the same viewpoint, δ / γ is preferably 1.35 or less, and most preferably 1.00 or less. The lower limit of δ / γ is not particularly limited, but may be 0.01 or more, 0.05 or more, or 0.1 or more.

[0046] The electrode used in the electrolytic coupling reaction step is not particularly limited as long as it is a commonly used electrode, but from the viewpoint of suppressing decomposition of the solvent, a platinum electrode is preferable.

[0047] In this embodiment, in the electrolytic coupling reaction, the plate gap between the anode and the cathode is preferably 0.001 mm to 9.9 mm. When the plate gap is 0.001 mm or more, the electrolyte flows easily between the plates, and the yield of compound (4) tends to be higher, which is preferable. When the plate gap is 9.9 mm or less, the voltage is reduced, and side reactions are suppressed, which tends to increase the yield of compound (4), which is preferable. From the same viewpoint, the plate gap between the anode and the cathode is preferably 0.01 mm to 5 mm, and most preferably 0.1 mm to 2.9 mm.

[0048] Patent Document 3 discloses a method for producing a bis(fluorosulfonyl) compound (FO2SCF2CF2SO2F) in one step by electrolytic coupling reaction using FOSCF2CO2H as a starting material. However, Patent Document 3 does not specifically describe the mixing ratio of the raw material and the solvent during the electrolytic coupling reaction, or the electrode gap between the anode and the cathode. In fact, even if FOSCF2CO2H is used as a starting material and an electric current is applied, the yield of the bis(fluorosulfonyl) compound varies greatly depending on the mixing ratio of the raw material and the solvent, and depending on the electrode gap between the anode and the cathode, the target bis(fluorosulfonyl) compound may not be obtained at all.

[0049] We unexpectedly discovered that by setting the ratio (δ / γ) of the mass (γ) of the fluorosulfonyl group-containing carboxylic acid compound to the mass (δ) of the mixed solvent to a specific numerical value or less and setting the electrode distance between the anode and the cathode within a certain range, a bis(fluorosulfonyl) compound can be stably obtained in high yield, which led to the present invention.

[0050] In this embodiment, the content of alkali metal in the reaction solution in the electrolytic coupling reaction is preferably 2000 mass ppm or less. When the content of alkali metal is within this range, the decomposition of compound (3) is suppressed, and the yield of compound (4) tends to be higher. The content of alkali metal in the reaction solution is more preferably 1000 mass ppm or less, and further preferably 500 mass ppm or less.

[0051] In the electrolytic coupling reaction step, after the electrolytic coupling reaction of compound (3), the reaction product containing compound (3), compound (4), and the solvent can be separated from each other by any commonly used separation and removal method without any particular limitation. For example, separation and removal of volatile components by distillation, separation of liquid components by a liquid separation operation, separation and removal of insoluble solids by filtration, etc. can be mentioned. These methods may be used alone or in combination of two or more types.

[0052] In the electrolytic coupling reaction step, the target compound (4) is produced as a by-product, along with H-(CR2). m -SO2F {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2.} (compound (5)) may be generated. Compound (5) is converted to compound (2) through a cyclization step and a cation exchange step following the electrolytic coupling reaction step, and causes a decrease in the heat resistance of compound (1A). Furthermore, both compound (1A) and compound (2) are solids, and it is difficult to separate and remove compound (2) from a mixture of compound (1A) and compound (2). Therefore, it is preferable to reduce the amount of compound (5), which causes a decrease in the heat resistance of compound (1A), to 0.1 mass% or less in the reaction solution obtained in the electrolytic coupling reaction step after the step.

[0053] The detailed reason why the compound represented by general formula (5) is produced as a by-product during the electrolytic coupling reaction of compound (3) is not clear. However, as shown in the reaction scheme below, it is believed that the decarboxylation reaction of compound (3) is promoted by the interaction between the carboxyl group of compound (3) and the nitrile group of the solvent, and then compound (5) is produced by reaction with the solvent water. [ka]

[0054] The method for separating compound (4) and compound (5) from a mixture of the two compounds is not particularly limited, and any commonly used separation and removal method can be used, such as a separation method by distillation.

[0055] In the general formula (5), R is defined as the same as R in the general formula (1A). R is most preferably a fluorine atom. m is most preferably 1. Specific examples of compound (5) include compounds represented by the following structural formulas: Among these, HCF2SO2F (1,1-difluoromethanesulfonyl fluoride, compound (5-1)) is preferred. [ka]

[0056] The current density during electrolytic coupling was 0.001 A / cm 2 ~2.0A / cm 2 When the current density is within the above range, side reactions are suppressed, and the yield of compound (4) tends to be increased, which is preferable. From the same viewpoint, the current density is preferably 0.005 A / cm 2 ~1.5A / cm 2 More preferably, it is 0.01 A / cm 2 ~1.0A / cm 2 It is most preferable that: The electrolytic cell used in this embodiment is one that is commonly used in organic electrolytic reactions, and may be of a batch type or a continuous type in which the compound (3) and the like are continuously supplied.

[0057] The reaction time of the electrolytic coupling reaction step is not particularly limited as long as it is within a commonly used range, but is preferably 0.5 to 100 hours, and more preferably 1 to 50 hours. The pressure in the electrolytic coupling reaction step depends on the temperature at which the reaction is carried out, but is not particularly limited as long as it is within a commonly used range, and is preferably 10 kPa to 5000 kPa. The reaction atmosphere is not particularly limited as long as it is a commonly used atmosphere, but usually, air atmosphere, nitrogen atmosphere, argon atmosphere, etc. are used. Among these, nitrogen atmosphere and argon atmosphere are preferred because they tend to produce compound (4) more safely. In addition, nitrogen atmosphere is more preferred because they tend to be a more economical production method. The reaction atmosphere may be used alone or in combination of a plurality of reaction atmospheres.

[0058] During the electrolytic coupling reaction, a supporting electrolyte may be added. The supporting electrolyte is not particularly limited as long as it is a commonly used supporting electrolyte, but specific examples include metal hydroxides such as lithium hydroxide, sodium hydroxide, and potassium hydroxide, sulfates such as sodium sulfate and potassium sulfate, acidic compounds such as nitric acid, sulfuric acid, and hydrochloric acid, perchlorates such as sodium perchlorate and ammonium perchlorate, and quaternary ammonium salts such as tetramethylammonium bromide and tetrabutylammonium paratoluenesulfonate.

[0059] In the production method of this embodiment, the molar ratio of compound (5) produced in the electrolytic coupling reaction is preferably 0.01 or less per mole of compound (4). The molar ratio of compound (5) produced is more preferably 0.008 or less, even more preferably 0.005 or less, and even more preferably 0.003 or less. This molar ratio can be achieved by carrying out the electrolytic coupling reaction in a predetermined β / α range as described above. The molar ratio can be determined by calculating the ratio of the reaction solution after electrolytic coupling. 19 It can be determined by measuring with F-NMR. Specific conditions are described in the Examples.

[0060] The yield of compound (4) in the electrolytic coupling reaction step is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, and particularly preferably 90% or more. By carrying out the electrolytic coupling reaction step with the above-mentioned yield of compound (4), the production cost of compound (4) can be reduced and the production amount per unit time can be improved.

[0061] <Cyclization process> By reacting compound (4) with ammonia, a compound represented by the following general formula (1-N): [ka] It is possible to produce a fluorine-containing cyclic sulfonylimide ammonium salt (compound (1-N)) represented by the following formula: {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and n is an integer of 1 to 4}.

[0062] In the general formula (4), R is defined as the same as R in the general formula (1A). R is most preferably a fluorine atom. m is most preferably 1.

[0063] Specific examples of compound (4) include compounds represented by the following structural formula: Among these, FO2SCF2CF2SO2F (1,1,2,2-tetrafluoro-1,2-ethanedisulfonyl difluoride, compound (4-1)) is preferred. [ka]

[0064] The molar ratio (μ / λ) of the amount of substance (λ) of compound (4) to the amount of substance (μ) of ammonia is not particularly limited as long as it is within a range that is generally used, but is preferably 2 to 50. When μ / λ is 2 or more, the yield of compound (1-N) tends to be higher, which is preferable. When δ / γ is 50 or less, waste can be reduced, which tends to result in a more economical production method, which is preferable. From the same viewpoint, μ / λ is more preferably 5 to 40, and most preferably 10 to 30.

[0065] In the cyclization step, a solvent may be used. The solvent is not particularly limited as long as it is inert during the reaction and is commonly used, and specific examples include aromatic solvents such as benzene, toluene, chlorobenzene, and 1,2-dichlorobenzene; ether group-containing solvents such as 1,2-dimethoxyethane, 1,2-diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 4-methyltetrahydropyran, cyclopentyl methyl ether, and anisole; nitrile group-containing solvents such as acetonitrile, propionitrile, and benzonitrile; and hydroxyl group-containing solvents such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and 2-butanol. Among them, ether group-containing solvents such as 1,2-dimethoxyethane, 1,2-diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 4-methyltetrahydropyran, cyclopentyl methyl ether, and anisole are more preferred because they tend to increase the yield of compound (1-N). From the same viewpoint, 1,2-dimethoxyethane, tetrahydrofuran, 1,4-dioxane, and 4-methyltetrahydropyran are more preferred, and 1,2-dimethoxyethane, tetrahydrofuran, and 4-methyltetrahydropyran are even more preferred. These organic solvents may be used alone or in combination of two or more kinds of solvents.

[0066] The ratio (ζ / ε) of the mass (ε) of compound (4) to the mass (ζ) of the solvent is not particularly limited as long as it is within a commonly used range, but is preferably 0.01 to 100. When ζ / ε is within the above range, the yield of compound (1-N) tends to be higher. From the same viewpoint, ζ / ε is more preferably 0.05 to 50, and further preferably 0.1 to 10.

[0067] The reaction temperature of the cyclization step is not particularly limited as long as it is within a commonly used range, but is preferably -90°C to 20°C. A reaction temperature of -90°C or higher is preferable because it increases the reactivity of compound (4) and tends to increase the yield of compound (1-N). A reaction temperature of 20°C or lower is preferable because it suppresses by-products and tends to increase the yield of compound (1-N). From the same viewpoint, the reaction temperature is more preferably -80°C to 10°C, and most preferably -80°C to 0°C.

[0068] The reaction time for the cyclization step is not particularly limited as long as it is within a commonly used range, but is preferably 1 to 100 hours, and more preferably 5 to 50 hours. The pressure in the cyclization step depends on the reaction temperature, but is not particularly limited as long as it is within a commonly used range, and is preferably 10 kPa to 5000 kPa. The reaction atmosphere is not particularly limited as long as it is a commonly used atmosphere, but usually, air atmosphere, nitrogen atmosphere, argon atmosphere, etc. are used. Among these, nitrogen atmosphere and argon atmosphere are preferred because they tend to produce compound (1-N) more safely. In addition, nitrogen atmosphere is more preferred because they tend to be a more economical production method. The reaction atmosphere may be used alone or in combination of a plurality of reaction atmospheres.

[0069] In the cyclization step, after the reaction of compound (4) with ammonia, the compound (1-N) and the solvent may be separated from the reaction product containing them by any commonly used separation and removal method without any particular limitation. For example, separation and removal of volatile components by distillation, separation of liquid components by a liquid separation operation, separation and removal of insoluble solids by filtration, etc. may be mentioned. These methods may be used alone or in combination of two or more types.

[0070] <Cation exchange process> Compound (1-N) and the following general formula (6): M 1 pX (6) (In the formula, M 1 is Li, Na or K, X is OH or CO3, and p is 1 when X is OH, and is 2 when X is CO3 (hereinafter also referred to as compound (6)) to produce compound (1A).

[0071] In the following general formula (1-N), R is defined as R in general formula (1A). R is most preferably a fluorine atom. n is preferably 1 or 2, and most preferably 2. m is most preferably 1. n in formula (1-N) is an integer of 1 to 4.

[0072] Specific examples of the compound (1-N) include compounds represented by the following general formulas (1-N-1) to (1-N-5): [ka] Among these, the ammonium salt represented by (1-N-2) is preferable. [ka]

[0073] The molar ratio (θ / η) of the amount of substance (η) of compound (1-N) to the amount of substance (θ) of compound (6) is not particularly limited as long as it is within a commonly used range, but is preferably 0.2 to 10. When θ / η is 0.2 or more, the yield of compound (1A) tends to be higher, which is preferable. When θ / η is 10 or less, waste can be reduced, which tends to result in a more economical production method, which is preferable. From the same viewpoint, θ / η is more preferably 0.5 to 5, and most preferably 0.8 to 3.

[0074] A solvent may be used in the cation exchange step. The solvent is not particularly limited as long as it is inert during the reaction and is commonly used, and specific examples include aromatic solvents such as benzene, toluene, chlorobenzene, and 1,2-dichlorobenzene; ether group-containing solvents such as 1,2-dimethoxyethane, 1,2-diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 4-methyltetrahydropyran, cyclopentyl methyl ether, and anisole; nitrile group-containing solvents such as acetonitrile, propionitrile, and benzonitrile; and hydroxyl group-containing solvents such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and 2-butanol. Among them, ether group-containing solvents such as 1,2-dimethoxyethane, 1,2-diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 4-methyltetrahydropyran, cyclopentyl methyl ether, and anisole are more preferred because they tend to increase the yield of compound (1A). From the same viewpoint, 1,2-dimethoxyethane, tetrahydrofuran, 1,4-dioxane, and 4-methyltetrahydropyran are more preferred, and 1,2-dimethoxyethane, tetrahydrofuran, and 4-methyltetrahydropyran are even more preferred. These organic solvents may be used alone or in combination of two or more kinds of solvents.

[0075] The ratio (κ / ι) of the mass (ι) of the compound (1-N) to the mass (κ) of the solvent is not particularly limited as long as it is within a commonly used range, but is preferably 0.01 to 100. When κ / ι is within the above range, the yield of the compound (1A) tends to be higher. From the same viewpoint, it is more preferably 0.05 to 50, and even more preferably 0.1 to 10.

[0076] The reaction temperature of the cation exchange step is not particularly limited as long as it is within a generally used range, but is preferably 0°C to 150°C. A reaction temperature of 0°C or higher is preferable because it increases the reactivity of compound (1-N) and tends to increase the yield of compound (1A). A reaction temperature of 150°C or lower is preferable because it suppresses by-products and tends to increase the yield of compound (1A). From the same viewpoint, the reaction temperature is more preferably 20°C to 140°C, and most preferably 40°C to 130°C.

[0077] The reaction time for the cation exchange step is not particularly limited as long as it is within a commonly used range, but is preferably 1 to 100 hours, and more preferably 5 to 50 hours. The pressure in the cation exchange step depends on the reaction temperature, but is not particularly limited as long as it is within a commonly used range, and is preferably 10 kPa to 5000 kPa. The reaction atmosphere is not particularly limited as long as it is a commonly used atmosphere, but usually, air atmosphere, nitrogen atmosphere, argon atmosphere, etc. are used. Among these, nitrogen atmosphere and argon atmosphere are preferred because they tend to produce compound (1A) more safely. In addition, nitrogen atmosphere is more preferred because they tend to be a more economical production method. The reaction atmosphere may be used alone or in combination of a plurality of reaction atmospheres.

[0078] <Crystallization step of fluorine-containing cyclic sulfonylimide salt (compound (1A))> Generally, fluorine-containing cyclic sulfonylimide salts have extremely high solubility in water and various organic solvents with coordinating properties, which is advantageous for their use in a wide range of applications, such as antistatic agents, ion-conducting materials such as organic electrolytes, and flame retardants. On the other hand, this high solubility is directly linked to low crystallinity and an increase in the amount of solvent remaining during drying. Crystallization is one of the most common and simple production methods for highly purifying powder substances such as fluorine-containing cyclic sulfonylimide salts, but the low crystallinity and the increase in the amount of solvent remaining are problems, and existing technologies related to the high purification of fluorine-containing cyclic sulfonylimide salts by crystallization are limited.

[0079] Patent Document 4 describes an example of crystallization purification of lithium salts in a mixed solvent of 1,4-dioxane as a poor solvent and acetonitrile as a good solvent. However, in the method of Patent Document 1, about 5% by mass of 1,4-dioxane remains in the crystals after drying, and there is a problem that it takes a long time and costs to remove the remaining solvent. This problem is essentially due to the use of 1,4-dioxane, a cyclic ether having two oxygen atoms, which causes the solvent to be strongly coordinated to lithium in the crystalline state. Patent Document 4 describes a high-purification method in which the same fluorine-containing cyclic sulfonylimide ammonium salt is suspended, filtered, and washed in 1,4-dioxane, but there is no description regarding the amount of remaining solvent after drying, and it is unclear whether this method contributes to solving the problem related to the amount of remaining solvent.

[0080] In addition, the inventors of the present invention have actually attempted crystallization by dissolving a fluorine-containing cyclic sulfonylimide salt in a solvent such as dimethyl carbonate, acetonitrile, tetrahydrofuran, or acetone, distilling off the solvent, and concentrating the solution, but have confirmed that problems arise in that the entire mixture becomes gel-like during concentration and does not crystallize, and does not dry up even when concentration is continued, and that cooling the concentrated solution does not produce crystals, making it impossible to achieve high purification. Thus, the high affinity of the fluorine-containing cyclic sulfonylimide salt with the solvent that dissolves it has been an obstacle to the crystallization of the fluorine-containing cyclic sulfonylimide salt.

[0081] As a result of intensive investigations, the present inventors unexpectedly found that a fluorinated cyclic sulfonylimide salt of extremely high purity and with a small amount of residual solvent can be easily obtained by using a monodentate chain ether solvent in crystallization, and thus completed the present invention.

[0082] The crystallization step may be carried out by cooling crystallization. In consideration of the high hygroscopicity of the fluorine-containing cyclic sulfonylimide salt, it is desirable to carry out the crystallization step under a dry atmosphere in order to facilitate the handling of the crystals obtained. The dry atmosphere is not particularly limited, and the crystallization step may be carried out under an atmosphere or air flow of a gas such as dry air, dry nitrogen, or dry argon, or may be carried out under vacuum reduced pressure.

[0083] In the following, the term "poor solvent" refers to a solvent that is suitable for producing crystals when a solution of a fluorinated cyclic sulfonylimide salt is cooled, and does not necessarily mean that the solubility of the fluorinated cyclic sulfonylimide salt is extremely low.

[0084] The solvent used for crystallization in the production method of this embodiment is a monodentate chain ether solvent, from the viewpoint of satisfying both the relatively high solubility of the fluorine-containing cyclic sulfonylimide salt and low coordination to metal. When a monodentate chain ether solvent is used for crystallization, the reason why a fluorine-containing cyclic sulfonylimide salt with reduced fluorine-based impurities and residual solvent amount can be produced with high purity and easily is not clear, but the present inventor presumes that the monodentate chain ether solvent has low coordination to metal, dielectric constant, dipole moment, all of which tend to be lower than other polar solvents, cyclic ethers, etc., and this works advantageously for removing the solvent from the crystals. In the production method of this embodiment, by using a monodentate chain ether solvent for crystallization of the fluorine-containing cyclic sulfonylimide salt, it is possible to easily obtain a fluorine-containing cyclic sulfonylimide salt with reduced fluorine-based impurities and residual solvent amount with high purity.

[0085] A "monodentate" solvent refers to a solvent that has one site that can coordinate to a metal, such as an ether bond.

[0086] In the crystallization step, it is desirable to use a single solvent from the viewpoint of production costs, and in this embodiment, since the monodentate chain ether solvent itself functions effectively as a poor solvent in crystallization, it is possible to obtain a high-purity imide salt even if only a single solvent is used. However, in this embodiment, multiple solvents can be mixed, and crystallization can be promoted by adding a polar solvent as a good solvent or by further adding a poor solvent. However, when multiple solvents are mixed, the amount of solvent remaining after drying tends to increase, which may be disadvantageous in terms of heat history and production costs. In addition, when a polar solvent, which is a good solvent, is added, the generated crystals may stick to the inside of the crystallizer, which may cause concerns such as a decrease in recovery rate and an increase in costs due to the introduction of special crushing equipment.

[0087] As the monodentate chain ether solvent, from the viewpoint of reducing the amount of remaining solvent after drying, those having a low boiling point, i.e., a carbon number of 6 or less are preferred, and examples thereof include ethyl ether, propyl methyl ether, propyl ethyl ether, propyl ether, isopropyl methyl ether, isopropyl ethyl ether, isopropyl ether, butyl methyl ether, butyl ethyl ether, isobutyl methyl ether, isobutyl ethyl ether, sec-butyl methyl ether, sec-butyl ethyl ether, tert-butyl methyl ether, tert-butyl ethyl ether, pentyl methyl ether, isopentyl methyl ether, sec-pentyl methyl ether, tert-pentyl methyl ether, neopentyl methyl ether, cyclopentyl methyl ether, etc., and from the viewpoint of solubility, More preferred are propyl methyl ether, propyl ethyl ether, isopropyl methyl ether, isopropyl ethyl ether, butyl methyl ether, butyl ethyl ether, isobutyl methyl ether, isobutyl ethyl ether, sec-butyl methyl ether, sec-butyl ethyl ether, tert-butyl methyl ether, tert-butyl ethyl ether, pentyl methyl ether, isopentyl methyl ether, sec-pentyl methyl ether, tert-pentyl methyl ether, neopentyl methyl ether and cyclopentyl methyl ether, and even more preferred are butyl methyl ether, butyl ethyl ether, tert-butyl methyl ether, tert-butyl ethyl ether, tert-pentyl methyl ether and cyclopentyl methyl ether.

[0088] When a polar solvent is added as the good solvent, the good solvent to be used is not particularly limited, but examples of the good solvent that dissolves the fluorinated cyclic sulfonylimide salt particularly favorably and has a relatively low boiling point include acetone, tetrahydrofuran, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, acetonitrile, methyl acetate, ethyl acetate, and butyl acetate. When a poor solvent is added specifically to promote crystallization, the poor solvent to be used is not particularly limited, but it is desirable that the poor solvent does not dissolve the fluorine-containing cyclic sulfonylimide salt, is miscible with the monodentate chain ether solvent, and has a low boiling point, and examples of such poor solvent include pentane, hexane, cyclohexane, heptane, chloroform, dichloromethane, and 1,2-dichloroethane.

[0089] The crystallization step is mainly composed of a step of dissolving the crude fluorine-containing cyclic sulfonylimide salt in a monodentate chain ether solvent and a crystallization step, but a step of removing insoluble matter from the mixture may be performed immediately before the crystallization step. This removal step can be performed by any of the known methods, such as centrifugation, natural filtration, reduced pressure filtration, and pressure filtration. When performing filtration, any known filter material may be used as long as it can withstand the use of an organic solvent, and a filter aid may also be added. The pore size of the filter material is preferably 10 μm or less, more preferably 1 μm or less.

[0090] In the process of dissolving the crude fluorine-containing cyclic sulfonylimide salt, 100 to 1000% by mass, more preferably 100 to 500% by mass, and even more preferably 100 to 300% by mass of a monodentate chain ether solvent is added to the solid containing the imide salt before crystallization. In this process, dissolution may be promoted by stirring with a magnetic stirrer or a stirring blade, shaking, ultrasonic vibration, or the like. The temperature during dissolution is not particularly limited, but can be from 0°C to the boiling point of the solvent + 50°C. When heating is performed above the boiling point of the solvent, a known reflux device can be used.

[0091] The crystallization step can be carried out, for example, by cooling the solution of the crude fluorine-containing cyclic sulfonylimide salt obtained by the dissolving step at a desired temperature. When cooling, it is preferable to cool gently to a desired temperature from the viewpoint of high purity of the resulting crystals. The cooling temperature is preferably -100°C to 30°C, more preferably -80°C to 20°C, and further preferably -50°C to 20°C. During crystallization, as is widely performed as a known method, seed crystals may be added, and before the start of cooling and during cooling, concentration may be performed by distilling off the solvent, and crystallization can also be promoted by adding the poor solvent while cooling.

[0092] The collection of the purified fluorine-containing cyclic sulfonylimide salt can be carried out by known methods such as centrifugation, natural filtration, reduced pressure filtration, and pressure filtration. Any known filter material may be used for filtration as long as it can withstand the use of an organic solvent. The pore size of the filter material is preferably 10 μm or less, more preferably 1 μm or less. In order to achieve high purity, it is preferable to wash the crystals when collecting them with a monodentate chain ether solvent, an added poor solvent, or a separately prepared solution of the fluorine-containing cyclic sulfonylimide salt in the solvent. The liquid used for washing may be heated or cooled to a desired temperature before use.

[0093] Although it is disadvantageous in terms of production costs, in order to obtain crystals of higher purity, the above crystallization step can be repeated multiple times as necessary.

[0094] From the viewpoint of increasing the efficiency of the production process, it is desirable to recover all of the liquid portion removed during collection of the crystals and the washing liquid, etc., and reuse them in the dissolving step or the crystallization step.

[0095] The purified fluorine-containing cyclic sulfonylimide salt obtained in the crystallization step is a high-purity imide salt in which impurities, particularly impurities having fluorine atoms mixed in during production, have been reduced. The purity of the purified fluorine-containing cyclic sulfonylimide salt is preferably 98% by mass or more, more preferably 99% by mass or more.

[0096] Also, 19 The ratio T1 / T2 of the sum of integrals of the peaks of the fluorine-containing cyclic sulfonylimide (1A) in F-NMR (T1) to the sum of integrals of the peaks of impurities that are characterized by appearing as a single or multiple doublet peaks in the region of -115 ppm to -125 ppm (T2) can be used as an index of the purity of the compound (1A). According to the investigations of the inventors, when the compound (1A) is produced by the above-mentioned process, unless special purification is performed, 19 The ratio T1 / T2 of the sum of integral values ​​of peaks of the fluorine-containing cyclic sulfonylimide (1A) in F-NMR (T1) to the sum of integral values ​​of peaks of an impurity that is characterized by appearing as a single or multiple doublet peaks in the region of -115 ppm to -125 ppm) is less than 500, and compound (1A) tends to be colored brown.

[0097] In this specification, the term "impurity characterized by a single or multiple doublet peaks in the region of -115 ppm to -125 ppm" is not particularly limited, but may be, for example, a compound having a difluoromethyl group such as H-CF2-XY (X is a linking group having no hydrogen or fluorine, and Y is a functional group not particularly limited).

[0098] The purified fluorine-containing cyclic sulfonylimide salt is 19The ratio T1 / T2 of the sum of integrals of peaks of fluorine-containing cyclic sulfonylimide (1A) in F-NMR (T1) to the sum of integrals of peaks of impurities that are characterized by appearing as a single or multiple doublet peaks in the region of -115 ppm to -125 ppm (T2) is preferably 500 or more, more preferably 800 or more, more preferably 1000 or more, and even more preferably 2000 or more. Most preferably, no impurity peaks are observed, but such a case is inefficient from the viewpoint of production costs. If T1 / T2 is the above value or more, the obtained fluorine-containing cyclic sulfonylimide salt tends to be highly purified and completely colored. This makes it possible to suppress, for example, poor appearance when mixed with a resin as an antistatic agent and quality deterioration during long-term storage, and to use it in a wider variety of applications.

[0099] <Drying step of fluorine-containing cyclic sulfonylimide salt (compound (1A))> Next, a drying step is preferably carried out to remove excess solvent in the fluorine-containing cyclic sulfonylimide salt after collection. In the drying step, heating and drying under reduced pressure can be carried out as is generally done. The heating temperature is preferably 40°C, more preferably 60°C, but may be carried out at a temperature of 100°C or higher as long as the decomposition of the fluorine-containing cyclic sulfonylimide salt does not proceed, and the upper limit is preferably 200°C in consideration of the thermal stability of the fluorine-containing cyclic sulfonylimide salt. The pressure during decompression is preferably 100hPa or less, more preferably 50hPa or less, even more preferably 10hPa or less, and most preferably 1hPa or less. When drying, the remaining solvent can be sufficiently removed by drying the crystals in the form collected in the above process, but in order to proceed with drying more quickly, the crystals may be crushed and stirred, in which case further reduction in heat history, time, and cost can be expected. According to the manufacturing method of this embodiment, the amount of remaining solvent in the obtained crystals is small, and adhesion between the crystals and to the container can be suppressed, so that no special manufacturing equipment is required for the crystal crushing and grinding process, and a stirring blade or mill that is generally widely used can be used.

[0100] When drying is performed, the remaining solvent can be sufficiently removed even if the crystals collected in the above step are dried in the form as they are, but a washing operation with a fluorine-containing solvent may be added in order to reduce the amount of remaining solvent and obtain a fluorine-containing cyclic sulfonylimide salt of higher purity. The washing operation with a fluorine-containing solvent is presumed to weaken the affinity between the remaining solvent and the lithium in the fluorine-containing cyclic sulfonylimide salt, and the amount of remaining solvent in the fluorine-containing cyclic sulfonylimide salt can be reduced. As a specific washing operation, a sufficient amount of fluorine-containing solvent is added to the fluorine-containing cyclic sulfonylimide salt after collection, and the mixture is stirred or left to stand for a certain period of time under non-stirring conditions, and then the solvent is removed by filtration or reduced pressure operation, and the above drying step is performed. The above washing operation may be repeated multiple times. Examples of the fluorine-containing solvent include HCFC (hydrochlorofluorocarbon), HFC (hydrofluorocarbon), CFC (chlorofluorocarbon), PFC (perfluorocarbon), PFPE (perfluoropolyether), HFE (hydrofluoroether), and HFO (hydrofluoroolefin). Among these, HFCs (hydrofluorocarbons) represented by 1,1,1,2,2,3,4,5,5,5-decafluoropentane, 1,1,1,2,2,3,4,4,5,5,5-undecafluoropentane, 1,1,1,2,2,3,3,4,5,5,5-undecafluoropentane, and perfluoropentane are preferred, and the HFC (hydrofluorocarbon) represented by 1,1,1,2,2,3,4,5,5,5-decafluoropentane is most preferred.

[0101] The amount of remaining solvent in the fluorine-containing cyclic sulfonylimide salt was determined by adding an internal standard such as benzotrifluoride. 1From the results of H-NMR measurement, it is preferably 5.0 mass% or less, more preferably 100 mass ppm or more, more preferably 100 mass ppm or more to 2.0 mass% or less, even more preferably 100 mass ppm or more to 1.0 mass% or less, and even more preferably 100 mass ppm or more to 0.1 mass% or less. When the residual solvent amount is 5.0 mass% or less, the handling property of the fluorine-containing cyclic sulfonylimide salt as a powder tends not to be deteriorated, which is desirable. In addition, when the residual solvent amount is 100 mass ppm or more, it tends to shorten the time of the drying process and to eliminate the need for further heating, which is desirable from the viewpoint of production cost.

[0102] <1.Non-aqueous electrolyte>

[0103] In the non-aqueous electrolyte, the following general formula (1): [ka] {where, R f may be the same or different and each represents a fluorine atom or a perfluoro group having 4 or less carbon atoms. By using the fluorine-containing cyclic sulfonylimide salt represented by the formula, the initial charge / discharge efficiency and cycle performance are improved. Although the detailed mechanism is unknown, it is speculated that this is because the cyclic anion generated by the dissociation of the fluorine-containing cyclic sulfonylimide salt is reduced and decomposed at the negative electrode, and accumulates on the negative electrode to act as SEI. It is also speculated that this is because the fluorine-containing cyclic sulfonylimide salt has low metal corrosivity, suppressing the dissolution of Al ions from the positive electrode current collector.

[0104] In a non-aqueous electrolyte solution in which the non-aqueous solvent contains acetonitrile, the use of a fluorine-containing cyclic sulfonylimide salt represented by formula (1) reduces metal corrosivity and improves the initial charge-discharge efficiency and cycle performance. The mechanism is presumed to be as follows.

[0105] The fluorine-containing cyclic sulfonylimide salt represented by formula (1) dissociates into a cation and a cyclic anion in a non-aqueous electrolyte solution containing acetonitrile. The cyclic anion electrically interacts with acetonitrile, weakening the metal coordination ability of the nitrile group of acetonitrile. This suppresses metal elution caused by acetonitrile forming a complex with a transition metal in the positive electrode active material at high temperatures, and suppresses the migration of the metal complex to the negative electrode. Therefore, deterioration of the negative electrode SEI due to reductive precipitation of the metal complex at the negative electrode is suppressed, improving the initial charge / discharge efficiency and cycle performance.

[0106] In addition, the decomposition products produced by the reductive decomposition of cyclic anions at the negative electrode accumulate on the negative electrode and act as SEI, improving the durability of the negative electrode SEI against reductive precipitation of metal complexes at the negative electrode and suppressing the reductive decomposition of the solvent at the negative electrode.

[0107] In formula (1), n ​​is an integer of 1 to 4. Specific examples of the fluorinated cyclic sulfonylimide salt in which n is 1 to 4 include lithium salts represented by the following compounds (1-1) to (1-5). Of these, compound (1-2) in which n is 2 is preferred from the viewpoint of facilitating the production of an electrolyte solution with high ionic conductivity. [ka]

[0108] The content of the fluorine-containing cyclic sulfonylimide salt represented by formula (1) is preferably 0.1 mol or more, more preferably 0.5 mol or more, and even more preferably 0.8 mol or more, per 1 L of non-aqueous solvent. When it is within the above range, the ionic conductivity increases, and there is a tendency for high output characteristics to be exhibited. In addition, the content of the fluorine-containing cyclic sulfonylimide salt represented by formula (1) is preferably less than 3 mol, more preferably 2.5 mol or less, more preferably 1.8 mol or less, more preferably 1.5 mol or less, and even more preferably 1.3 mol or less, per 1 L of non-aqueous solvent. When the content of the fluorine-containing cyclic sulfonylimide salt represented by formula (1) is within the above range, there is a tendency for the ionic conductivity of the non-aqueous electrolyte to increase, and the high output characteristics of the battery to be exhibited, and the decrease in ionic conductivity associated with the increase in viscosity of the non-aqueous electrolyte at low temperatures to be suppressed, and there is a tendency for the high-temperature cycle characteristics and other characteristics of the battery to be further improved while maintaining the excellent performance of the non-aqueous electrolyte.

[0109] In order to improve the volumetric energy density of the non-aqueous secondary battery, the weight of the positive electrode active material layer contained in the positive electrode is set to 24 to 200 mg / cm 2 When the content of the fluorine-containing cyclic sulfonylimide salt represented by formula (1) is adjusted to within the above range, the content of the fluorine-containing cyclic sulfonylimide salt represented by formula (1) is preferably 1 mol or more, more preferably 1.2 mol or more, even more preferably 1.5 mol or more, and particularly preferably 2 mol or more. When the content of the fluorine-containing cyclic sulfonylimide salt represented by formula (1) is within the above range, rapid ion conduction is possible even in the deep part of the positive electrode away from the positive electrode-electrolyte interface, and there is a tendency that the volumetric energy density can be improved while maintaining a balance with the output performance in the nonaqueous secondary battery.

[0110] The content of the fluorine-containing cyclic sulfonylimide salt in the electrolyte can be measured using, for example, perfluorobenzene as an internal standard. 19One example is a method that combines the measurement of the cyclic anion content by F-NMR and the measurement of the lithium ion content by ion chromatography.

[0111] In addition, in a non-aqueous electrolyte, while excess LiPF6 causes a decrease in battery performance at high temperatures, the fluorine-containing cyclic sulfonylimide salt suppresses the decrease in battery performance at high temperatures by a mechanism that is presumed to contribute to the negative electrode SEI, etc., so the molar ratio of the content of the fluorine-containing cyclic sulfonylimide salt represented by formula (1) to the content of LiPF6 is preferably 2.5 or more, more preferably greater than 10, more preferably 15 or more, even more preferably 20 or more, and particularly preferably 25 or more. When the molar ratio of the content of the fluorine-containing cyclic sulfonylimide salt to the content of LiPF6 is within the above-mentioned range, the decrease in battery performance at high temperatures, such as 50 ° C. or more, can be effectively suppressed, and excellent high-temperature durability can be obtained.

[0112] The non-aqueous electrolyte according to one embodiment of the present invention contains a non-aqueous solvent and a lithium salt, The non-aqueous solvent comprises a carbonate solvent; The lithium salt is represented by the above general formula (1) The compound contains a fluorine-containing cyclic sulfonylimide salt represented by the formula: The following general formula (2): H(CR2)m-SO2NHM 2 (2) In the formula, R may be the same or different and each represents a fluorine atom or a trifluoromethyl group; M 2 is Li, Na, K, H or NH4, and m is 1 or 2. The nonaqueous electrolyte solution contains 1000 mass ppm or less of a fluorine-containing sulfonamide compound represented by the following formula (1) relative to the total amount of the nonaqueous electrolyte solution.

[0113] The non-aqueous electrolyte refers to an electrolyte containing 1% by mass or less of water relative to the total amount of the non-aqueous electrolyte. The non-aqueous electrolyte according to the present embodiment is preferably free of water as much as possible, but may contain a very small amount of water as long as it does not impede the solution of the problem of the present invention. The content of such water is 300 ppm by mass or less, preferably 200 ppm by mass or less, based on the total amount of the non-aqueous electrolyte. As long as the non-aqueous electrolyte has a configuration for achieving the solution of the problem of the present invention, the other components can be appropriately selected and applied from the constituent materials in the known non-aqueous electrolyte used in lithium ion batteries.

[0114] The nonaqueous electrolyte of the present embodiment contains a nonaqueous solvent, a lithium salt, and compound (2), and can be produced by further mixing, if desired, various additives shown below (sometimes simply referred to as "additives" in this specification) by any means. Note that the various additives are a general term for additives for protecting electrodes and other optional additives, and the contents thereof are as shown below.

[0115] Unless otherwise specified, the content of each compound in the non-aqueous solvent is specified in terms of volume % relative to the total amount of each component constituting the non-aqueous solvent for each component described in <2-1. Non-aqueous solvent> and the electrode protection additive described in <2-3. Additive for electrode protection>, the mixing ratio is specified in terms of the number of moles per 1 L of non-aqueous solvent for the lithium salt described in <2-2. Lithium salt>, and the mixing ratio is specified in terms of parts by mass when the lithium salt and the entire non-aqueous solvent are taken as 100 parts by mass for <2-4. Other optional additives>.

[0116] In the present embodiment, when the electrolyte solution contains a compound other than the compounds specifically shown in each of the items <2-1> to <2-4> below, if the compound is liquid at room temperature (25°C), it is treated as a non-aqueous solvent and the mixing ratio is expressed in volume % relative to the total amount of each component (including the compound) constituting the non-aqueous solvent. On the other hand, if the compound is solid at room temperature (25°C), the mixing ratio is expressed in parts by mass when the total amount of the lithium salt and the non-aqueous solvent is 100 parts by mass.

[0117] <2-1.Non-aqueous solvents> The non-aqueous solvent of the present embodiment includes a carbonate solvent, such as a cyclic carbonate, a fluoroethylene carbonate, a chain carbonate, or a compound in which some or all of the H atoms of the carbonate solvent are substituted with halogen atoms.

[0118] Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, trans-2,3-butylene carbonate, cis-2,3-butylene carbonate, 1,2-pentylene carbonate, trans-2,3-pentylene carbonate, cis-2,3-pentylene carbonate, vinylene carbonate, 4,5-dimethylvinylene carbonate, and vinylethylene carbonate;

[0119] Fluoroethylene carbonates include, for example, 4-fluoro-1,3-dioxolane-2-one, 4,4-difluoro-1,3-dioxolane-2-one, cis-4,5-difluoro-1,3-dioxolane-2-one, trans-4,5-difluoro-1,3-dioxolane-2-one, 4,4,5-trifluoro-1,3-dioxolane-2-one, 4,4,5,5-tetrafluoro-1,3-dioxolane-2-one, and 4,4,5-trifluoro-5-methyl-1,3-dioxolane-2-one;

[0120] Examples of chain carbonates include ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, methyl butyl carbonate, dibutyl carbonate, and ethyl propyl carbonate; The following can be mentioned.

[0121] Here, examples of the fluorinated chain carbonate include methyl trifluoroethyl carbonate, trifluorodimethyl carbonate, trifluorodiethyl carbonate, trifluoroethyl methyl carbonate, methyl 2,2-difluoroethyl carbonate, methyl 2,2,2-trifluoroethyl carbonate, methyl 2,2,3,3-tetrafluoropropyl carbonate, etc. The above-mentioned fluorinated chain carbonate is represented by the following general formula: R cc -OC(O)OR dd {where, R cc and R dd are CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and CH2R f ee and R f ee is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is substituted with at least one fluorine atom, and R cc and / or R dd contains at least one fluorine atom} It can be expressed as: In the present embodiment, the carbonate solvent other than acetonitrile may be used alone or in combination of two or more kinds.

[0122] In the present embodiment, the non-aqueous solvent is preferably used in combination with acetonitrile together with one or more of cyclic carbonate and chain carbonate from the viewpoint of improving the stability of the non-aqueous electrolyte. From this viewpoint, the non-aqueous solvent in the present embodiment is more preferably used in combination with cyclic carbonate together with acetonitrile, and further preferably used with both cyclic carbonate and chain carbonate together with acetonitrile.

[0123] When a cyclic carbonate is used with acetonitrile, it is particularly preferred that such cyclic carbonate comprises ethylene carbonate, vinylene carbonate, and / or fluoroethylene carbonate.

[0124] In the present embodiment, the term "non-aqueous solvent" refers to elements in the non-aqueous electrolyte excluding lithium salt and various additives. When the non-aqueous electrolyte contains an additive for protecting an electrode, the term "non-aqueous solvent" refers to elements in the non-aqueous electrolyte excluding lithium salt and additives other than the additive for protecting an electrode. Examples of non-aqueous solvents include alcohols such as methanol and ethanol; aprotic solvents, etc. Among them, aprotic solvents are preferred as non-aqueous solvents. The non-aqueous solvent may contain a solvent other than the aprotic solvent as long as it does not hinder the problem solving of the present invention.

[0125] The non-aqueous solvent related to the non-aqueous electrolyte of this embodiment may contain acetonitrile as an aprotic solvent. The non-aqueous solvent contains acetonitrile, which improves the ionic conductivity of the non-aqueous electrolyte, thereby increasing the diffusibility of lithium ions in the battery. Therefore, even in a positive electrode in which the positive electrode active material layer is thickened to increase the amount of positive electrode active material filled, lithium ions can be well diffused to the area near the current collector where lithium ions are difficult to reach during high-load discharge. Therefore, it is possible to extract sufficient capacity even during high-load discharge, and a non-aqueous secondary battery with excellent load characteristics can be obtained.

[0126] Furthermore, the non-aqueous solvent contains acetonitrile, which can improve the rapid charging characteristics of the non-aqueous secondary battery. In constant current (CC)-constant voltage (CV) charging of a non-aqueous secondary battery, the capacity per unit time during the CC charging period is greater than the charge capacity per unit time during the CV charging period. When acetonitrile is used as the non-aqueous solvent of the non-aqueous electrolyte, the range in which CC charging is possible can be expanded (CC charging time can be extended) and the charging current can also be increased, so that the time from the start of charging to fully charging the non-aqueous secondary battery can be significantly shortened.

[0127] In addition, acetonitrile is easily electrochemically reduced and decomposed, so when acetonitrile is used, it is preferable to use another solvent (e.g., an aprotic solvent other than acetonitrile) together with acetonitrile as a non-aqueous solvent and / or to add an additive for protecting an electrode for forming a protective film on the electrode.

[0128] The content of acetonitrile is preferably 3% by volume or more and 97% by volume or less, based on the total amount of the non-aqueous solvent. The content of acetonitrile is more preferably 5% by volume or more, 10% by volume or more, 20% by volume or more, 30% by volume or more, 40% by volume or more, or 50% by volume or more, and more preferably 60% by volume or more, based on the total amount of the non-aqueous solvent. This value is more preferably 97% by volume or less, and even more preferably 95% by volume or less. When the content of acetonitrile is 3% by volume or more, based on the total amount of the non-aqueous solvent, the ion conductivity tends to increase and high output characteristics can be expressed, and furthermore, the dissolution of the lithium salt can be promoted. Since the additive described later suppresses the increase in the internal resistance of the battery, when the content of acetonitrile in the non-aqueous solvent is within the above range, the high temperature cycle characteristics and other battery characteristics tend to be further improved while maintaining the excellent performance of acetonitrile.

[0129] Examples of aprotic solvents other than acetonitrile include lactones, organic compounds having sulfur atoms, cyclic ethers, mononitriles other than acetonitrile, alkoxy group-substituted nitriles, dinitriles, cyclic nitriles, short-chain fatty acid esters, linear ethers, fluorinated ethers, ketones, and compounds in which some or all of the H atoms of the aprotic solvents have been substituted with halogen atoms.

[0130] Lactones include γ-butyrolactone, α-methyl-γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, δ-caprolactone, and ε-caprolactone;

[0131] Examples of organic compounds having sulfur atoms include ethylene sulfite, propylene sulfite, butylene sulfite, pentene sulfite, sulfolane, 3-sulfolene, 3-methyl sulfolane, 1,3-propane sultone, 1,4-butane sultone, 1-propene 1,3-sultone, dimethyl sulfoxide, tetramethylene sulfoxide, and ethylene glycol sulfite;

[0132] Cyclic ethers include, for example, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, and 1,3-dioxane;

[0133] Examples of mononitriles other than acetonitrile include propionitrile, butyronitrile, valeronitrile, benzonitrile, and acrylonitrile;

[0134] Alkoxy group-substituted nitriles include, for example, methoxyacetonitrile and 3-methoxypropionitrile;

[0135] Dinitriles include, for example, malononitrile, succinonitrile, glutaronitrile, adiponitrile, 1,4-dicyanoheptane, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 2,6-dicyanoheptane, 1,8-dicyanooctane, 2,7-dicyanooctane, 1,9-dicyanononane, 2,8-dicyanononane, 1,10-dicyanodecane, 1,6-dicyanodecane, and 2,4-dimethylglutaronitrile;

[0136] Cyclic nitriles include, for example, benzonitrile;

[0137] Examples of short-chain fatty acid esters include methyl acetate, methyl propionate, methyl isobutyrate, methyl butyrate, methyl isovalerate, methyl valerate, methyl pivalate, methyl hydroangelate, methyl caproate, ethyl acetate, ethyl propionate, ethyl isobutyrate, ethyl butyrate, ethyl isovalerate, ethyl valerate, ethyl pivalate, ethyl hydroangelate, ethyl caproate, propyl acetate, propyl propionate, propyl isobutyrate, propyl butyrate, propyl isovalerate, propyl valerate, propyl pivalate, propyl hydroangelate, propyl caproate, isopropyl acetate, isopropyl propionate, isopropyl isobutyrate, isopropyl butyrate, isopropyl isovalerate, isopropyl valerate, and isopropyl pivalate. propyl, isopropyl hydroangelate, isopropyl caproate, butyl acetate, butyl propionate, butyl isobutyrate, butyl butyrate, butyl isovalerate, butyl valerate, butyl pivalate, butyl hydroangelate, butyl caproate, isobutyl acetate, isobutyl propionate, isobutyl isobutyrate, isobutyl butyrate, isobutyl isovalerate, isobutyl valerate, isobutyl pivalate, isobutyl hydroangelate, isobutyl caproate, tert-butyl acetate, tert-butyl propionate, tert-butyl isobutyrate, tert-butyl butyrate, tert-butyl isovalerate, tert-butyl valerate, tert-butyl pivalate, tert-butyl hydroangelate, and tert-butyl caproate;

[0138] Chain ethers include, for example, dimethoxyethane, diethyl ether, 1,3-dioxolane, diglyme, triglyme, and tetraglyme;

[0139] Examples of fluorinated ethers include R f aa -OR bb {where, R f aa is an alkyl group containing a fluorine atom, R bb is an organic group which may contain a fluorine atom};

[0140] Ketones, for example, acetone, methyl ethyl ketone, and methyl isobutyl ketone;

[0141] Examples of the aprotic solvent compound in which some or all of the H atoms have been replaced with halogen atoms include compounds in which the halogen atoms are fluorine; The following can be mentioned.

[0142] Examples of fluorinated short-chain fatty acid esters include fluorinated short-chain fatty acid esters such as 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, and 2,2,3,3-tetrafluoropropyl acetate. Fluorinated short-chain fatty acid esters are represented by the following general formula: R ff -C(O)OR gg {where, R ff is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, CF3CF2H, CFH2, CF2R f hh , CFHR f hh , and CH2R f ii and R gg are CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and CH2R f ii and R f hh is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom may be substituted with at least one fluorine atom, and R f ii is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is substituted with at least one fluorine atom, and R ff and / or R gg contains at least one fluorine atom, and R ff If is CF2H, R gg is not CH3} It can be expressed as:

[0143] In the present embodiment, the aprotic solvent other than acetonitrile may be used alone or in combination of two or more kinds.

[0144] <2-2. Lithium salts> (Fluorine-containing cyclic sulfonylimide salt (1)) The lithium salt is a fluorine-containing cyclic sulfonylimide salt represented by the above general formula (1).

[0145] The content of the fluorine-containing cyclic sulfonylimide salt represented by the formula (1) is preferably 0.8 mol or more and 1.5 mol or less per 1 L of the non-aqueous solvent. The fluorine-containing cyclic sulfonylimide salt represented by the formula (1) may be the same as that described in the above section <Composition containing fluorine-containing cyclic sulfonylimide salt (compound (1A))>.

[0146] The fluorine-containing cyclic sulfonylimide salt represented by the formula (1) has a five-membered ring structure. [ka] In the six-membered fluorine-containing cyclic sulfonylimide salt represented by the formula {wherein R may be the same or different and represent a fluorine atom or a perfluoro group having 4 or less carbon atoms}, the bond between the carbon atom in the CR2 group that is not adjacent to the sulfonyl group and the R group is weak, so that the high-temperature durability of the battery is reduced at the negative electrode during charging. In addition, the molecular weight of the lithium salt in the six-membered or more fluorine-containing cyclic sulfonylimide salt is larger than that of the five-membered fluorine-containing cyclic sulfonylimide salt. Therefore, the weight of the lithium salt required to prepare a nonaqueous electrolyte containing a certain molar concentration of lithium ions increases, and the viscosity of the nonaqueous electrolyte tends to increase and the output characteristics tend to decrease.

[0147] (Production method of fluorine-containing cyclic sulfonylimide salt (compound (1))) The method for producing the fluorine-containing cyclic sulfonylimide salt (compound (1)) represented by the above formula (1) may be the same as that described in the above section <Production method of fluorine-containing cyclic sulfonylimide salt (compound (1A))>.

[0148] The lithium salt in the present embodiment may further contain, in addition to the fluorine-containing cyclic sulfonylimide salt, one or more selected from a lithium-containing imide salt, a fluorine-containing inorganic lithium salt, an organic lithium salt, and other lithium salts.

[0149] The method for measuring the content of the lithium salt in this embodiment is the same as the method for measuring the content of the fluorinated cyclic sulfonylimide salt described above.

[0150] (LiPF6) The non-aqueous electrolyte of this embodiment may further contain LiPF6 as a lithium salt. The content of LiPF6 in the non-aqueous electrolyte of this embodiment is preferably less than 0.5 mol, more preferably less than 0.1 mol, and even more preferably less than 0.01 mol per 1 L of non-aqueous solvent. When the content of LiPF6 is within the above range, the generation of acid components due to the thermal decomposition reaction of LiPF6 can be suppressed, and the increase in resistance of the negative electrode due to excessive deposition of inorganic components in the negative electrode SEI can be minimized.

[0151] The content of LiPF6 is 4 or less, preferably 1 or less, and more preferably 0.2 or less, in terms of molar ratio to the content of vinylene carbonate and fluoroethylene carbonate. The content of LiPF6 is 0.01 or more, preferably 0.05 or more, and more preferably 0.1 or more, in terms of molar ratio to the content of vinylene carbonate and fluoroethylene carbonate. By adjusting the content of LiPF6 within the above range, a negative electrode SEI having an excellent balance between the organic components derived from vinylene carbonate and fluoroethylene carbonate and the inorganic components derived from LiPF6 is formed, and the increase in the resistance of the negative electrode in a high-temperature test, for example, at 50°C or higher, can be suppressed.

[0152] When the ratio of organic components derived from vinylene carbonate and fluoroethylene carbonate in the negative electrode SEI is extremely high compared to the ratio of inorganic components derived from LiPF6, the internal resistance of non-aqueous secondary batteries tends to increase in high-temperature durability tests. Although the details are unclear, it is speculated that the strength of the negative electrode SEI composed mainly of organic components derived from vinylene carbonate and fluoroethylene carbonate is low, and the reductive decomposition of the solvent in the negative electrode cannot be sufficiently suppressed, and the decomposition products accumulate on the negative electrode, increasing the internal resistance. In this case, the reversible capacity of the battery is maintained high because the reductive decomposition of the solvent occurs without consuming lithium ions, but the output performance tends to decrease significantly due to the high internal resistance of the battery.

[0153] In addition, when the ratio of organic components derived from vinylene carbonate and fluoroethylene carbonate in the negative electrode SEI is extremely low compared to the ratio of inorganic components derived from LiPF6, the internal resistance of the non-aqueous secondary battery tends to increase in high-temperature durability tests. Although the details are unclear, it is speculated that the high insulating properties of the negative electrode SEI, which is mainly composed of inorganic components derived from LiPF6, inhibit the lithium ion conduction at the negative electrode-electrolyte interface.

[0154] (Lithium-containing imide salt) Specifically, the imide salt preferably contains at least one of LiN(SO2F)2 and LiN(SO2CF3)2.

[0155] When the non-aqueous solvent contains acetonitrile, the saturation concentration of the lithium-containing imide salt in acetonitrile is higher than that of LiPF6, so that the imide salt is preferably contained at a molar concentration of LiPF6≦lithium-containing imide salt, since this can suppress the association and precipitation of the lithium salt and acetonitrile at low temperatures. In addition, the content of the lithium-containing imide salt is preferably 0.5 mol or more and 3.0 mol or less per 1 L of the non-aqueous solvent, from the viewpoint of ensuring the amount of ions supplied to the non-aqueous electrolyte according to this embodiment.

[0156] According to the acetonitrile-containing nonaqueous electrolyte solution containing at least one of LiN(SO2F)2 and LiN(SO2CF3)2, the decrease in ion conductivity at a low temperature range such as −10° C. or −30° C. can be effectively suppressed, and excellent low-temperature characteristics can be obtained. In this embodiment, by limiting the content of the lithium-containing imide salt in this way, it is also possible to more effectively suppress the increase in resistance during high-temperature heating.

[0157] (Fluorine-containing inorganic lithium salt) The lithium salt used in the nonaqueous electrolyte of the present embodiment may include a fluorine-containing inorganic lithium salt other than LiPF, for example, LiBF, LiAsF, LiSiF, LiSbF, LiB 12 F b H 12-b [wherein b is an integer of 0 to 3]. Here, "inorganic lithium salt" refers to a lithium salt that does not contain a carbon atom in the anion and is soluble in acetonitrile. Also, "fluorine-containing inorganic lithium salt" refers to a lithium salt that does not contain a carbon atom in the anion and contains a fluorine atom in the anion and is soluble in acetonitrile. Fluorine-containing inorganic lithium salts are excellent in that they form a passive film on the surface of the aluminum foil that is the positive electrode current collector, and suppress corrosion of the positive electrode current collector. These fluorine-containing inorganic lithium salts are used alone or in combination of two or more. As the fluorine-containing inorganic lithium salt, a compound that is a double salt of LiF and a Lewis acid is preferred, and among them, when a fluorine-containing inorganic lithium salt having a phosphorus atom is used, it is more preferred because it is easy to release free fluorine atoms. When a fluorine-containing inorganic lithium salt having a boron atom is used as the fluorine-containing inorganic lithium salt, it is preferred because it is easy to capture excess free acid components that may cause battery deterioration, and from this viewpoint, LiBF4 is particularly preferred.

[0158] The content of the fluorine-containing inorganic lithium salt in the lithium salt used in the non-aqueous electrolyte of this embodiment is preferably 0.01 mol or more, more preferably 0.1 mol or more, and even more preferably 0.25 mol or more, relative to 1 L of the non-aqueous solvent. When the content of the fluorine-containing inorganic lithium salt is within the above-mentioned range, the ion conductivity increases, and there is a tendency for high-output characteristics to be exhibited. In addition, this content is preferably less than 2.8 mol, more preferably less than 1.5 mol, and even more preferably less than 1 mol, relative to 1 L of the non-aqueous solvent. When the content of the fluorine-containing inorganic lithium salt is within the above-mentioned range, there is a tendency for the ion conductivity to increase, high-output characteristics to be exhibited, and the decrease in ion conductivity associated with an increase in viscosity at low temperatures to be suppressed, and there is a tendency for the high-temperature cycle characteristics and other battery characteristics to be further improved while maintaining the excellent performance of the non-aqueous electrolyte.

[0159] (Organic Lithium Salts) The lithium salt in this embodiment may include an organic lithium salt. The term "organic lithium salt" refers to a lithium salt other than an imide salt that contains a carbon atom in the anion and is soluble in acetonitrile.

[0160] The organic lithium salt may be an organic lithium salt having an oxalic acid group. Specific examples of the organic lithium salt having an oxalic acid group include organic lithium salts represented by LiB(C2O4)2, LiBF2(C2O4), LiPF4(C2O4), and LiPF2(C2O4)2, and among them, at least one lithium salt selected from the lithium salts represented by LiB(C2O4)2 and LiBF2(C2O4) is preferred. It is more preferred to use one or more of these together with a fluorine-containing inorganic lithium salt. The organic lithium salt having an oxalic acid group may be added to a non-aqueous electrolyte solution or may be contained in the negative electrode (negative electrode active material layer).

[0161] In the present embodiment, the amount of the organic lithium salt added to the non-aqueous electrolyte is preferably 0.005 mol or more, more preferably 0.01 mol or more, even more preferably 0.02 mol or more, and particularly preferably 0.05 mol or more, per 1 L of non-aqueous solvent, in order to better ensure the effect of its use. However, if the amount of the organic lithium salt having an oxalic acid group in the non-aqueous electrolyte is too large, it may precipitate. Therefore, the amount of the organic lithium salt having an oxalic acid group added to the non-aqueous electrolyte is preferably less than 1.0 mol, more preferably less than 0.5 mol, and even more preferably less than 0.2 mol, per 1 L of non-aqueous solvent.

[0162] It is known that the organic lithium salt having an oxalic acid group is poorly soluble in organic solvents with low polarity, particularly in chain carbonates. The content of the organic lithium salt in the non-aqueous electrolyte according to this embodiment may be, for example, 0.01 mol or more and 0.5 mol or less per 1 L of non-aqueous solvent.

[0163] In addition, the organic lithium salt having an oxalic acid group may contain a small amount of lithium oxalate, and when mixed as a non-aqueous electrolyte solution, it may react with a small amount of water contained in other raw materials to generate new white precipitation of lithium oxalate. Therefore, it is preferable to suppress the content of lithium oxalate in the non-aqueous electrolyte solution according to this embodiment to a range of 500 ppm or less.

[0164] (Other lithium salts) The lithium salt in the present embodiment may contain other lithium salts in addition to those mentioned above.

[0165] Other specific examples of lithium salts include, for example, LiClO4, LiAlO4, LiAlCl4, LiB 10 Cl 10 , chloroborane Li, and other inorganic lithium salts that do not contain a fluorine atom in the anion; LiCF3SO3, LiCF3CO2, Li2C2F4(SO3)2, LiC(CF3SO2)3, LiCnF (2n+1) SO3 {wherein n≧2}, organic lithium salts such as lower aliphatic carboxylic acids Li, tetraphenylborate LiB(C3O4H2)2, etc.; LiPF such as LiPF5(CF3) n (C p F 2p+1 ) 6-n

[0033] (wherein n is an integer of 1 to 5, and p is an integer of 1 to 8); LiBF such as LiBF3(CF3) q (C s F 2s+1 ) 4-q (wherein q is an integer of 1 to 3, and s is an integer of 1 to 8); Lithium salts combined with multivalent anions; The following formula (XXa): LiC(SO2R jj )(SO2R kk )(SO2R ll ) (XXa) {where, R jj , R kk , and R ll may be the same or different and represent a perfluoroalkyl group having 1 to 8 carbon atoms. The following formula (XXb): LiN(SO2OR mm )(SO2OR nn ) (XXb) {where, R mm , and R nn may be the same or different and represent a perfluoroalkyl group having 1 to 8 carbon atoms.}, and The following formula (XXc): LiN(SO2R oo )(SO2OR pp ) (XXc) {where, R oo , and R pp may be the same or different and represent a perfluoroalkyl group having 1 to 8 carbon atoms.} One or more of these can be used together with the fluorine-containing inorganic lithium salt.

[0166] The amount of the other lithium salt added to the non-aqueous electrolyte solution may be appropriately set within the range of, for example, 0.01 mol or more and 0.5 mol or less per 1 L of the non-aqueous solvent.

[0167] <2-3. Additives for electrode protection> The non-aqueous electrolyte according to the present embodiment may contain an additive for protecting the electrodes (electrode protection additive). The electrode protection additive may substantially overlap with a substance that serves as a solvent for dissolving the lithium salt (i.e., the above-mentioned non-aqueous solvent). The electrode protection additive is preferably a substance that contributes to improving the performance of the non-aqueous electrolyte and the non-aqueous secondary battery, but also includes a substance that is not directly involved in the electrochemical reaction.

[0168] Specific examples of the electrode protection additive include, for example, Fluoroethylene carbonates represented by 4-fluoro-1,3-dioxolan-2-one, 4,4-difluoro-1,3-dioxolan-2-one, cis-4,5-difluoro-1,3-dioxolan-2-one, trans-4,5-difluoro-1,3-dioxolan-2-one, 4,4,5-trifluoro-1,3-dioxolan-2-one, 4,4,5,5-tetrafluoro-1,3-dioxolan-2-one, and 4,4,5-trifluoro-5-methyl-1,3-dioxolan-2-one; unsaturated bond-containing cyclic carbonates, such as vinylene carbonate, 4,5-dimethylvinylene carbonate, and vinylethylene carbonate; Lactones represented by γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, δ-caprolactone, and ε-caprolactone; Cyclic ethers, such as 1,4-dioxane; Cyclic sulfur compounds represented by ethylene sulfite, propylene sulfite, butylene sulfite, pentene sulfite, sulfolane, 3-sulfolene, 3-methylsulfolane, 1,3-propane sultone, 1,4-butane sultone, 1-propene 1,3-sultone, and tetramethylene sulfoxide; These may be used alone or in combination of two or more.

[0169] The content of the electrode protection additive in the nonaqueous electrolyte solution is preferably 0.1 to 30 volume %, more preferably 0.3 to 15 volume %, even more preferably 0.4 to 8 volume %, and particularly preferably 0.5 to 4 volume %, relative to the total amount of the nonaqueous solvent.

[0170] In this embodiment, the greater the content of the electrode protection additive, the more the deterioration of the non-aqueous electrolyte solution is suppressed. However, the smaller the content of the electrode protection additive, the more the high-output characteristics of the non-aqueous secondary battery in a low-temperature environment are improved. Therefore, by adjusting the content of the electrode protection additive within the above range, it is possible to exhibit excellent performance based on the high ionic conductivity of the electrolyte solution without impairing the basic function of the non-aqueous secondary battery, and by preparing the non-aqueous electrolyte solution with such a composition, it is possible to further improve the cycle performance of the non-aqueous secondary battery, the high-output performance in a low-temperature environment, and other battery characteristics.

[0171] Acetonitrile is easily electrochemically decomposed by reduction. Therefore, the non-aqueous solvent containing acetonitrile preferably contains one or more cyclic aprotic polar solvents, more preferably one or more unsaturated bond-containing cyclic carbonates, as an electrode protection additive for forming a protective film on the negative electrode.

[0172] As the unsaturated bond-containing cyclic carbonate, vinylene carbonate is preferred, and the content of vinylene carbonate in the non-aqueous electrolyte is preferably 0.1% by volume or more and 4% by volume or less, more preferably 0.2% by volume or more and less than 3% by volume, and even more preferably 0.5% by volume or more and less than 2.5% by volume. This makes it possible to more effectively improve low-temperature durability and provide a secondary battery with excellent low-temperature performance.

[0173] Vinylene carbonate as an additive for electrode protection suppresses the reductive decomposition reaction of acetonitrile on the surface of the negative electrode, while excessive film formation leads to a decrease in low-temperature performance. Therefore, by adjusting the amount of vinylene carbonate added within the above range, the interface (film) resistance can be kept low, and cycle deterioration at low temperatures can be suppressed.

[0174] (acid anhydride) The non-aqueous secondary battery according to this embodiment is stabilized by forming an SEI on the negative electrode surface as a result of a part of the non-aqueous electrolyte being decomposed during the initial charge. In order to more effectively strengthen this SEI, an acid anhydride can be added to the non-aqueous electrolyte, the battery material, or the non-aqueous secondary battery. When acetonitrile is included as the non-aqueous solvent, the strength of the SEI tends to decrease with increasing temperature, but the addition of an acid anhydride promotes the strengthening of the SEI. Therefore, by using such an acid anhydride, it is possible to effectively suppress the increase in internal resistance over time due to thermal history.

[0175] Specific examples of acid anhydrides include chain acid anhydrides such as acetic anhydride, propionic anhydride, and benzoic anhydride; cyclic acid anhydrides such as malonic anhydride, succinic anhydride, glutaric anhydride, maleic anhydride, phthalic anhydride, 1,2-cyclohexanedicarboxylic anhydride, 2,3-naphthalene dicarboxylic anhydride, and naphthalene-1,4,5,8-tetracarboxylic dianhydride; and mixed acid anhydrides having a structure in which different types of acids, such as two different types of carboxylic acids or a carboxylic acid and a sulfonic acid, are dehydrated and condensed. These may be used alone or in combination of two or more types.

[0176] Since it is preferable that the non-aqueous secondary battery according to this embodiment strengthens the SEI before the reductive decomposition of the non-aqueous solvent, it is preferable that the acid anhydride contains at least one cyclic acid anhydride that acts early during the first charge. These cyclic acid anhydrides may contain only one type or multiple types. Or, it may contain a cyclic acid anhydride other than these cyclic acid anhydrides. In addition, it is preferable that the cyclic acid anhydride contains at least one type of succinic anhydride, maleic anhydride, and phthalic anhydride.

[0177] A non-aqueous electrolyte solution containing at least one of succinic anhydride, maleic anhydride, and phthalic anhydride can form a strong SEI on the negative electrode and more effectively suppress the increase in resistance during high-temperature heating. In particular, it is preferable to contain succinic anhydride. This makes it possible to more effectively form a strong SEI on the negative electrode while suppressing side reactions.

[0178] When the nonaqueous electrolyte solution according to the present embodiment contains an acid anhydride, the content thereof is preferably in the range of 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.05 parts by mass or more and 1 part by mass or less, and even more preferably 0.1 parts by mass or more and 0.5 parts by mass or less, per 100 parts by mass of the nonaqueous electrolyte solution.

[0179] The acid anhydride is preferably contained in the non-aqueous electrolyte. On the other hand, since it is sufficient that the acid anhydride can act in the non-aqueous secondary battery, at least one battery member selected from the group consisting of the positive electrode, the negative electrode, and the separator may contain the acid anhydride. As a method for containing the acid anhydride in the battery member, for example, the acid anhydride may be contained in the battery member during the preparation of the battery member, or the acid anhydride may be impregnated into the battery member by a post-treatment represented by coating, immersion, or spray drying of the battery member.

[0180] <2-4. Other optional additives> In this embodiment, for the purpose of improving the charge / discharge cycle characteristics, high-temperature storage property, and safety (e.g., prevention of overcharging) of the nonaqueous secondary battery, optional additives (additives other than the acid anhydride and the additive for protecting the electrodes) may be appropriately contained in the nonaqueous electrolyte solution.

[0181] Examples of optional additives include sulfonic acid esters, diphenyl disulfide, cyclohexylbenzene, biphenyl, fluorobenzene, tert-butylbenzene, phosphate esters (ethyl diethylphosphonoacetate (EDPA); (C2H5O)2(P=O)-CH2(C=O)OC2H5, tris(trifluoroethyl) phosphate (TFEP); (CF3CHO)3P=O, triphenyl phosphate (TPP); (C6H5O)3P=O, triallyl phosphate; (CH2=CHCHO)3P=O, triamyl phosphate, trioctyl phosphate, tris(2-butoxyethyl) phosphate, tris(2-ethylhexyl) phosphate, etc.), and nitrogen-containing cyclic compounds with no steric hindrance around the unshared electron pair (pyridine, 1-methyl-1H-benzotriazole, 1-methylpyrazole, etc.). In particular, phosphoric acid esters have the effect of suppressing side reactions during storage and improving the impregnation of the separator with a non-aqueous electrolyte, and are therefore effective as optional additives.

[0182] When the non-aqueous electrolyte according to the present embodiment contains other optional additives, the content of the additives is preferably in the range of 0.01% by mass to 10% by mass, more preferably 0.02% by mass to 5% by mass, and even more preferably 0.05 to 3% by mass, based on the total amount of the non-aqueous electrolyte. By adjusting the content of the other optional additives within the above range, there is a tendency that it is possible to add even better battery characteristics without impairing the basic functions of the non-aqueous secondary battery.

[0183] <2-5. Compound (2)> The compound (2) is a fluorine-containing sulfonamide compound represented by the above general formula (2).

[0184] Compound (2) is corrosive to metals, and when a non-aqueous electrolyte containing a large amount of a fluorine-containing sulfonamide compound is used, the metal foil used in the positive electrode current collector corrodes, leading to an increase in irreversible capacity during charging and discharging and a decrease in cycle performance. In particular, when an Al foil or a stainless steel foil is used as the metal foil, the corrosion is remarkable.

[0185] In detail, for example, when an Al current collector is used for the positive electrode, the Al corrosion reaction (reaction formula a) at the positive electrode and the reduction and precipitation reaction of Al (reaction formula b) at the negative electrode are promoted during charging, which promotes the irreversible reaction in which Al moves from the positive electrode to the negative electrode during charging, and it is presumed that this increases the irreversible capacity of the battery. Even in the long term, it is believed that the large amount of Al precipitation at the negative electrode promotes the formation of a non-uniform SEI or non-uniform precipitation of metallic lithium at the negative electrode, leading to a decrease in the battery capacity or a micro-short circuit or short circuit of the battery. Reaction formula a: Al+3(H(CR2) m -SO2NHM) → [Al(H(CR2) m -SO2NHM)3] 3+ +3e - Reaction formula b: [Al(H(CR2) m -SO2NHM)3] 3+ +3e - →Al+3(H(CR2) m -SO2NHM) By reducing the content of compound (2), the Al corrosion reaction (reaction formula a) at the positive electrode and the reduction and precipitation reaction (reaction formula b) of Al at the negative electrode during charging can be suppressed, the irreversible capacity during charging and discharging can be reduced, and the cycle performance can be improved. These phenomena were newly discovered by the present inventors through their studies and are not described at all in Patent Documents 1 to 4.

[0186] The content of the fluorine-containing sulfonamide compound (2) contained in the non-aqueous electrolyte is 1000 mass ppm or less, preferably 500 mass ppm or less, more preferably 300 mass ppm or less, more preferably 200 mass ppm or less, more preferably 150 mass ppm or less, and even more preferably 120 mass ppm or less, based on the total amount of the non-aqueous electrolyte. By adjusting the content of the fluorine-containing sulfonamide compound within the above range, it is possible to suppress an increase in irreversible capacity during charging and discharging and a decrease in cycle performance due to corrosion of the positive electrode Al current collector.

[0187] The content of the fluorine-containing sulfonamide compound contained in the non-aqueous electrolyte is preferably 0.001 mass ppm or more, more preferably 0.01 mass ppm or more, more preferably 0.1 mass ppm or more, more preferably 1 mass ppm or more, and even more preferably 80 mass ppm or more, based on the total amount of the non-aqueous electrolyte. By adjusting the content of the fluorine-containing sulfonamide compound within the above-mentioned range, the decomposition product of the fluorine-containing sulfonamide compound reduced at the negative electrode acts as the negative electrode SEI, and the long-term durability of the battery can be improved.

[0188] <3.Non-aqueous secondary battery> The nonaqueous electrolyte solution of the present embodiment can be used in a nonaqueous secondary battery. The nonaqueous secondary battery according to this embodiment is not particularly limited, but is configured by housing a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte solution in a suitable battery exterior.

[0189] Specifically, the nonaqueous secondary battery according to this embodiment may be a nonaqueous secondary battery 100 shown in Figures 1 and 2. Here, Figure 1 is a plan view that shows a schematic diagram of the nonaqueous secondary battery, and Figure 2 is a cross-sectional view taken along line AA in Figure 1.

[0190] The nonaqueous secondary battery 100 shown in FIG. 1 and FIG. 2 is composed of a pouch-type cell. The nonaqueous secondary battery 100 accommodates a laminated electrode body formed by laminating a positive electrode 150 and a negative electrode 160 with a separator 170 interposed therebetween, and a nonaqueous electrolyte (not shown) in a space 120 of a battery exterior 110. The battery exterior 110 is composed of, for example, an aluminum laminate film, and is sealed by heat-sealing the upper and lower films at the outer periphery of the space formed by the two aluminum laminate films. The laminate formed by laminating the positive electrode 150, the separator 170, and the negative electrode 160 in this order is impregnated with a nonaqueous electrolyte. However, in FIG. 2, in order to avoid the drawing becoming complicated, the layers constituting the battery exterior 110 and the layers of the positive electrode 150 and the negative electrode 160 are not shown separately.

[0191] The aluminum laminate film constituting the battery exterior 110 is preferably made of aluminum foil coated on both sides with a polyolefin resin.

[0192] The positive electrode 150 is connected to the positive electrode lead body 130 within the nonaqueous secondary battery 100. Although not shown, the negative electrode 160 is also connected to the negative electrode lead body 140 within the nonaqueous secondary battery 100. One end of each of the positive electrode lead body 130 and the negative electrode lead body 140 is drawn out to the outside of the battery exterior 110 so that they can be connected to an external device, and the ionomer portions of these are heat-fused to one side of the battery exterior 110.

[0193] 1 and 2, the positive electrode 150 and the negative electrode 160 each have one laminated electrode body, but the number of laminated positive electrodes 150 and negative electrodes 160 can be appropriately increased depending on the capacity design. In the case of a laminated electrode body having a plurality of positive electrodes 150 and negative electrodes 160, the tabs of the same electrode may be joined by welding or the like and then joined to a single lead body by welding or the like and taken out of the battery. The tabs of the same electrode may be formed from an exposed portion of a current collector, or may be formed by welding a metal piece to the exposed portion of a current collector, or the like.

[0194] The positive electrode 150 is composed of a positive electrode current collector and a positive electrode active material layer. The negative electrode 160 is composed of a negative electrode current collector and a negative electrode active material layer.

[0195] The positive electrode active material layer contains a positive electrode active material, and the negative electrode active material layer contains a negative electrode active material.

[0196] The positive electrode 150 and the negative electrode 160 are arranged such that the positive electrode active material layer and the negative electrode active material layer face each other with the separator 170 interposed therebetween. Hereinafter, each element constituting the non-aqueous secondary battery according to the present embodiment will be described in order.

[0197] <4. Positive Electrode> The positive electrode 150 is composed of a positive electrode active material layer made from a positive electrode mixture and a positive electrode current collector. The positive electrode mixture contains a positive electrode active material and, if necessary, a conductive assistant and a binder.

[0198] The positive electrode active material layer contains, as a positive electrode active material, a material capable of occluding and releasing lithium ions. Such a material can obtain a high voltage and a high energy density.

[0199] Examples of the positive electrode active material include a positive electrode active material containing at least one transition metal element selected from the group consisting of Ni, Mn, and Co, and having the following general formula (a t ): Li p Ni q Co r Mn s M t O u ·····(a t ) {In the formula, M is at least one metal selected from the group consisting of Al, Sn, In, Fe, V, Cu, Mg, Ti, Zn, Mo, Zr, Sr, and Ba, and 0 < p < 1.3, 0 < q < 1.2, 0 < r < 1.2, 0 ≦ s < 0.5, 0 ≦ t < 0.3, 0.7 ≦ q + r + s + t ≦ 1.2, 1.8 < u < 2.2, and p is a value determined by the charge and discharge state of the battery.} At least one Li-containing metal oxide selected from the lithium (Li)-containing metal oxides represented by

[0200] Specific examples of the positive electrode active material include, for example, lithium cobalt oxides typified by LiCoO2; lithium manganese oxides typified by LiMnO2, LiMn2O4, and Li2Mn2O4; lithium nickel oxides typified by LiNiO2; LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.2 O2, Li z MO2 (wherein M represents two or more metal elements selected from the group consisting of Ni, Mn, Al, and Mg, and z represents a number greater than 0.9 and less than 1.2), and lithium-containing composite metal oxides represented thereby, etc. can be mentioned.

[0201] In particular, when the Ni content ratio q of the Li-containing metal oxide represented by the general formula (a t ) is 0.5 < q < 1.2, it is preferable because both reduction of the usage amount of Co, which is a rare metal, and increase in the energy density are achieved. Examples of such positive electrode active materials include, for example, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.75 Co 0.15 Mn 0.15 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.85 Co 0.075 Mn 0.075 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.81 Co 0.1 Al 0.09 O2, LiNi 0.85 Co 0.1 Al 0.05 O2, etc., and lithium-containing composite metal oxides represented thereby can be mentioned.

[0202] On the other hand, the higher the Ni content of the Li-containing metal oxide, the more degradation tends to occur at low voltages. t ) essentially have active sites that cause the electrolyte to oxidize and deteriorate. These active sites can unintentionally consume the electrode protection additive.

[0203] In addition, the decomposition products of these additives that are taken in and deposited on the positive electrode side not only increase the internal resistance of non-aqueous secondary batteries, but also accelerate the deterioration of the lithium salt. In particular, when LiPF6 is included as a lithium salt, HF is generated due to the deterioration, which is thought to promote the elution of transition metals. In non-aqueous electrolytes that contain acetonitrile as a non-aqueous solvent, complexes between metal cations and acetonitrile are formed, accelerating the deterioration of the battery.

[0204] Furthermore, the deterioration of the electrode protection additive or lithium salt makes the protection of the negative electrode surface, which was the original purpose, insufficient. In particular, in a non-aqueous electrolyte solution containing acetonitrile as a non-aqueous solvent, if the protection of the negative electrode surface is insufficient, the reductive decomposition of acetonitrile proceeds, and the battery performance rapidly deteriorates, which is a fatal problem.

[0205] In order to deactivate the active sites that essentially cause the oxidation deterioration of the non-aqueous electrolyte, it is important to control the Jahn-Teller distortion or to have a component that acts as a neutralizer. Therefore, it is preferable that the positive electrode active material contains at least one metal selected from the group consisting of Al, Sn, In, Fe, V, Cu, Mg, Ti, Zn, Mo, Zr, Sr, and Ba.

[0206] For the same reason, it is preferable that the surface of the positive electrode active material is coated with a compound containing at least one metal element selected from the group consisting of Zr, Ti, Al, and Nb. It is more preferable that the surface of the positive electrode active material is coated with an oxide containing at least one metal element selected from the group consisting of Zr, Ti, Al, and Nb. Furthermore, it is particularly preferable that the surface of the positive electrode active material is coated with at least one oxide selected from the group consisting of ZrO2, TiO2, Al2O3, NbO3, and LiNbO2, since this does not inhibit the permeation of lithium ions.

[0207] In the nonaqueous secondary battery according to this embodiment, it is preferable to use a lithium phosphorus metal oxide having an olivine crystal structure containing iron (Fe) atoms, and the lithium phosphorus metal oxide is represented by the following formula (Xba): Li w M II PO4(Xba) {In formula, M II represents one or more transition metal elements including at least one transition metal element including Fe, and the value of w is determined depending on the charge / discharge state of the battery and represents a number from 0.05 to 1.10. It is more preferable to use a lithium phosphorus metal oxide having an olivine structure represented by the formula: In order to stabilize the structure, these lithium-containing metal oxides may be those in which a part of the transition metal element is replaced with Al, Mg, or other transition metal element, those in which these metal elements are contained in the crystal grain boundaries, those in which a part of the oxygen atoms is replaced with fluorine atoms, or those in which at least a part of the surface of the positive electrode active material is coated with another positive electrode active material, or the like.

[0208] Examples of the positive electrode active material include metal phosphate oxides containing lithium and a transition metal element, and metal silicate oxides containing lithium and a transition metal element. From the viewpoint of obtaining a higher voltage, the lithium-containing metal oxide is preferably a metal phosphate oxide containing lithium and at least one transition metal element selected from the group consisting of Co, Ni, Mn, Fe, Cu, Zn, Cr, V, and Ti, and from the viewpoint of the lithium phosphorus metal oxide represented by the above formula (Xba), a metal phosphate oxide containing Li and Fe is more preferable.

[0209] As a lithium phosphorus metal oxide different from the lithium phosphorus metal oxide represented by the above formula (Xba), Li v M I D2(Xa) In the formula, D represents a chalcogen element, and M I represents one or more transition metal elements including at least one transition metal element, and the value of v is determined depending on the charge / discharge state of the battery and represents a number from 0.05 to 1.10. A compound represented by the following formula may also be used.

[0210] In the present embodiment, the positive electrode active material may be the lithium-containing metal oxide alone, or may be used in combination with other positive electrode active materials. Examples of other positive electrode active materials include metal oxides or metal chalcogenides having a tunnel structure and a layer structure; sulfur; and conductive polymers. Examples of metal oxides or metal chalcogenides having a tunnel structure and a layer structure include MnO2, FeO2, FeS2, V2O5, and V6O 13 Examples of the conductive polymer include oxides, sulfides, and selenides of metals other than lithium, such as TiO2, TiS2, MoS2, and NbSe2. Examples of the conductive polymer include conductive polymers such as polyaniline, polythiophene, polyacetylene, and polypyrrole.

[0211] The above-mentioned other positive electrode active materials may be used alone or in combination of two or more. The positive electrode active material layer preferably contains at least one transition metal element selected from Ni, Mn, and Co, because it is capable of reversibly and stably absorbing and releasing lithium ions and achieving a high energy density.

[0212] When a lithium-containing metal oxide and another positive electrode active material are used in combination as a positive electrode active material, the ratio of the two materials is preferably 80 mass% or more, and more preferably 85 mass% or more, of the lithium-containing metal oxide relative to the total positive electrode active material.

[0213] The positive electrode active material layer is formed by dispersing a positive electrode mixture, which is a mixture of a positive electrode active material and, if necessary, a conductive assistant and a binder, in a solvent to form a positive electrode mixture-containing slurry, which is applied to a positive electrode current collector, drying (solvent removal), and pressing if necessary. As such a solvent, a known one can be used. For example, N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, water, etc. can be used.

[0214] Examples of the conductive assistant include graphite, carbon black such as acetylene black and ketjen black, and carbon fiber. The content of the conductive assistant is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, per 100 parts by mass of the positive electrode active material.

[0215] If the content of the conductive assistant is too high, the volume energy density decreases, but if the content is too low, the formation of the electron conduction path becomes insufficient. In particular, since the electron conductivity of the positive electrode active material layer is lower than that of the negative electrode active material layer, if the amount of the conductive assistant is insufficient, it becomes impossible to obtain a predetermined battery capacity when the nonaqueous secondary battery is discharged or charged at a high current value. Therefore, in applications requiring high output and / or rapid charging, it is preferable to increase the content of the conductive assistant to a range in which the reaction based on the transfer of electrons is not rate-determining.

[0216] Examples of the binder include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid, carboxymethyl cellulose, styrene butadiene rubber, and fluororubber. The content of the binder is preferably 6 parts by mass or less, and more preferably 0.5 to 4 parts by mass, relative to 100 parts by mass of the positive electrode active material.

[0217] The positive electrode current collector is made of a metal foil such as aluminum foil, nickel foil, stainless steel foil, etc. The positive electrode current collector may have a carbon coating on the surface, or may be processed into a mesh shape. The thickness of the positive electrode current collector is preferably 5 to 40 μm, more preferably 7 to 35 μm, and further preferably 9 to 30 μm.

[0218] The weight per surface of the positive electrode, excluding the positive electrode current collector, is set to 15 mg / cm from the viewpoint of improving the volumetric energy density of the non-aqueous secondary battery. 2 It is preferable that the concentration is 17.5 mg / cm or more. 2 More preferably, it is 24 mg / cm or more. 2 The weight per surface of the positive electrode excluding the positive electrode current collector is more preferably 200 mg / cm2 or more. 2 It is preferable that the concentration is less than 100 mg / cm 2 More preferably, it is 60 mg / cm or less. 2 By limiting the basis weight per one side of the positive electrode excluding the positive electrode current collector to the above range, it is possible to provide a nonaqueous secondary battery that achieves high output performance even in the case where an electrode active material layer with a high volumetric energy density is designed.

[0219] Here, the basis weight is the weight per unit area of ​​the electrode when forming an electrode active material layer on one side of the current collector. 2 When electrode active material layers are formed on both sides of a current collector, the mass of the electrode active material is calculated based on the electrode area of ​​each side (1 cm2). 2If a large amount of electrode active material is applied to the electrode current collector, the amount of electrode active material per unit volume of the battery will be relatively greater than other battery materials that are not related to battery capacity, such as the current collector foil and separator, resulting in a high capacity battery. When an electrode active material layer is formed on one surface of a current collector, the coating weight can be calculated by the following formula (12). Weight [mg / cm 2 ] = (electrode mass [mg] - electrode current collector mass [mg]) ÷ electrode area [cm 2 ] ·····(12)

[0220] <5. Negative electrode> The negative electrode 160 is composed of a negative electrode active material layer made of a negative electrode mixture and a negative electrode current collector. The negative electrode 160 can function as a negative electrode of a non-aqueous secondary battery.

[0221] The negative electrode mixture contains a negative electrode active material, and optionally contains a conductive assistant and a binder.

[0222] Examples of the negative electrode active material include amorphous carbon (hard carbon, soft carbon), graphite (artificial graphite, natural graphite), pyrolytic carbon, coke, glassy carbon, a fired body of an organic polymer compound, mesocarbon microbeads, carbon fiber, activated carbon, carbon colloid, and carbon materials such as carbon black, metallic lithium, metal oxides, metal nitrides, lithium alloys, tin alloys, silicon alloys, intermetallic compounds, organic compounds, inorganic compounds, metal complexes, organic polymer compounds, etc. The negative electrode active material can be used alone or in combination of two or more.

[0223] As the negative electrode active material of this embodiment, it is preferable to use graphite or a compound containing one or more elements selected from the group consisting of Ti, V, Sn, Cr, Mn, Fe, Co, Ni, Zn, Al, Si, and B.

[0224] The negative electrode active material layer uses lithium ions as the negative electrode active material at 0.4V vs. Li / Li in order to increase the battery voltage.+ It is preferable that the hydrogen-containing gas contains a material capable of absorbing at a potential lower than the hydrogen potential.

[0225] The negative electrode active material layer is formed by dispersing a negative electrode mixture, which is a mixture of a negative electrode active material and, if necessary, a conductive assistant and a binder, in a solvent to form a negative electrode mixture-containing slurry, which is applied to a negative electrode current collector, drying (solvent removal), and pressing if necessary. As such a solvent, a known one can be used, and examples thereof include N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, water, etc.

[0226] Examples of the conductive assistant include carbon black, such as acetylene black and ketjen black, carbon fiber, and graphite. The content of the conductive assistant is preferably 20 parts by mass or less, and more preferably 0.1 to 10 parts by mass, relative to 100 parts by mass of the negative electrode active material.

[0227] Examples of the binder include carboxymethyl cellulose, PVDF, PTFE, polyacrylic acid, and fluororubber. Also included are diene rubbers such as styrene-butadiene rubber. The content of the binder is preferably 10 parts by mass or less, more preferably 0.5 to 6 parts by mass, based on 100 parts by mass of the negative electrode active material.

[0228] The negative electrode current collector is made of a metal foil such as copper foil, nickel foil, stainless steel foil, etc. The surface of the negative electrode current collector may be carbon-coated or processed into a mesh shape. The thickness of the negative electrode current collector is preferably 5 to 40 μm, more preferably 6 to 35 μm, and further preferably 7 to 30 μm.

[0229] <6. Separator> In the present embodiment, the nonaqueous secondary battery 100 preferably includes a separator 170 between the positive electrode 150 and the negative electrode 160 from the viewpoint of preventing short circuits between the positive electrode 150 and the negative electrode 160 and providing safety such as shutdown. The separator 170 is preferably an insulating thin film having high ion permeability and excellent mechanical strength. Examples of the separator 170 include woven fabric, nonwoven fabric, and synthetic resin microporous membrane, and among these, synthetic resin microporous membrane is preferable.

[0230] As the synthetic resin microporous film, for example, a microporous film containing polyethylene or polypropylene as a main component, or a polyolefin-based microporous film such as a microporous film containing both of these polyolefins is preferably used. As the nonwoven fabric, for example, a porous film made of a heat-resistant resin such as glass, ceramic, polyolefin, polyester, polyamide, liquid crystal polyester, or aramid can be used.

[0231] Separator 170 may be configured as a single layer or multiple layers of one type of microporous film, or may be configured as a stack of two or more types of microporous films. Separator 170 may be configured as a single layer or multiple layers of a mixed resin material obtained by melting and kneading two or more types of resin materials.

[0232] For the purpose of providing functions, inorganic particles may be present on the surface or inside of the separator, or other organic layers may be further coated or laminated. The separator may also include a crosslinked structure. In order to improve the safety performance of the nonaqueous secondary battery, these techniques may be combined as necessary.

[0233] By using such a separator 170, it is possible to realize good input / output characteristics and low self-discharge characteristics required for lithium ion batteries for high power applications. The thickness of the separator is preferably 1 μm or more from the viewpoint of separator strength, and is preferably 500 μm or less from the viewpoint of permeability, more preferably 5 μm to 30 μm, and even more preferably 10 μm to 25 μm. In addition, when emphasis is placed on short circuit resistance performance, the thickness of the separator is more preferably 15 μm to 20 μm, but when emphasis is placed on high energy density, the thickness is more preferably 10 μm to less than 15 μm. The porosity of the separator is preferably 30% to 90%, more preferably 35% to 80%, and even more preferably 40% to 70% from the viewpoint of following the rapid movement of lithium ions at high power. In addition, when priority is given to improving output performance while ensuring safety, 50% or more and 70% or less is particularly preferable, and when emphasis is placed on both short circuit resistance and output performance, 40% or more and less than 50% is particularly preferable. The air permeability of the separator is set to 1 sec / 100 cm from the viewpoint of the balance between the thickness and porosity of the separator. 3 More than 400 seconds / 100cm 3 Less than 100 seconds / 100 cm is preferable. 3 More than 350 / 100cm 3 It is more preferable that the air permeability is 150 sec / 100 cm. 3 More than 350 seconds / 100cm 3 The following is particularly preferable. If you prioritize improving output performance while ensuring safety, 100 / 100cm 3 150 seconds / 100cm 3is particularly preferably less than 10 mS / cm. On the other hand, when a non-aqueous electrolyte with low ionic conductivity is combined with a separator within the above range, the lithium ion migration rate is not determined by the structure of the separator, but by the high ionic conductivity of the electrolyte, and the expected input / output characteristics tend not to be obtained. Therefore, the ionic conductivity of the non-aqueous electrolyte at 25°C is preferably 10 mS / cm or more, more preferably 15 mS / cm or more, and even more preferably 20 mS / cm or more. However, the thickness, air permeability and porosity of the separator, and the ionic conductivity of the non-aqueous electrolyte are not limited to the above examples.

[0234] <7. Battery exterior> The battery exterior 110 of the nonaqueous secondary battery 100 in this embodiment may be, for example, a battery can (not shown) or a laminate film exterior. The battery can may be, for example, a metal can made of steel, stainless steel (SUS), aluminum, clad material, or the like, and may be rectangular, rectangular tube, cylindrical, elliptical, flat, coin, or button-shaped. The laminate film exterior may be, for example, a laminate film made of a three-layer structure of heat-melting resin / metal film / resin.

[0235] The laminate film exterior body can be used as an exterior body by stacking two sheets with the heat-melting resin side facing inward, or by folding the laminate film exterior body so that the heat-melting resin side faces inward, and sealing the ends by heat sealing. When using a laminate film exterior body, the positive electrode lead body 130 (or a lead tab connected to the positive electrode terminal and the positive electrode terminal) may be connected to the positive electrode current collector, and the negative electrode lead body 140 (or a lead tab connected to the negative electrode terminal and the negative electrode terminal) may be connected to the negative electrode current collector. In this case, the laminate film exterior body may be sealed with the ends of the positive electrode lead body 130 and the negative electrode lead body 140 (or the lead tabs connected to the positive electrode terminal and the negative electrode terminal, respectively) pulled out to the outside of the exterior body.

[0236] In the present embodiment, the battery exterior of the nonaqueous secondary battery preferably contains aluminum in at least a part of the liquid-contacting layer on the positive electrode side with the nonaqueous electrolyte. By using such a battery exterior, it is possible to minimize corrosion deterioration of the battery exterior and improve the cycle characteristics of the battery. The liquid-contacting layer may be made of the same material as the main body, i.e., the liquid-contacting layer of the main body, or may be a layer formed by coating the main body with another material.

[0237] The aluminum contained in the liquid contact layer may be present in a portion of the liquid contact layer with the nonaqueous electrolyte, or may be present in the entire liquid contact layer. However, in order to minimize corrosion deterioration of the battery exterior and maximize improvement in the cycle characteristics of the battery, it is more preferable that the entire liquid contact layer is aluminum.

[0238] In addition, the battery exterior of the nonaqueous secondary battery in this embodiment may be one in which the main body is made of a metal other than aluminum, and at least a part of the liquid contact layer with the nonaqueous electrolyte contains aluminum. The liquid contact layer containing aluminum can be provided by plating, cladding, or the like. More preferably, it is made of aluminum cladding. A cladding is a material in which two or more different metals are bonded together, and is generally considered to be one in which the boundary surface between the different metals is diffusion bonded (has an alloy layer). The cladding can be produced by pressing or explosive welding.

[0239] In the case of a coin-type nonaqueous secondary battery, the battery exterior preferably contains aluminum in at least a part of the liquid contact layer on the positive electrode side, and more preferably has at least a part of the liquid contact layer on the positive electrode side clad with aluminum.

[0240] When the main metal layer of the battery exterior is made of a metal other than aluminum, the main metal is not particularly limited, but from the viewpoint of preventing corrosion of the outside of the container, it is preferable to use austenitic stainless steels such as SUS304, SUS316, and SUS316L, austenitic-ferritic stainless steels such as SUS329J1 and SUS329J3L, ferritic stainless steels such as SUS405 and SUS430, and martensitic stainless steels such as SUS403 and SUS410.

[0241] <8. How to make a battery> The nonaqueous secondary battery 100 in this embodiment is produced by a known method using the above-mentioned nonaqueous electrolyte, a positive electrode 150 having a positive electrode active material layer on one or both sides of a current collector, a negative electrode 160 having a negative electrode active material layer on one or both sides of a current collector, a battery exterior 110, and, if necessary, a separator 170.

[0242] First, a laminate is formed consisting of the positive electrode 150, the negative electrode 160, and, if necessary, the separator 170. For example, possible modes include a mode in which the long positive electrode 150 and the negative electrode 160 are wound in a stacked state with the long separator interposed between the positive electrode 150 and the negative electrode 160 to form a laminate with a wound structure; a mode in which the positive electrode sheets and the negative electrode sheets obtained by cutting the positive electrode 150 and the negative electrode 160 into a plurality of sheets having a certain area and shape are alternately stacked with a separator sheet between to form a laminate with a laminate structure; a mode in which a long separator is folded zigzag and a positive electrode body sheet and a negative electrode body sheet are alternately inserted between the zigzag folded separators to form a laminate with a laminate structure; and the like.

[0243] Next, the above-mentioned laminate is housed in a battery exterior 110 (battery case), the electrolyte solution according to this embodiment is poured into the battery case, and the laminate is immersed in the electrolyte solution and sealed, thereby producing the nonaqueous secondary battery of this embodiment. Alternatively, a gelled electrolyte membrane is produced in advance by impregnating a substrate made of a polymer material with the electrolyte solution, and a laminate having a laminated structure is formed using a sheet-like positive electrode 150, a negative electrode 160, and an electrolyte membrane, and a separator 170 as necessary, and then the laminate is housed in the battery exterior 110 to produce the nonaqueous secondary battery 100.

[0244] In addition, if the arrangement of the electrodes is designed so that there is a portion where the outer peripheral edge of the negative electrode active material layer overlaps with the outer peripheral edge of the positive electrode active material layer, or there is a portion where the width is too small in the non-facing portion of the negative electrode active material layer, the position of the electrodes may be shifted during battery assembly, which may deteriorate the charge-discharge cycle characteristics of the non-aqueous secondary battery. Therefore, it is preferable that the electrode positions of the electrode body used in the non-aqueous secondary battery are fixed in advance by tapes such as polyimide tape, polyphenylene sulfide tape, and polypropylene (PP) tape, adhesives, etc.

[0245] In a non-aqueous electrolyte solution containing acetonitrile, due to the high ionic conductivity of acetonitrile, lithium ions released from the positive electrode during the initial charge of a non-aqueous secondary battery may diffuse throughout the negative electrode. In a non-aqueous secondary battery, the area of ​​the negative electrode active material layer is generally made larger than that of the positive electrode active material layer. However, if lithium ions diffuse and are absorbed to a portion of the negative electrode active material layer that does not face the positive electrode active material layer, the lithium ions will not be released during the initial discharge and will remain in the negative electrode. Therefore, the contribution of the lithium ions that are not released becomes irreversible capacity. For these reasons, in a non-aqueous secondary battery using a non-aqueous electrolyte solution containing acetonitrile, the initial charge / discharge efficiency may be low.

[0246] On the other hand, if the area of ​​the positive electrode active material layer is larger than that of the negative electrode active material layer or they are the same, current tends to concentrate at the edge portions of the negative electrode active material layer during charging, making lithium dendrites more likely to form.

[0247] Although there is no particular restriction on the ratio of the area of ​​the entire negative electrode active material layer to the area of ​​the portion where the positive electrode active material layer and the negative electrode active material layer face each other, for the reasons described above, it is preferably greater than 1.0 and less than 1.1, more preferably greater than 1.002 and less than 1.09, even more preferably greater than 1.005 and less than 1.08, and particularly preferably greater than 1.01 and less than 1.08. In a nonaqueous secondary battery using a nonaqueous electrolyte solution containing acetonitrile, the initial charge / discharge efficiency can be improved by reducing the ratio of the area of ​​the entire negative electrode active material layer to the area of ​​the portion where the positive electrode active material layer and the negative electrode active material layer face each other.

[0248] Reducing the ratio of the area of ​​the entire negative electrode active material layer to the area of ​​the portion where the positive electrode active material layer and the negative electrode active material layer face each other means limiting the ratio of the area of ​​the portion of the negative electrode active material layer that does not face the positive electrode active material layer. This makes it possible to reduce as much as possible the amount of lithium ions absorbed in the portion of the negative electrode active material layer that does not face the positive electrode active material layer among the lithium ions released from the positive electrode during the initial charge (i.e., the amount of lithium ions that are not released from the negative electrode during the initial discharge and become irreversible capacity). Therefore, by designing the ratio of the area of ​​the entire negative electrode active material layer to the area of ​​the portion where the positive electrode active material layer and the negative electrode active material layer face each other within the above range, it is possible to improve the load characteristics of the battery by using acetonitrile, increase the initial charge / discharge efficiency of the battery, and further suppress the generation of lithium dendrites.

[0249] The non-aqueous secondary battery 100 in this embodiment can function as a battery through the first charge, but is stabilized by the decomposition of a part of the electrolytic solution during the first charge. There is no particular limitation on the method of the first charge, but the first charge is preferably performed at 0.001 to 0.3 C, more preferably at 0.002 to 0.25 C, and even more preferably at 0.003 to 0.2 C. It is also preferable to perform the first charge via constant voltage charging, which gives favorable results. By setting a long voltage range in which the lithium salt participates in the electrochemical reaction, a stable and strong negative electrode SEI is formed on the electrode surface, suppressing an increase in internal resistance, and the reaction products are not firmly fixed only to the negative electrode 160, but also have a good effect on members other than the negative electrode 160, such as the positive electrode 150 and the separator 170. Therefore, it is very effective to perform the first charge in consideration of the electrochemical reaction of the lithium salt dissolved in the non-aqueous electrolytic solution.

[0250] The non-aqueous secondary battery 100 in this embodiment can also be used as a battery pack in which a plurality of non-aqueous secondary batteries 100 are connected in series or in parallel. From the viewpoint of managing the charge and discharge state of the battery pack, when using the positive electrode active material represented by the above formula (Xba) at the positive electrode, the operating voltage range per battery is preferably 1.5 to 4.0 V, and particularly preferably 2.0 to 3.8 V.

[0251] Also, when using the positive electrode active material represented by the general formula (a t ), the operating voltage range per battery is preferably 2 to 5 V, more preferably 2.5 to 5 V, and particularly preferably 2.75 V to 5 V.

Examples

[0252] Examples specifically illustrating this embodiment are exemplified below. The present invention is not limited to the following examples as long as the gist thereof is not exceeded.

[0253] <I. Heat Resistance Test of Fluorine-Containing Cyclic Sulfonyl Imide Salt (Compound (1A)) Composition> <Analysis Method> The analytical methods, raw materials, reaction conditions, etc. used in the examples and comparative examples are as follows.

[0254] (Nuclear magnetic resonance analysis (NMR): 1 H-NMR, and 19 Molecular structure analysis by F-NMR) Regarding the products obtained in the examples and comparative examples, 1 H-NMR (400MHz), and 19 Molecular structure analysis was carried out using F-NMR (337 MHz) under the following measurement conditions. [Measurement conditions] Measurement equipment: JNM-ECZ400S nuclear magnetic resonance equipment (manufactured by JEOL Ltd.) Observation kernel: 1 H, 19 F Solvent: deuterated chloroform, deuterated dimethyl sulfoxide Reference material: Tetramethylsilane ( 1 H, 0.00 ppm), trichlorofluoromethane ( 19 F, 0.00 ppm) Reference substance concentration: 5% by mass Measurement sample concentration: 20% by mass Pulse width: 6.5μsec Wait time: 2 seconds Number of times accumulated: 8 times ( 1 H), 1024 times ( 19 F) <Content of compound (2)> 19 From the results of F-NMR measurement, the content of compound (2) was determined from the integral values ​​of typical peaks of compound (1A) and compound (2). In this example, the compound of the following structural formula: [ka] The content of the fluorinated cyclic sulfonimide lithium salt represented by the formula (compound (1-2)) was calculated from the integral value of the peak at -115.4 ppm (4F), and the content of HCF2SO2NHLi (compound (2-1)) was calculated from the integral value of the peak at -122.6 ppm (2F).

[0255] (ICP atomic emission spectrometry) The products obtained in the examples and comparative examples were subjected to molecular structure analysis under the following measurement conditions. [Measurement conditions] Measuring device: SPS3520UV-DD (manufactured by Hitachi High-Tech Science Corporation) Measuring atom: Li Sample preparation conditions: 0.1 g of the product was mixed with 9.9 g of ultrapure water to obtain a temporary dilution solution with a concentration of 1% by mass. Then, 1.5 g of the temporary dilution solution was mixed with 28.5 g of a 1% by mass aqueous nitric acid solution to obtain a measurement sample. High frequency power: 1.2kW Plasma gas (argon) flow rate: 16 L / min Auxiliary gas (argon) flow rate: 0.5 L / min Carrier gas (argon) pressure: 0.24MPa Carrier gas (argon) flow rate: 0.3 L / min Photometric height: 12mm Chamber gas (argon) flow rate: 0.6 L / min

[0256] (Temperature at which mass reduction rate becomes 1% and 2% by mass) The mass reduction rate of the products obtained in the examples and comparative examples was measured under the following measurement conditions. 5 mg of sample was weighed into an aluminum pan ("Crimp Cell (for autosampler) part number 346-66963-91", manufactured by Shimadzu Corporation; no cover was used during measurement.) and using a differential thermal thermogravimetry analyzer ("DTG-60A", manufactured by Shimadzu Corporation) the sample was heated from 25°C to 100°C at a heating rate of 10°C / min under a nitrogen stream (flow rate 50 mL / min), and then held at 100°C for 30 minutes. After that, the sample was heated at a heating rate of 10°C / min over the measurement temperature range of 100°C to 500°C, and the mass loss was observed. The mass at the start of heating from 100°C after holding at 100°C for 30 minutes as mentioned above was taken as the reference (100 mass%), and the temperatures (°C) at which a mass loss of 1 mass% and 2 mass% was confirmed were observed during heating at a heating rate of 10°C / min over a measurement temperature range of 100°C to 500°C.

[0257] <Raw materials used> The raw materials used in the examples and comparative examples are shown below. (Fluorosulfonyl group-containing carboxylic acid (compound (3))) 2,2-Difluoro-2-(fluorosulfonyl)acetic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (compound (3-1))

[0258] Ammonia (Sumitomo Seika Chemicals Co., Ltd.)

[0259] (Alkali metal salt (compound (6))) Lithium hydroxide monohydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (solvent)

[0260] Acetonitrile (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; the water content was adjusted by adding dried molecular sieve 3A 1 / 16 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), dehydrating, and removing the molecular sieve 3A 1 / 16) Tetrahydrofuran (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; the water content was adjusted by adding dried molecular sieve 3A 1 / 16 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), dehydrating, and removing the molecular sieve 3A 1 / 16)

[0261] Activated carbon (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0262] <Reaction temperature> The reaction temperature is room temperature when no external heating / cooling device is used, and is the temperature of the medium used in the external heating / cooling device when an external heating / cooling device such as a water bath or an oil bath is used.

[0263] [Example I-1] (Electrolytic coupling reaction process) A stirrer, acetonitrile (59 g), and water (75 g) were added to a 200 mL three-neck flask under a nitrogen atmosphere, and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 25.7 g, 144.3 mmol) was added. Platinum plate electrodes (25 mm x 50 mm) were placed as the anode and cathode with an interval of 6 mm and immersed in the solution. While maintaining stirring under cooling at 0°C, a current of 1.5 A was applied to the electrodes for 4 hours. When the current was applied and the stirring was stopped, the reaction solution separated into two phases. The lower layer was separated to obtain 7.9 g of liquid. The resulting liquid was sampled, 19 F-NMR measurement confirmed that the product contained 90.3 mass% FO2SCF2CF2SO2F (compound (4-1)) (yield 37.1%) and 1.2 mass% HCF2SO2F (compound (5-1)). The crude FO2SCF2CF2SO2F (compound (4-1)) obtained by the above operation was purified by simple distillation at atmospheric pressure to obtain 6.9 g of a liquid containing 95.6 mass% FO2SCF2CF2SO2F (compound (4-1)) and 0.042 mass% HCF2SO2F (compound (5-1)). FO2SCF2CF2SO2F (compound (4-1)) 19 F-NMR: δ(ppm)46.1(2F), -108.7(4F) HCF2SO2F (compound (5-1)) 1 H-NMR: δ(ppm) 7.0 ppm (1H) 19 F-NMR: 36.0 (1F), -122.0 (2F)

[0264] (Cyclization process) A 3 L autoclave was cooled to -78°C, and ammonia gas (250 g, 14680 mmol) and tetrahydrofuran (222.3 g) were added, followed by dropwise addition of a solution of FOSCFCFSOF (compound (4-1), 208 g, purity 95.6 mass%, 747.2 mmol) obtained in the electrolytic coupling reaction step in tetrahydrofuran (222.3 g) over a period of 3 hours. After completion of dropwise addition, the mixture was stirred at room temperature for 12 hours. After completion of stirring, the reaction solution was pressure filtered to remove insoluble solids, and the filtrate was concentrated under reduced pressure and dried to obtain 193.0 g of a flesh-colored solid. The obtained solid was sampled, 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the compound (1-N-2) contained 99.0% by mass (yield 98.3%) of a fluorine-containing cyclic sulfonylimide ammonium salt represented by the following formula (1-N-2) and 0.048% by mass of HCF2SO2NHNH4 (compound (2-2)). Compound (1-N-2) 19 F-NMR: δ(ppm)-115.4(4F) HF2CSO2NHNH4 (Compound (2-2)) 1 H-NMR: δ(ppm) 6.0 ppm (1H) 19 F-NMR: 36.0 (1F), -122.6 (2F)

[0265] (Cation exchange process) In a 1L three-neck flask, a stirrer, tetrahydrofuran (400 g), the fluorine-containing cyclic sulfonylimide ammonium salt obtained in Example I-1 (compound (1-N-2), 192.7 g, purity 99.0 mass%, 733.2 mmol) and lithium hydroxide monohydrate (34.2 g, 815.1 mmol) were added under a nitrogen atmosphere, and the mixture was stirred at 70°C for 4 hours. The reaction solution obtained was concentrated under reduced pressure, and then water (500 mL) and activated carbon (65.8 g) were added, and the mixture was stirred at 105°C for 3 hours. The reaction solution obtained was filtered under pressure to remove insoluble solids, and then concentrated under reduced pressure to obtain a skin-colored solid. Tetrahydrofuran (889 g) was added to the obtained skin-colored solid, and the mixture was stirred at 50°C for 30 minutes, and then filtered under pressure to remove insoluble solids, and concentrated under reduced pressure to obtain 177.9 g of a white solid. The obtained solid was sampled and analyzed by ICP atomic emission spectrometry, and it was confirmed that the ammonium cations were exchanged for lithium cations. moreover, 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the composition contained 99.9% by mass (yield 97.3%) of a fluorinated cyclic sulfonimide lithium salt represented by the following formula (compound (1-2)) and 0.046% by mass of HCF2SO2NHLi (compound (2)). Compound (1-2) 19 F-NMR: δ(ppm)-115.4(4F) HCF2SO2NHLi (compound (2-1)) 1 H-NMR: δ(ppm) 6.0 ppm (1H) 19 F-NMR: 36.0 (1F), -122.6 (2F)

[0266] [Comparative example I-1] (Electrolytic coupling reaction process) FO2SCF2CF2SO2F (compound (4-1)) was produced in the same manner as in Example I-1, except that distillation purification was not performed after the electrolytic reaction, and 7.9 g of a liquid containing 90.3 mass% FO2SCF2CF2SO2F (compound (4-1)) and 1.2 mass% HCF2SO2F (compound (5-1)) was obtained (yield 37.2%).

[0267] (Cyclization process) Using the FO2SCF2CF2SO2F (compound (4-1)) obtained in the electrolytic coupling reaction process, a fluorine-containing cyclic sulfonylimide ammonium salt (compound (1-N-2)) was produced in the same manner as in Example I-1, and 188.0 g (yield 98.3%) of a flesh-colored solid containing 96.2 mass% of the fluorine-containing cyclic sulfonylimide ammonium salt (compound (1-N-2)) and 1.43 mass% of HCF2SO2NHNH4 (compound (2-2)) was obtained.

[0268] (Cation exchange process) Using the fluorine-containing cyclic sulfonylimide ammonium salt (compound (1-N-2)) obtained in the cyclization step, a fluorine-containing cyclic sulfonimide lithium salt (compound (1-2)) was produced in the same manner as in Example I-1, and 170.3 g (yield 97.2%) of a white solid containing 98.3 mass% of the fluorine-containing cyclic sulfonimide lithium salt (compound (1-2)) and 1.22 mass% of HCF2SO2NHLi (compound (2-1)) was obtained.

[0269] The temperatures at which the mass loss rates of the fluorinated cyclic sulfonimide lithium salts (compound (1-2)) obtained in Example I-1 and Comparative Example I-1 reached 1% by mass and 2% by mass were measured according to the above-mentioned method.

[0270] [Table 1]

[0271] From Table 1, it can be seen that the fluorine-containing cyclic sulfonimide lithium salt (Compound (1-2)) of Example I-1 with a reduced content of HF2CSO2NHLi (Compound (2-1)) has an increased temperature at which the mass loss rate reaches 2% by mass compared to the fluorine-containing cyclic sulfonimide lithium salt (Compound (1-2)) of Comparative Example I-1 with a high content of HCF2SO2NHLi (Compound (2-1)), indicating improved heat resistance characteristics. This is presumably because the reduction in the content of the thermally unstable Compound (2) suppresses the decomposition of Compound (1A) caused by the decomposition reaction of Compound (2), resulting in improved heat resistance characteristics of Compound (1A).

[0272] <II. Non-aqueous electrolyte>

[0273] (1) Preparation of non-aqueous electrolyte Under an inert atmosphere, various non-aqueous solvents were mixed so that each had a predetermined concentration. Further, various lithium salts were added so that each had a predetermined concentration to prepare non-aqueous electrolytes (S01) to (S20). Also, using (S01) as the mother electrolyte, a non-aqueous electrolyte (S21) was prepared by adding a compound represented by the formula (2-1) to a predetermined mass part. The compositions of these non-aqueous electrolytes are shown in Table 2.

[0274] Compound (1-2) was synthesized by the method described below. Lot A is the compound after purification by the crystallization process, Lot B is the compound synthesized through the cyclization process and the cation exchange process after purification by distillation after the electrolytic coupling reaction process, and Lot C is the compound that underwent neither crystallization purification nor distillation purification after the electrolytic coupling reaction process.

[0275] Insoluble components different from Compound (2-1) derived from the unpurified Compound (1-2) (Lot C) were observed in electrolytes (S02) and (S15). Therefore, for electrolytes (S02) and (S15), a coin-type non-aqueous secondary battery was fabricated using an electrolyte obtained by precipitating the insoluble components at the bottom of the container and performing decantation to remove the insoluble solids.

[0276] In addition, the abbreviations for the non-aqueous solvents and lithium salts in Table 2 have the following meanings. (Non-aqueous solvent) AN: Acetonitrile PC: Propylene carbonate EMC: Ethyl methyl carbonate ES: Ethylene sulfite VC: Vinylene carbonate FEC: 4-fluoro-1,3-dioxolan-2-one (Lithium salts) (1-2): A compound represented by the above formula (1-2) (1-6): A compound represented by the following formula (1-6): [ka] LiFSI: Lithium bis(fluorosulfonyl)imide (LiN(SO2F)2) LiTFSI: Lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2) (Fluorine-containing sulfonamide compound) (2-1): A fluorine-containing sulfonamide compound represented by the above formula (2-1): HCF2SO2NHLi

[0277] Preparation of compound (1-2) <Analysis method> The analytical methods, raw materials, reaction conditions, and the like used in the preparation of compound (1-2) are as follows.

[0278] (Nuclear magnetic resonance analysis (NMR): 1 H-NMR, and 19 Molecular structure analysis by F-NMR) Regarding the product obtained in the process of producing compound (1-2), 1 H-NMR (400MHz), and 19 Molecular structure analysis was carried out using F-NMR (337 MHz) under the following measurement conditions. [Measurement conditions] Measurement equipment: JNM-ECZ400S nuclear magnetic resonance equipment (manufactured by JEOL Ltd.) Observation kernel: 1 H, 19 F Solvent: deuterated chloroform, deuterated dimethyl sulfoxide Reference material: Tetramethylsilane ( 1 H, 0.00 ppm), trichlorofluoromethane ( 19 F, 0.00 ppm) Reference substance concentration: 5% by mass Measurement sample concentration: 20% by mass Pulse width: 6.5μsec Wait time: 2 seconds Number of times accumulated: 8 times ( 1 H), 1024 times ( 19 F)

[0279] <Content of compound (2-1)> 19 From the results of F-NMR measurement, the content of compound (2-1) was determined from the integral values ​​of typical peaks of compound (1-2) and compound (2-1).

[0280] In this example, the compound of the following structural formula: [ka] The content of compound (2-1) was calculated from the integral value of the peak at −115.4 ppm (4F) for the fluorinated cyclic sulfonimide lithium salt represented by the formula (compound (1-2)) and from the integral value of the peak at −122.6 ppm (2F) for HCF2SO2NHLi (compound (2-1)).

[0281] (ICP atomic emission spectrometry) The prepared compound (1-2) was subjected to molecular structure analysis under the following measurement conditions. [Measurement conditions] Measuring device: SPS3520UV-DD (manufactured by Hitachi High-Tech Science Corporation) Measuring atom: Li Sample preparation conditions: 0.1 g of the product was mixed with 9.9 g of ultrapure water to obtain a temporary dilution solution with a concentration of 1% by mass. Then, 1.5 g of the temporary dilution solution was mixed with 28.5 g of a 1% by mass aqueous nitric acid solution to obtain a measurement sample. High frequency power: 1.2kW Plasma gas (argon) flow rate: 16 L / min Auxiliary gas (argon) flow rate: 0.5 L / min Carrier gas (argon) pressure: 0.24MPa Carrier gas (argon) flow rate: 0.3 L / min Photometric height: 12mm Chamber gas (argon) flow rate: 0.6 L / min

[0282] <Raw materials used> The raw materials used in the preparation of compound (1-2) are shown below. 2,2-Difluoro-2-(fluorosulfonyl)acetic acid (compound (3-1), manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.)

[0283] Ammonia (Sumitomo Seika Chemicals Co., Ltd.)

[0284] Lithium hydroxide monohydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0285] Acetonitrile (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; the water content was adjusted by adding dried molecular sieve 3A 1 / 16 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), dehydrating, and removing the molecular sieve 3A 1 / 16) Tetrahydrofuran (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; the water content was adjusted by adding dried molecular sieve 3A 1 / 16 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), dehydrating, and removing the molecular sieve 3A 1 / 16)

[0286] Activated carbon (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0287] <Reaction temperature> The reaction temperature is room temperature when no external heating / cooling device is used, and when an external heating / cooling device such as a water bath or an oil bath is used, the temperature of the medium used in the external heating / cooling device is the reaction temperature.

[0288] <Synthesis of compound (1-2) (Lots A and C)> (Electrolytic coupling reaction process) A 200 mL three-neck flask was charged with a stirrer, acetonitrile (59 g), and water (75 g) under a nitrogen atmosphere, then cooled to 0°C, and FOSCFCOH (compound (3-1), Fujifilm Wako Pure Chemical Industries, Ltd., 25.7 g, 144.3 mmol) was added. Platinum plate electrodes (25 mm x 50 mm) were placed at an interval of 6 mm as the anode and cathode, and immersed in the solution. A current of 1.5 A was applied to the electrodes for 4 hours while maintaining stirring under cooling at 0°C. When the current was applied, the stirring was stopped and the reaction solution separated into two phases. The lower layer was separated to obtain 7.9 g of liquid. The obtained liquid was washed with water and dried with molecular sieves to obtain 6.9 g of liquid containing FOSCFCFSOF (compound (4-1)). FO2SCF2CF2SO2F (compound (4-1)) 19 F-NMR (deuterated chloroform): δ(ppm) 46.1 (2F), -108.7 (4F)

[0289] (Cyclization process) A 3L autoclave was cooled to -78°C, and ammonia gas (250g, 14.68mol) and tetrahydrofuran (250mL) were added. Then, while maintaining the temperature inside the autoclave at -55°C or lower, a solution of FOSCFCFSOF (compound (4-1), 208g, 0.71mol) in tetrahydrofuran (250.0mL) was added dropwise. After the dropwise addition, the mixture was stirred overnight at room temperature. Then, while maintaining stirring, the internal pressure was returned to normal pressure, and argon was blown into the autoclave at a rate of 0.5L / min for 1.5 hours to discharge the ammonia. The reaction solution was filtered to remove the white solid, which was washed several times with tetrahydrofuran. The obtained filtrate was transferred to a 3L flask, concentrated under reduced pressure, and further vacuum dried at 40°C for 12 hours to obtain 188.0g of a solid. The obtained solid was sampled, 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the compound was a fluorine-containing cyclic sulfonylimide ammonium salt represented by the following formula (compound (1-N-2), 0.7 mol, yield 98%). 19 F-NMR (deuterated dimethyl sulfoxide): δ(ppm)-115.4(4F)

[0290] (Cation exchange process) In a 1L three-neck flask, a stirrer, tetrahydrofuran (450mL), fluorine-containing cyclic sulfonylimide ammonium salt (compound (1-N-2), 187.0g, 0.69mol), and lithium hydroxide monohydrate (32.2g, 0.77mol) were added under a nitrogen atmosphere, and the mixture was stirred at 70°C for 4 hours. The obtained reaction liquid was concentrated under reduced pressure, and then ion-exchanged water (500mL) and activated carbon (65.8g) were added, and the mixture was stirred at 105°C for 3 hours. The obtained reaction liquid was filtered under pressure to remove insoluble solids, and then concentrated under reduced pressure to obtain a solid (205.8g). Tetrahydrofuran (1L) was added to the obtained flesh-colored solid, and the mixture was stirred at 50°C for 30 minutes, and then filtered under pressure to remove insoluble solids, and the mixture was concentrated under reduced pressure, and then vacuum dried at 70°C for 16 hours and at 90°C for 10 hours to obtain 170.3g of a slightly brown solid. The solid obtained was sampled and analyzed by ICP atomic emission spectrometry, which confirmed that the ammonium cations had been exchanged for lithium cations. 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the resulting crystals were fluorine-containing cyclic sulfonimide lithium salt (compound (1-2), 0.68 mol, yield 98%) represented by the formula: 19 F-NMR analysis confirmed that the product contained 99.1% by mass of compound (1-2) and 6,600 ppm by mass of HCF2SO2NHLi (compound (2-1)) (Lot C). Compound (1-2) 19 F-NMR (deuterated dimethyl sulfoxide): δ(ppm)-115.4(4F) HCF2SO2NHLi (compound (2-1)) 1 H-NMR (deuterated dimethyl sulfoxide): δ(ppm) 6.0(1H) 19 F-NMR (deuterated dimethyl sulfoxide): δ(ppm)-122.6(2F)

[0291] (Crystallization process) 10 g of the synthesized compound (1-2) and 27 g of tert-butyl methyl ether were weighed into a 100 mL eggplant flask equipped with a stirrer, and the flask was sealed and stirred for 30 minutes. The resulting mixture was filtered under reduced pressure and cooled in a freezer at -20°C for 30 minutes, resulting in the formation of colorless crystals. After removing the liquid by decantation, the crystals were washed by adding tert-butyl methyl ether at -35°C and mixing with a medicine spoon, and the liquid was removed by decantation. The resulting crystals were dried under reduced pressure for 3 hours at 60°C and 40 hPa without stirring. The crystals were crushed using a mortar and pestle, 20 mL of Vertrel (Mitsui-Chemours Fluoroproducts, Inc., main component: 1,1,1,2,2,3,4,5,5,5-decafluoropentane) was added, and the mixture was dried under reduced pressure at 100°C and 15 hPa for 2 hours without stirring. This operation was repeated four times to obtain 4.9 g (yield 49.0%) of crystals. The obtained crystals were sampled, 19 F-NMR analysis confirmed that the product contained 99.9% by mass of compound (1-2) and 462 ppm by mass of HCF2SO2NHLi (compound (2-1)) (Lot A). Compound (1-2) 19 F-NMR (deuterated dimethyl sulfoxide): δ(ppm)-115.4(4F) HCF2SO2NHLi (compound (2-1)) 1 H-NMR (deuterated dimethyl sulfoxide): δ(ppm) 6.0(1H) 19 F-NMR (deuterated dimethyl sulfoxide): δ(ppm)-122.6(2F)

[0292] <Synthesis of compound (1-2) (Lot B)> (Electrolytic coupling reaction process) A stirrer, acetonitrile (4.5 g), and water (22.6 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere, and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 30.0 g, 168.2 mmol) was added. Platinum plate electrodes (13 mm x 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. A current of 1.5 A (231 mA / cm2) was applied to the electrodes while stirring was maintained under cooling at 0°C. 2 ) was passed through the reaction mixture for 3 hours. After the end of the current, stirring was stopped and the reaction mixture separated into two phases. The lower layer was separated to obtain 17.2 g of liquid. The obtained liquid was dried using molecular sieves and then purified by distillation to obtain 12.2 g of liquid containing FO2SCF2CF2SO2F (compound (4-1)). FO2SCF2CF2SO2F (compound (4-1)) 19 F-NMR (deuterated chloroform): δ(ppm) 46.1 (2F), -108.7 (4F)

[0293] (Cyclization process) A 3L autoclave was cooled to -78°C, and ammonia gas (240g, 14.09mol) and tetrahydrofuran (200mL) were added. Then, while maintaining the temperature inside the autoclave at -55°C or lower, a solution of FOSCFCFSOF (compound (4-1), 173g, 0.59mol) in tetrahydrofuran (200.0mL) was added dropwise. After the dropwise addition, the mixture was stirred overnight at room temperature. Then, while maintaining stirring, the internal pressure was returned to normal pressure, and argon was blown into the autoclave at a rate of 0.5L / min for 1.5 hours to discharge the ammonia. The reaction solution was filtered to remove the white solid, which was then washed several times with tetrahydrofuran. The obtained filtrate was transferred to a 3L flask, concentrated under reduced pressure, and further vacuum dried at 40°C for 12 hours to obtain 160.2g of a solid. The obtained solid was sampled, 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the compound was a fluorine-containing cyclic sulfonylimide ammonium salt represented by the following formula (compound (1-N-2), 0.56 mol, yield 95%). 19 F-NMR (deuterated dimethyl sulfoxide): δ(ppm)-115.4(4F)

[0294] (Cation exchange process) In a 1L three-neck flask, a stirrer, tetrahydrofuran (564mL), fluorine-containing cyclic sulfonylimide ammonium salt (compound (1-N-2), 242.0g, 0.93mol), and lithium hydroxide monohydrate (42.9g, 1.02mol) were added under a nitrogen atmosphere, and the mixture was stirred at 75°C for 4 hours. The obtained reaction liquid was concentrated under reduced pressure, and then ion-exchanged water (628mL) and activated carbon (82.7g) were added, and the mixture was stirred at 105°C for 3 hours. The obtained reaction liquid was filtered under pressure to remove insoluble solids, and then concentrated under reduced pressure to obtain a solid (245g). Tetrahydrofuran (1.27L) was added to the obtained flesh-colored solid, and the mixture was stirred at 50°C for 30 minutes, after which insoluble solids were removed by pressure filtration, and the mixture was concentrated under reduced pressure, and then vacuum dried at 70°C for 16 hours and at 90°C for 6 hours to obtain 212g of a white solid. The solid obtained was sampled and analyzed by ICP atomic emission spectrometry, which confirmed that the ammonium cations had been exchanged for lithium cations. 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the resulting crystals were fluorine-containing cyclic sulfonimide lithium salt (compound (1-2), 0.85 mol, yield 91%) represented by the formula: 19 F-NMR analysis confirmed that the product contained 99.8 mass% of compound (1-2) and 761 mass ppm of HCF2SO2NHLi (compound (2-1)) (Lot B). Compound (1-2) 19 F-NMR (deuterated dimethyl sulfoxide): δ(ppm)-115.4(4F) HCF2SO2NHLi (compound (2-1)) 1 H-NMR (deuterated dimethyl sulfoxide): δ(ppm) 6.0(1H) 19 F-NMR (deuterated dimethyl sulfoxide): δ(ppm)-122.6(2F)

[0295] [Table 2]

[0296] (2) Preparation of coin-type non-aqueous secondary batteries (2-1) Preparation of positive electrode (P1) The positive electrode active material is a composite oxide of lithium, nickel, manganese and cobalt (LiNi 0.33 Mn 0.33 Co 0.33 O2), carbon black powder as a conductive assistant, and polyvinylidene fluoride (PVDF) as a binder were mixed in a mass ratio of 94:3:3 to obtain a positive electrode mixture.

[0297] The obtained positive electrode mixture was mixed with N-methyl-2-pyrrolidone as a solvent to prepare a positive electrode mixture-containing slurry. The positive electrode mixture-containing slurry was applied to one side of an aluminum foil having a thickness of 20 μm to serve as a positive electrode current collector in an amount of 11.4 mg / cm. 2 The positive electrode active material layer was then coated while adjusting the density so that the density became 2.71 g / cm. 3 The positive electrode (P1) was obtained by rolling the positive electrode active material layer and the positive electrode current collector.

[0298] (2-2) Preparation of negative electrode (N1) A negative electrode mixture was obtained by mixing graphite powder as a negative electrode active material, carbon black powder as a conductive assistant, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio of 90:3:7.

[0299] The obtained negative electrode mixture was mixed with water as a solvent to prepare a negative electrode mixture-containing slurry. The negative electrode mixture-containing slurry was applied to one side of a copper foil having a thickness of 8 μm to serve as a negative electrode current collector in an amount of 5.4 mg / cm. 2 The negative electrode active material layer was then coated while adjusting the density so that the density became 1.31 g / cm. 3 The negative electrode (N1) was obtained by rolling the negative electrode active material layer and the negative electrode current collector.

[0300] (2-3) Assembly of coin-type non-aqueous secondary batteries A polypropylene gasket was set in a CR2032 type battery case (SUS304 / Al clad), and the positive electrode (P1) obtained as described above was punched into a disk shape with a diameter of 15.958 mm and set in the center with the positive electrode active material layer facing up. On top of that, a glass fiber filter paper (GA-100; Advantec) was punched into a disk shape with a diameter of 16.156 mm and set, and 150 μL of non-aqueous electrolyte (S01 to S21) was poured, and then the negative electrode (N1) obtained as described above was punched into a disk shape with a diameter of 16.156 mm and set with the negative electrode active material layer facing down. Furthermore, after setting a spacer and a spring in the battery case, the battery cap was fitted and crimped with a crimping machine. The overflowing non-aqueous electrolyte was wiped off with a rag. The assembly including the laminate of the positive electrode, glass fiber filter paper, and negative electrode, and the nonaqueous electrolyte solution was kept at 25° C. for 12 hours to allow the nonaqueous electrolyte solution to fully penetrate the laminate, thereby obtaining a coin-type nonaqueous secondary battery.

[0301] (3) Evaluation of coin-type non-aqueous secondary batteries The coin-type non-aqueous secondary batteries obtained as described above were first subjected to an initial charge process and an initial charge / discharge capacity measurement according to the procedure in (3-1) below. Next, each non-aqueous secondary battery was evaluated according to the procedure in (3-2) below. The charge / discharge was performed using a charge / discharge device ACD-M01A (product name) manufactured by Asuka Electronics Co., Ltd. and a programmable thermostatic chamber IN804 (product name) manufactured by Yamato Scientific Co., Ltd. Here, 1C means a current value at which a battery in a fully charged state is expected to be discharged at a constant current to complete discharging in one hour. In the evaluations (3-1) to (3-2) below, specifically, 1C means a current value at which a battery in a fully charged state of 4.2V is discharged at a constant current to 3.0V to complete discharging in one hour.

[0302] The small nonaqueous secondary battery assembled according to the procedure in (2-3) above is a 3 mAh class cell, the battery voltage in a fully charged state is set to 4.2 V, and the current value equivalent to 1 C is set to 3.0 mA. Hereinafter, unless otherwise specified, the notation of current value and voltage will be omitted for convenience.

[0303] (3-1) Initial charge / discharge process The ambient temperature of the coin-type non-aqueous secondary battery was set to 25°C, and the battery was charged at a constant current of 0.075mA, which corresponds to 0.025C, until it reached 3.1V, and then charged at a constant voltage of 4.2V until the current attenuated to 0.025mA. After a 3-hour pause, the battery was charged at a constant current of 0.15mA, which corresponds to 0.05C, until it reached 4.2V, and then charged at a constant voltage of 4.2V until the current attenuated to 0.025C. The charge capacity at this time (the sum of the charge capacity up to 3.1V and the charge capacity up to 4.2V) was taken as the initial charge capacity (X). Then, the battery was discharged to 3.0V at a constant current of 0.45mA, which corresponds to 0.15C. The discharge capacity at this time was taken as the initial discharge capacity (Y). In addition, the initial charge / discharge efficiency was calculated based on the following formula. Initial charge / discharge efficiency = (initial discharge capacity (Y) / initial charge capacity (X)) x 100 [%] Next, after reaching 4.2 V at a constant current of 0.6 mA, which corresponds to 0.2 C, charging was performed at a constant voltage of 4.2 V until the current attenuated to 0.025 C. Then, discharging was performed to 3 V at a current value of 0.6 mA, which corresponds to 0.2 C. Then, one cycle of charging and discharging was performed in the same manner as above.

[0304] (3-2) 25℃ cycle test The coin-type non-aqueous secondary battery that had been subjected to the initial charge-discharge treatment according to the method described in (3-1) above was charged at a constant current of 3 mA, which corresponds to 1 C, at an ambient temperature of 25° C. until it reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current attenuated to 0.025 C. It was then discharged at a constant current of 3 mA, which corresponds to 1 C, until the battery voltage reached 3.0 V. This process of charging and discharging once each constituted one cycle, and 100 cycles of charging and discharging were performed. The discharge capacity at this time was taken as the 100th cycle discharge capacity (hereinafter, sometimes referred to as (T)). The cycle capacity retention rate was calculated based on the following formula. Cycle capacity retention rate = (100th cycle discharge capacity in 25°C cycle test (T) / initial discharge capacity in initial charge / discharge treatment (Y)) x 100 [%] If the voltage had dropped to 2 V or less before the 25° C. cycle test, the voltage was determined to be abnormal and the cycle test was not performed.

[0305] (4) ICP optical emission spectroscopy of the negative electrode After the 25°C cycle test, the battery was discharged at a constant current equivalent to 0.1C in a 25°C environment until the battery voltage reached 2.5V. The coin-type nonaqueous secondary battery was then disassembled in an argon atmosphere to remove the negative electrode. The negative electrode was washed with acetonitrile and then dried. Furthermore, after the pretreatment described below, the negative electrode was subjected to ICP emission spectroscopy analysis.

[0306] As a pretreatment, the sample was placed in a Teflon (registered trademark) decomposition vessel, and a mixed solvent of 68% nitric acid: 3 mL and 98% sulfuric acid: 5 mL was added, and the sample was decomposed by microwave heating at 220 ° C for 45 minutes (first-stage reaction), and then 68% nitric acid: 2 mL was added, and the sample was decomposed by microwave heating again at 230 ° C for 40 minutes (second-stage reaction), and the total amount was adjusted to about 100 g with ultrapure water. Since graphite remained as a residue, the filtered liquid was used for ICP measurement. The microwave pretreatment device used was Milestone General's ETHOS one, and the microwave output was set to 1000 W.

[0307] The ICP emission spectroscopic analysis was carried out under the following conditions to measure the amount of Al eluted from the negative electrode per 1 g of the negative electrode (including the negative electrode current collector foil). Equipment: SII NanoTechnology SPS3520UV-DD High frequency power: 1.2 (Kw) Plasma gas (Ar) flow rate: 16 (L / min) Auxiliary gas (Ar) flow rate: 0.5 (L / min) Carrier gas (Ar) pressure: 0.24 (MPa) Carrier gas (Ar) flow rate: 0.3 (L / min) Chamber gas (Ar) flow rate: 0.6 (L / min) Purge gas (N2) flow rate: 5 (L / min) Photometric height: 12 (mm) Element: Al Spectrometer:R Wavelength: 167.079(nm) Purge gas: ON The calibration curve was created using six calibration standard solutions of 0, 0.01, 0.05, 0.1, 0.5, 1, and 2 mg / L, which were prepared by diluting a 100 mg / L Al standard solution with an acid aqueous solution (prepared by adding 68% nitric acid and 98% sulfuric acid to ultrapure water to achieve the same acid concentration as the sample digestion solution).

[0308] (5) SEM analysis of the surface of the positive electrode Al current collector After the 25°C cycle test was completed, the battery was discharged at a constant current equivalent to 0.1C until the battery voltage reached 2.5V in a 25°C environment. The coin-type nonaqueous secondary battery was then disassembled in an argon atmosphere to remove the positive electrode. The positive electrode active material on the positive electrode Al current collector was removed with a cotton swab soaked in N-methyl-2-pyrrolidone (NMP). The positive electrode Al current collector was washed with acetonitrile and then dried. The positive electrode Al current collector was then cut to an appropriate size in an argon atmosphere and fixed to a sample stage for scanning electron microscope (SEM) observation to prepare a surface SEM observation sample. The sample was introduced into the SEM device in an atmosphere-blocked state using a dedicated transfer vessel.

[0309] SEM observation was performed using a Hitachi SU8220. The measurement conditions were an accelerating voltage of 1 kV.

[0310] FIG. 3 (magnification: 40 times) and FIG. 4 (magnification: 1000 times) are SEM photographs of the surface of the positive electrode Al current collector of the coin-type nonaqueous secondary battery prepared with the nonaqueous electrolyte solution used in Example II-1 after the cycle test.

[0311] FIG. 5 (magnification: 40x) and FIG. 6 (magnification: 1000x) are SEM photographs of the surface of the positive electrode Al current collector of the coin-type nonaqueous secondary battery prepared using the nonaqueous electrolyte solution used in Comparative Example II-1 after the cycle test.

[0312] In addition, SEM photographs of the surface of the positive electrode Al current collector of the coin-type nonaqueous secondary battery prepared using the nonaqueous electrolyte solution used in Comparative Example II-3 after the cycle test are shown in FIG. 7 (magnification: 40 times), FIG. 8 (magnification: 1000 times), and FIG. 9 (magnification: 10000 times).

[0313] Here, we discuss the interpretation of each test.

[0314] The initial efficiency indicates the ratio of the initial discharge capacity to the initial charge capacity, and is generally lower than the charge / discharge efficiency from the second time onwards. This is because Li ions are used during the initial charge to form the negative electrode SEI. This results in fewer Li ions being able to be discharged. Here, there is no problem if the initial charge / discharge efficiency is 84% ​​or more, and it is desirable for it to be 85% or more.

[0315] The 25°C cycle capacity retention is an index of battery deterioration due to repeated use. The higher this value, the less capacity loss due to repeated use, and the more suitable the battery is for long-term use. Therefore, it is desirable that the 25° C. cycle capacity retention rate be 70% or more. Furthermore, if the voltage drops to 2 V or less before the 25°C cycle test, it is believed that a slight short circuit has occurred within the battery, making it difficult to use the battery in applications intended for long-term use.

[0316] The amount of Al elution from the negative electrode is an index of battery degradation due to repeated use. The smaller this value, the more suppressed the corrosion of the positive electrode Al current collector foil due to repeated use and the more suppressed the degradation of the negative electrode SEI due to reduction precipitation of Al at the negative electrode, and the more usable the battery is for long-term use. Therefore, the amount of Al elution from the negative electrode is preferably 1000 ppm by mass or less, and more preferably 500 ppm by mass or less.

[0317] Table 3 shows the results of the initial charge / discharge treatment, the 25°C cycle test, and the ICP emission spectroscopic analysis of the negative electrode.

[0318] [Table 3]

[0319] As shown in Table 3, in Examples II-1 to II-13, the initial efficiency, cycle capacity retention rate, and amount of Al eluted from the negative electrode were all within the preferred range. On the other hand, in Comparative Examples II-2, II-3, II-4, II-5, and II-7, the initial efficiency was less than 84%. In Comparative Examples II-3, II-4, II-7, and II-8, the cycle capacity retention rate was less than 70%. In Comparative Examples II-1, II-3, and II-6, the amount of Al eluted from the negative electrode was more than 1000 ppm by mass.

[0320] Comparing Example II-1 with Comparative Examples II-1 to II-3, the initial efficiency is improved by using a fluorine-containing cyclic sulfonylimide salt as the lithium salt and adjusting the amount of the fluorine-containing sulfonamide compound to a preferred range. This is thought to be because the Al corrosion reaction at the positive electrode during the initial charge and the reduction and precipitation reaction of Al at the negative electrode are suppressed, suppressing the increase in irreversible capacity. Regarding the initial charge capacity and initial discharge capacity, although the initial charge capacity of Example II-1 is lower than that of Comparative Examples II-1 to II-3, the initial discharge capacity of Example II-1 is not lower than that of Comparative Examples II-1 to II-3, suggesting that the irreversible reaction caused by Al corrosion is suppressed.

[0321] In addition, comparing Example II-1 with Comparative Examples II-1 and II-3, by using a fluorine-containing cyclic sulfonylimide salt as the lithium salt and adjusting the amount of the fluorine-containing sulfonamide compound to a preferred range, the cycle capacity retention rate is improved and the amount of Al elution from the negative electrode is reduced. This is believed to be because the continuous Al corrosion reaction at the positive electrode and the Al reduction and precipitation reaction at the negative electrode during the cycle test are suppressed, the increase in irreversible capacity is suppressed, and physical damage to the negative electrode SEI caused by Al reduced and precipitated at the negative electrode is suppressed.

[0322] In Comparative Example II-2, in which LiFSI was used as the lithium salt, the voltage dropped to 2 V or less before the start of the cycle test, causing a voltage abnormality. This is believed to be due to the fact that a severe Al corrosion reaction occurred at the positive electrode and an Al reduction and precipitation reaction occurred at the negative electrode during the initial charge and discharge, causing a micro-short circuit due to the Al reduced and precipitated at the negative electrode.

[0323] In addition, in Figure 7, numerous pits were observed on the surface of the Al current collector. Figures 8 and 9 show an enlarged view of one of the pits, and in Figure 9, in addition to the outer edge of the pit being distorted, further holes were observed inside the pit. This is thought to be because the positive electrode Al current collector was severely corroded when a fluorine-containing cyclic sulfonylimide salt was not used as the lithium salt. On the other hand, in Figures 3 and 4, no pits were observed on the surface of the Al current collector, and the use of a fluorine-containing cyclic sulfonylimide salt as the lithium salt can suppress severe corrosion of the positive electrode Al current collector.

[0324] Furthermore, when Example II-1 and Example II-2 are compared, when Lot A is used as the fluorine-containing cyclic sulfonylimide salt, the cycle capacity retention rate is improved and the amount of Al eluted from the negative electrode is reduced compared to when Lot B is used. This is thought to be because the crystallization purification has a higher effect of reducing fluorine-containing sulfonamide compounds than the distillation purification after the electrolytic coupling reaction step, and the fluorine-containing cyclic sulfonylimide salt and the fluorine-containing sulfonamide compounds in the electrolyte are reduced, so that the continuous Al corrosion reaction at the positive electrode and the Al reduction and precipitation reaction at the negative electrode during the cycle test are suppressed, the increase in irreversible capacity is suppressed, and physical damage to the negative electrode SEI due to Al reduced and precipitated at the negative electrode is suppressed.

[0325] (6) Increase in discharge IR drop after 100 cycles in 25℃ cycle test In each cycle, the difference in voltage before the start of discharge and the voltage 10 seconds after the start of discharge (unit: V) was divided by the discharge current value of 3.0 (unit: mA) to obtain the discharge IR drop in each cycle (unit: kΩ), which was used as an index of internal resistance.

[0326] The discharge IR drop at the first cycle was defined as the first cycle discharge IR drop, and the discharge IR drop at the 100th cycle was defined as the 100th cycle discharge IR drop. The discharge IR drop increase rate after 100 cycles was calculated based on the following formula. IR drop increase rate after 100 cycles = (100th cycle discharge IR drop in 25°C cycle test / 1st cycle discharge IR drop) x 100 [%]

[0327] The increase rate of discharge IR drop after 100 cycles is an index of battery deterioration due to repeated use. The smaller this value, the smaller the increase in internal resistance due to repeated use, and it is considered that the battery can be used for applications aimed at long-term use. Therefore, in a non-aqueous secondary battery containing a non-aqueous electrolyte solution containing acetonitrile, the increase rate of discharge IR drop after 100 cycles is preferably 400% or less, and more preferably 200% or less. The obtained evaluation results are shown in Table 4.

[0328] [Table 4]

[0329] As shown in Table 4, in Examples II-14 and II-15, the increase rate of discharge IR drop after 100 cycles was within a preferable range. On the other hand, in Comparative Example II-9, the increase rate of discharge IR drop after 100 cycles was greater than 400%. This is believed to be because the continuous Al corrosion reaction at the positive electrode and the Al reduction precipitation reaction at the negative electrode during the cycle test were suppressed, suppressing the increase in internal resistance.

[0330] Furthermore, when Example II-14 and Example II-15 are compared, when Lot A is used as the fluorine-containing cyclic sulfonylimide salt, the increase rate of discharge IR drop after 100 cycles is reduced compared to when Lot B is used. This is considered to be because crystallization purification is more effective at reducing fluorine-containing sulfonamide compounds than distillation purification after the electrolytic coupling reaction step, and the fluorine-containing cyclic sulfonylimide salt and the fluorine-containing sulfonamide compounds in the electrolyte are reduced, thereby suppressing the continuous Al corrosion reaction at the positive electrode and the Al reduction precipitation reaction at the negative electrode during the cycle test, thereby suppressing the increase in internal resistance.

[0331] (7) Fabrication of small non-aqueous secondary batteries (7-1) Preparation of positive electrode (P2) The positive electrode active material is a composite oxide of lithium, nickel, manganese and cobalt (LiNi 0.8 Mn 0.1 Co 0.1 O2), carbon black powder as a conductive assistant, and polyvinylidene fluoride (PVDF) as a binder were mixed in a mass ratio of 94:3:3 to obtain a positive electrode mixture.

[0332] The obtained positive electrode mixture was mixed with N-methyl-2-pyrrolidone as a solvent to prepare a positive electrode mixture-containing slurry. The positive electrode mixture-containing slurry was applied to one side of an aluminum foil having a thickness of 20 μm to serve as a positive electrode current collector in an amount of 16.6 mg / cm.2 The positive electrode active material layer was then coated while adjusting the density so that the density became 2.91 g / cm. 3 The positive electrode (P2) was obtained by rolling the positive electrode active material layer and the positive electrode current collector.

[0333] (7-2) Preparation of negative electrode (N2) (A) Graphite powder as the negative electrode active material, (B) carbon black powder as a conductive additive, and (C) polyvinylidene fluoride (PVDF) as a binder were mixed in a solids mass ratio of 90:3:7 to obtain a negative electrode mixture.

[0334] The obtained negative electrode mixture was mixed with water as a solvent to prepare a negative electrode mixture-containing slurry. The slurry was applied to one side of a copper foil having a thickness of 8 μm to be used as a negative electrode current collector in an amount of 10.3 mg / cm2. 2 The negative electrode active material layer was then coated while adjusting the density so that the density became 1.36 g / cm. 3 The negative electrode (N2) was obtained by rolling the negative electrode active material layer and the negative electrode current collector.

[0335] (7-3) Assembly of small non-aqueous secondary batteries The positive electrode (P2) obtained as described above was punched into a disk shape with a diameter of 18 mm, and the negative electrode (N2) obtained as described above was punched into a disk shape with a diameter of 18 mm. The positive electrode was then stacked on both sides of an insulating sleeve with a built-in separator (EL-Cell, ECC1-00-0210-W / X), 120 μL of non-aqueous electrolyte (S19-S20) was poured in, and the positive electrode side was pressed with an aluminum plunger and the negative electrode side with a SUS plunger to obtain a laminate. The laminate was then inserted into a battery case (EL-Cell, PAT-Cell) and assembled, after which the battery case was sealed and held at 25 ° C for 12 hours to allow the non-aqueous electrolyte to fully soak into the laminate, thereby obtaining a small non-aqueous secondary battery.

[0336] (8) Evaluation of small non-aqueous secondary batteries The small non-aqueous secondary batteries obtained as described above were first subjected to an initial charge / discharge treatment and an initial charge / discharge capacity measurement according to the procedure in (8-1) below. Next, each small non-aqueous secondary battery was evaluated according to the procedure in (8-2) below. The charge / discharge was performed using a charge / discharge device ACD-M01A (product name) manufactured by Asuka Electronics Co., Ltd. and a programmable thermostatic chamber IN804 (product name) manufactured by Yamato Scientific Co., Ltd.

[0337] In this specification, 1C means a current value at which a battery in a fully charged state is expected to be discharged at a constant current to complete discharging in one hour. In the evaluations (8-1) and (8-2) below, specifically, 1C means a current value at which a battery in a fully charged state of 4.2 V is discharged at a constant current to 3.0 V to complete discharging in one hour.

[0338] The small non-aqueous secondary battery assembled according to the procedure in (7-3) above is a 7.4mAh class cell, with the battery voltage in a fully charged state set to 4.2V and the current value equivalent to 1C set to 7.4mA. Hereinafter, unless otherwise specified, the notation of current value and voltage will be omitted for convenience.

[0339] (8-1) Initial charge / discharge treatment of small non-aqueous secondary batteries The ambient temperature of the small non-aqueous secondary battery was set to 25°C, and it was charged at a constant current of 0.185 mA, equivalent to 0.025 C, until it reached 3.1 V, after which it was charged for 1.5 hours at a constant voltage of 3.1 V. After a 3-hour pause, the battery was charged at a constant current of 0.37 mA, equivalent to 0.05 C, until it reached 4.2 V, after which it was charged for 1.5 hours at a constant voltage of 4.2 V. The battery was then discharged to 3.0 V at a constant current of 1.11 mA, equivalent to 0.15 C.

[0340] (8-2) 50℃ cycle test of small non-aqueous secondary batteries The small nonaqueous secondary battery that had been initially charged and discharged by the method described in (8-1) above was charged at a constant current of 3.7 mA, equivalent to 0.5 C, at an ambient temperature of 50° C. until it reached 4.2 V, and then charged at a constant voltage of 4.2 V for 1.5 hours. The battery was then discharged to 3.0 V at a current value of 3.7 mA, equivalent to 0.5 C. This process of charging and discharging once each constitutes one cycle, and 100 cycles of charging and discharging were performed.

[0341] In each cycle, the difference in voltage before the start of discharge and the voltage 10 seconds after the start of discharge (unit: V) was divided by the discharge current value of 3.7 (unit: mA) to obtain the discharge IR drop in each cycle (unit: kΩ), which was used as an index of internal resistance.

[0342] The discharge IR drop at the first cycle was defined as the first cycle discharge IR drop, and the discharge IR drop at the 100th cycle was defined as the 100th cycle discharge IR drop. The discharge IR drop increase rate after 100 cycles was calculated based on the following formula. IR drop increase rate after 100 cycles = (100th cycle discharge IR drop in 50℃ cycle test / 1st cycle discharge IR drop) x 100 [%]

[0343] The increase rate of discharge IR drop after 100 cycles is an index of battery deterioration due to repeated use. The smaller this value, the smaller the increase in internal resistance due to repeated use, and it is considered that the battery can be used for applications aimed at long-term use. Therefore, in a non-aqueous secondary battery containing a non-aqueous electrolyte that does not contain acetonitrile, the increase rate of discharge IR drop after 100 cycles is preferably 200% or less, and more preferably 130% or less. The obtained evaluation results are shown in Table 5.

[0344] [Table 5]

[0345] As shown in Table 5, in Example II-16, the increase rate of the discharge IR drop after 100 cycles showed a value of 130% or less, while in Example II-17, the increase rate of the discharge IR drop after 100 cycles showed a value exceeding 130%.

[0346] Comparing Example II-16 and Example II-17, the increase rate of the discharge IR drop after 100 cycles is improved by the non-aqueous electrolyte containing LiPF6. This is presumably because the amount of hydrogen fluoride (HF) necessary for the formation of the aluminum passive film and the negative electrode SEI is satisfied by containing LiPF6, and the decomposition products of the cyclic anion acted as negative electrode SEI components.

[0347] Also, comparing Example II-16 and Example II-17, the increase rate of the discharge IR drop after 100 cycles is improved by the content of LiPF6 being in the range of 0.01 or more and 4 or less in molar ratio with respect to the content of vinylene carbonate. This is presumably because the ratio of the organic components derived from the lithium salt containing the cyclic anion and the cyclic carbonate and the inorganic components derived from LiPF6 in the negative electrode SEI is appropriately controlled by the content of LiPF6 being in a preferable range with respect to the content of vinylene carbonate.

[0348] <III. Electrolytic Coupling Reaction (Relationship between β / α and Relationship between Reaction Vessel - Electrode)>

[0349] <Analysis Method> The analysis methods, raw materials, reaction conditions, etc. used in the examples and comparative examples were as follows. (Nuclear Magnetic Resonance Analysis (NMR): 1 1H-NMR, and 19 19F-NMR for molecular structure analysis) Regarding the products obtained in the examples and comparative examples, 1 1H-NMR (400 MHz), and 19 19F-NMR (337 MHz) were used for molecular structure analysis under the following measurement conditions. [Measurement Conditions] Measurement equipment: JNM-ECZ400S nuclear magnetic resonance equipment (manufactured by JEOL Ltd.) Observation kernel: 1 H, 19 F Solvent: deuterated chloroform, deuterated dimethyl sulfoxide Reference material: Tetramethylsilane ( 1 H, 0.00 ppm), trichlorofluoromethane ( 19 F, 0.00 ppm) Reference substance concentration: 5% by mass Measurement sample concentration: 20% by mass Pulse width: 6.5μsec Wait time: 2 seconds Number of times accumulated: 8 times ( 1 H), 1024 times ( 19 F)

[0350] <Raw materials used> The raw materials used in the examples and comparative examples are shown below. (Fluorosulfonyl group-containing carboxylic acid compound (3)) 2,2-Difluoro-2-(fluorosulfonyl)acetic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (compound (3-1)) Ammonia (Sumitomo Seika Chemicals Co., Ltd.) (Alkali Metal Salts (6)) Lithium hydroxide monohydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0351] (solvent) Acetonitrile (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; the water content was adjusted by adding dried molecular sieve 3A 1 / 16 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), dehydrating, and removing the molecular sieve 3A 1 / 16) Tetrahydrofuran (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; the water content was adjusted by adding dried molecular sieve 3A 1 / 16 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), dehydrating, and removing the molecular sieve 3A 1 / 16)

[0352] Activated carbon (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Octafluorotoluene (Tokyo Chemical Industry Co., Ltd.)

[0353] <Reaction temperature> The reaction temperature is room temperature when no external heating / cooling device is used, and is the temperature of the medium used in the external heating / cooling device when an external heating / cooling device such as a water bath or an oil bath is used.

[0354] <Examples of β / α> [Example III-1] A stirrer, acetonitrile (12.9 g), and water (17.1 g) were added to a 100 mL three-neck flask under a nitrogen atmosphere (β / α=0.75), and then cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 5.0 g, 28.1 mmol) was added. Platinum plate electrodes (25 mm x 50 mm) were placed as the anode and cathode with a gap of 3 mm and immersed in the solution. While maintaining stirring under cooling at 0°C, a current of 1.5 A was passed through the electrodes for 0.5 hours. After the current had been passed, the resulting liquid was sampled, 19 When measured by F-NMR, the production ratio of FO2SCF2CF2SO2F (compound (4-1)) and HCF2SO2F (compound (5-1)) was 100:0.9. FO2SCF2CF2SO2F (compound (4-1)) 19 F-NMR: δ(ppm)46.1(2F), -108.7(4F) HCF2SO2F (compound (5-1)) 1 H-NMR: δ(ppm) 7.7ppm(1H) 19 F-NMR: 37.0 (1F), -120.3 (2F)

[0355] [Example III-2] The current was applied in the same manner as in Example III-1, except that acetonitrile (10.0 g) and water (20.0 g) were used (β / α=0.50). After the current was applied, the obtained liquid was sampled, 19When measured by F-NMR, the production ratio of FO2SCF2CF2SO2F (compound (4-1)) and HCF2SO2F (compound (5-1)) was 100:0.8.

[0356] [Example III-3] The current was applied in the same manner as in Example III-1, except that acetonitrile (5.0 g) and water (25.0 g) were used (β / α=0.20). After the current was applied, the obtained liquid was sampled, 19 When measured by F-NMR, the production ratio of FO2SCF2CF2SO2F (compound (4-1)) and HCF2SO2F (compound (5-1)) was 100:0.4.

[0357] [Example III-4] (Electrolytic coupling reaction) The current was applied in the same manner as in Example III-1, except that acetonitrile (2.5 g) and water (27.5 g) were used (β / α=0.09). After the current was applied, the obtained liquid was sampled, 19 When measured by F-NMR, the production ratio of FO2SCF2CF2SO2F (compound (4-1)) and HCF2SO2F (compound (5-1)) was 100:0.3.

[0358] (Cyclization process) A 1L autoclave was cooled to -78°C, and ammonia gas (60.0 g, 3523.2 mmol) and tetrahydrofuran (110.0 g) were added, followed by the dropwise addition over 3 hours of a solution of FOSCFCFSOF (compound (3-1), 50 g, 187.5 mmol) obtained by the electrolytic coupling reaction in tetrahydrofuran (50.0 g). After the dropwise addition was completed, the mixture was stirred at room temperature for 12 hours. After the stirring was completed, the reaction solution was pressure filtered to remove insoluble solids, and the filtrate was concentrated under reduced pressure and dried to obtain 49.1 g of a flesh-colored solid. The obtained solid was sampled, 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the compound was a fluorine-containing cyclic sulfonylimide ammonium salt represented by the following formula (compound (1-N-2), yield 99.1%). 19 F-NMR: δ(ppm)-115.4(4F)

[0359] (Cation exchange process) In a 1L three-neck flask, a stirrer, tetrahydrofuran (100 g), the fluorine-containing cyclic sulfonylimide ammonium salt obtained in the cyclization step (compound (1-N-2), 45.0 g, 170.4 mmol), and lithium hydroxide monohydrate (8.1 g, 193.0 mmol) were added under a nitrogen atmosphere, and the mixture was stirred at 70°C for 4 hours. The reaction solution obtained was concentrated under reduced pressure, and then water (120 mL) and activated carbon (16.5 g) were added, and the mixture was stirred at 105°C for 3 hours. The reaction solution obtained was filtered under pressure to remove insoluble solids, and then concentrated under reduced pressure to obtain a skin-colored solid. Tetrahydrofuran (220 g) was added to the obtained skin-colored solid, and the mixture was stirred at 50°C for 30 minutes, and then filtered under pressure to remove insoluble solids, and then concentrated under reduced pressure to obtain 40.9 g of a white solid. The obtained solid was sampled and analyzed by ICP atomic emission spectrometry, and it was confirmed that the ammonium cations had been exchanged for lithium cations. Furthermore, 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the compound was a fluorine-containing cyclic sulfonimide lithium salt represented by the following formula (compound (1-2), yield 95.9%). 19 F-NMR: δ(ppm)-115.4(4F)

[0360] [Example III-5] The current was applied in the same manner as in Example III-1, except that acetonitrile (13.0 g) and water (17.0 g) were used (β / α=0.76). After the current was applied, the obtained liquid was sampled, 19 When measured by F-NMR, the production ratio of FO2SCF2CF2SO2F (compound (4-1)) and HCF2SO2F (compound (5-1)) was 100:1.6.

[0361] [Example III-6] The current was applied in the same manner as in Example III-1, except that acetonitrile (15.0 g) and water (15.0 g) were used (β / α=1.00). After the current was applied, the obtained liquid was sampled, 19 When measured by F-NMR, the production ratio of FO2SCF2CF2SO2F (compound (4-1)) and HCF2SO2F (compound (5-1)) was 100:4.4.

[0362] [Example III-7] The current was applied in the same manner as in Example III-1, except that acetonitrile (20.0 g) and water (10.0 g) were used (β / α=2.00). After the current was applied, the obtained liquid was sampled, 19 When measured by F-NMR, the production ratio of FO2SCF2CF2SO2F (compound (4-1)) and HCF2SO2F (compound (5-1)) was 100:8.4.

[0363] [Example III-8] A stirrer, acetonitrile (5 g), and water (25 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere (β / α=0.2), and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 5.2 g, 29.4 mmol) was added. Platinum plate electrodes (13 mm × 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. A current of 1.5 A (231 mA / cm) was applied to the electrodes while stirring was maintained under cooling at 0°C. 2 A current of 1 F / mol was applied for 0.5 hours. After the current was applied, the stirring was stopped and the reaction solution separated into two phases. 19 F-NMR analysis revealed that HCF2SO2F (compound (5-1)) was produced in a yield of 0.4%, HO2CCF2SO3H in a yield of 0.2%, and FO2SCF2CO2H remained at 23%. 19F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a yield of 49%, and a trace amount of HCF2SO2F (compound (5-1)) was produced. The current efficiency was 49%. The production ratio of FO2SCF2CF2SO2F (compound (4-1)) to HCF2SO2F (compound (5-1)) was 100:0.8.

[0364] [Example III-9] A stirrer, acetonitrile (10 g), and water (20 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere (β / α=0.5), and then cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 5.1 g, 28.7 mmol) was added. Platinum plate electrodes (13 mm × 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. A current of 1.5 A (231 mA / cm) was applied to the electrodes while stirring was maintained under cooling at 0°C. 2 A current of 1 F / mol was applied for 0.5 hours. After the current was applied, the stirring was stopped and the reaction solution separated into two phases. 19 F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a yield of 0.5%, FO2SCF2CF2SO3H in a yield of 0.8%, HCF2SO2F (compound (5-1)) in a yield of 1%, and HO2CCF2SO3H in a yield of 0.2%, with 16% of FO2SCF2CO2H (compound (3-1)) remaining. 19 F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a yield of 53% and a trace amount of HCF2SO2F was produced. The current efficiency was 53%. The production ratio of FO2SCF2CF2SO2F (compound (4-1)) to HCF2SO2F (compound (5-1)) was 100:1.9.

[0365] [Example III-10] A stirrer, acetonitrile (4.17 g), and water (20.85 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere (β / α=0.2), and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 10.1 g, 56.9 mmol) was added. Platinum plate electrodes (13 mm × 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. A current of 1.5 A (231 mA / cm) was applied to the electrodes while stirring was maintained under cooling at 0°C. 2 A current of 1 F / mol was applied for 1 hour. After the current was applied, the stirring was stopped and the reaction solution separated into two phases. 19 F-NMR analysis revealed that HCF2SO2F (compound (5-1)) was produced in a yield of 0.3%, HO2CCF2SO3H in a yield of 0.6%, and FO2SCF2CO2H (compound (3-1)) remained at 17%. 19 F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a yield of 57% and a trace amount of HCF2SO2F (compound (5-1)). The current efficiency was 57%. The production ratio of FO2SCF2CF2SO2F (compound (4-1)) to HCF2SO2F (compound (5-1)) was 100:0.5.

[0366] [Example III-11] A stirrer, acetonitrile (3.3 g), and water (16.7 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere (β / α=0.2), and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 15.2 g, 85.2 mmol) was added. Platinum plate electrodes (13 mm × 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. A current of 1.5 A (231 mA / cm) was applied to the electrodes while stirring was maintained under cooling at 0°C. 2 A current of 1 F / mol was applied for 1.5 hours. After the current was applied, the stirring was stopped and the reaction solution separated into two phases. 19F-NMR analysis revealed that HCF2SO2F (compound (5-1)) was produced in a yield of 0.1%, HO2CCF2SO3H in a yield of 0.6%, and FO2SCF2CO2H (compound (3-1)) remained at 13%. 19 F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a 62% yield, and a trace amount of HCF2SO2F (compound (5-1)) was produced. The current efficiency was 62%. The production ratio of FO2SCF2CF2SO2F (compound (4-1)) to HCF2SO2F (compound (5-1)) was 100:0.2.

[0367] [Example III-12] A stirrer, acetonitrile (4.5 g), and water (22.5 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere (β / α=0.2), and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 30.0 g, 168.5 mmol) was added. Platinum plate electrodes (13 mm × 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. A current of 1.5 A (231 mA / cm) was applied to the electrodes while stirring was maintained under cooling at 0°C. 2 A current of 1 F / mol was applied for 3 hours. After the current was applied, the stirring was stopped and the reaction solution separated into two phases. 19 F-NMR analysis revealed that HCF2SO2F (compound (5-1)) was produced in a yield of 0.1%, HO2CCF2SO3H in a yield of 0.7%, and FO2SCF2CO2H (compound (3-1)) remained at 9%. 19 F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a yield of 72% and a trace amount of HCF2SO2F (compound (5-1)). The current efficiency was 72%. The production ratio of FO2SCF2CF2SO2F (compound (4-1)) to HCF2SO2F (compound (5-1)) was 100:0.1.

[0368] <Reaction vessel-electrode relationship> [Example III-13] A stirrer, acetonitrile (15 g), and water (15 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere, and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 5.0 g, 28.3 mmol) was added. Platinum plate electrodes (13 mm x 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. While stirring was maintained under cooling at 0°C, a current of 1.5 A (231 mA / cm) was applied to the electrodes. 2 A current of 0.5 F / mol was applied for 0.25 hours. After the current was applied, the stirring was stopped and the reaction solution separated into two phases. 19 F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in an 8% yield, FO2SCF2CF2SO3H in a 1% yield, HCF2SO2F (compound (5-1)) in a 3% yield, and HO2CCF2SO3H in a 0.3% yield, with 41% of FO2SCF2CO2H (compound (3-1)) remaining. 19 F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a yield of 22%, and a trace amount of HCF2SO2F (compound (5-1)) was produced. The current efficiency was 60%. Regarding the relationship between the reaction vessel and the electrodes, the height TL was 75 mm, the highest TE was 65 mm, the height TS was 8 mm, and the lowest TE' was 15 mm, so that TL>TE and TE'>TS were satisfied. During the reaction, the voltage did not rise suddenly, and hunting did not occur. FO2SCF2CF2SO3H 19 F-NMR: δ(ppm)44.3(1F), -106.2(2F), -113.7(2F) HCF2SO2F (compound (5-1)) 19 F-NMR: δ(ppm)37.0(1F), -120.3(2F) 1 H-NMR: δ(ppm) 6.5(1H) HO2CCF2SO3H 19 F-NMR: δ(ppm)-111.5(2F) FO2SCF2CO2H (compound (3-1)) 19 F-NMR: δ(ppm)37.1(1F), -102.0(2F)

[0369] [Example III-14] A stirrer, acetonitrile (15 g), and water (15 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere, and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 5.1 g, 28.4 mmol) was added. Platinum plate electrodes (13 mm x 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. A current of 1.5 A (231 mA / cm2) was applied to the electrodes while stirring was maintained under cooling at 0°C. 2 ) for 0.5 hours (1F / mol). After the end of the current, stirring was stopped and the reaction solution separated into two phases. Analysis of the upper layer revealed that FOSCF2CF2SO2F (compound (4-1)) was produced in an 8% yield, FOSCF2CF2SO3H in a 2% yield, and HCF2SO2F (compound (5-1)) in a 2% yield, with 11% FOSCF2CO2H remaining. Analysis of the lower phase revealed that FOSCF2CF2SO2F (compound (4-1)) was produced in a 41% yield, and a trace amount of HCF2SO2F (compound (5-1)) was produced. The current efficiency was 49%. Regarding the relationship between the reaction vessel and the electrodes, the height TL was 75 mm, the highest TE was 65 mm, the height TS was 8 mm, and the lowest TE' was 15 mm, so TL>TE and TE'>TS were satisfied. During the reaction, the voltage did not rise suddenly and hunting did not occur.

[0370] [Example III-15] A stirrer, acetonitrile (15 g), and water (15 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere, and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 5.1 g, 28.5 mmol) was added. Platinum plate electrodes (13 mm x 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. A current of 1.5 A (231 mA / cm2) was applied to the electrodes while stirring was maintained under cooling at 0°C. 2 ) was passed for 0.75 hours (1.5F / mol). After the end of the current, stirring was stopped and the reaction solution separated into two phases. Analysis of the upper layer revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a 7% yield, FO2SCF2CF2SO3H in a 3% yield, HCF2SO2F (compound (5-1)) in a 1% yield, traces of HO2CCF2SO3H, and 5% of FO2SCF2CO2H (compound (3-1)) remained. Analysis of the lower phase revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a 38% yield, and traces of HCF2SO2F (compound (5-1)) were produced. The current efficiency was 30%. Regarding the relationship between the reaction vessel and the electrodes, the height TL was 75 mm, the highest position TE was 65 mm, the height TS was 5 mm, and the lowest position TE' was 15 mm, so TL>TE and TE'>TS were satisfied. During the reaction, the voltage did not rise suddenly, and hunting did not occur.

[0371] [Example III-16] A stirrer, acetonitrile (15 g), and water (15 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere, and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (3-1), 5.0 g, 28.3 mmol) was added. Platinum plate electrodes (13 mm x 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. While stirring was maintained under cooling at 0°C, a current of 1.5 A (231 mA / cm) was applied to the electrodes. 2 A current of 2 F / mol was applied for 1 hour. After the current was applied, the stirring was stopped and the reaction solution separated into two phases. 19F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a 7% yield, FO2SCF2CF2SO3H in a 3% yield, HCF2SO2F (compound (5-1)) in a 1% yield, traces of HO2CCF2SO3H, and 2% of FO2SCF2CO2H (compound (3-1)) remained. 19 F-NMR analysis revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a 44% yield, and a trace amount of HCF2SO2F (compound (5-1)) was produced. The current efficiency was 26%. Regarding the relationship between the reaction vessel and the electrodes, the height TL was 75 mm, the highest TE was 65 mm, the height TS was 8 mm, and the lowest TE' was 15 mm, so that TL>TE and TE'>TS were satisfied. During the reaction, the voltage did not rise suddenly, and hunting did not occur.

[0372] The storage stability of FO2SCF2CO2H (compound (3-1)) was measured according to the following method. [Storage stability evaluation] In a 30 mL screw tube, add FO2SCF2CO2H (compound (3-1), 10.0 g), acetonitrile (1.5 g), water (7.5 g), and 19 Octafluorotoluene (0.3 g) was added as an internal standard for F-NMR, and the mixture was shaken. 19 F-NMR was measured, and the integral value of the doublet peak at -102.0 ppm of compound (3-1) was calculated to be 88.72 when the integral value of the triplet peak at -57.4 ppm of octafluorotoluene was set to 3. This value was taken as the reference content of compound (3-1) at 0 hours. Next, the above solution was divided into three 10 mL screw tubes, and each screw tube was left to stand at -20°C, -3°C, and 23°C, and after a predetermined time had passed, 19 F-NMR was measured, and the integral value of the doublet peak at -102.0 ppm of compound (3-1) was calculated when the integral value of the triplet peak at -57.4 ppm of octafluorotoluene was set to 3, and the residual rate of compound (3-1) was calculated using the following formula. Residual ratio of compound (3-1) = (Integral value of the doublet peak at -102.0 ppm) / 88.72 × 100

[0373] [Table 6]

[0374] From Table 6, it can be seen that the mixture of FO2SCF2CO2H (compound (3-1)), acetonitrile, and water shows a dramatic improvement in stability when stored at 3°C or lower. Therefore, it is considered that the electrolytic coupling reaction is carried out at a low temperature (for example, in the range of -35°C to 10°C), ensuring the stability of the raw materials and suppressing the formation of by-products.

[0375] [IV. Electrolytic Coupling Reaction (Relationship between δ / γ and Reaction Vessel - Electrode Relationship)] [Example IV-1] Under a nitrogen atmosphere, a stir bar, acetonitrile (4.0 g), and water (18.5 g) were added to a 100 mL three-necked flask, and then cooled to 0°C. FO2SCF2CO2H (compound (3-1), 15.0 g, 84.2 mmol) was added (δ / γ = 1.5). As the anode and cathode, platinum plate electrodes (25 mm × 50 mm) were installed at an interval of 3 mm and immersed in the solution. While maintaining stirring under 0°C cooling, a current of 1.5 A was passed through the electrodes for 1.5 hours. After the energization was completed, when the stirring was stopped, the reaction solution separated into two phases. Among them, the lower phase was separated by liquid separation, and 9.0 g of liquid was obtained. The obtained liquid was sampled and 19 Measured by 19F-NMR, it was found to be FO2SCF2CF2SO2F (compound (4-1), purity 90.5%, yield 72.7%). FO2SCF2CF2SO2F (compound (4-1)) 19 19F-NMR: δ (ppm) 46.1 (2F), -108.7 (4F)

[0376] [Example IV-2] Except for using acetonitrile (3.3 g), water (16.7 g), and FOSCFCOH (compound (3-1), 15.0 g, 84.2 mmol), the current was applied in the same manner as in Example IV-1 (δ / γ=1.3). After the current was applied, the stirring was stopped and the reaction liquid separated into two phases. The lower phase was separated to obtain 9.4 g of liquid. The obtained liquid was sampled, 19 Measurement by F-NMR revealed that the product was FO2SCF2CF2SO2F (compound (4-1), purity 92.4%, yield 77.5%).

[0377] [Example IV-3] (Electrolytic coupling reaction) Acetonitrile (4.5 g), water (22.5 g), and FOSCFCOH (compound (3-1), 30.0 g, 168.5 mmol) were used, and the current application time was changed to 3 hours. Except for this, the same procedure as in Example IV-1 was carried out (δ / γ=0.9). After the current application was completed, stirring was stopped and the reaction liquid separated into two phases. The lower phase was separated to obtain 20.6 g of liquid. The obtained liquid was sampled, 19 Measurement by F-NMR revealed that the product was FO2SCF2CF2SO2F (compound (4-1), purity 92.4%, yield 84.9%).

[0378] (Cyclization process) A 1L autoclave was cooled to -78°C, and ammonia gas (60.0 g, 3523.2 mmol) and tetrahydrofuran (110.0 g) were added, followed by the dropwise addition over 3 hours of a solution of FOSCFCFSOF (compound (4-1), 50 g, purity 92.4%, 173.6 mmol) obtained by the electrolytic coupling reaction in tetrahydrofuran (50.0 g). After the dropwise addition was completed, the mixture was stirred at room temperature for 12 hours. After the stirring was completed, the reaction solution was pressure filtered to remove insoluble solids, and the filtrate was concentrated under reduced pressure and dried to obtain 45.4 g of a flesh-colored solid. The obtained solid was sampled, 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the compound was a fluorine-containing cyclic sulfonylimide ammonium salt represented by the following formula (compound (1-N-2), purity 97.7%, yield 98.2%). Compound (1-N-2) 19 F-NMR: δ(ppm)-115.4(4F)

[0379] (Cation exchange step) A stirrer, tetrahydrofuran (100 g), the fluorine-containing cyclic sulfonylimide ammonium salt obtained in the cyclization step (compound (1-N-2), 45.0 g, 169.0 mmol), and lithium hydroxide monohydrate (8.0 g, 190.7 mmol) were added to a 1 L three-neck flask under a nitrogen atmosphere, and the mixture was stirred at 70° C. for 4 hours. The reaction solution obtained was concentrated under reduced pressure, and then water (120 mL) and activated carbon (16.5 g) were added, and the mixture was stirred at 105° C. for 3 hours. The reaction solution obtained was filtered under pressure to remove insoluble solids, and then concentrated under reduced pressure to obtain a skin-colored solid. Tetrahydrofuran (220 g) was added to the obtained skin-colored solid, and the mixture was stirred at 50° C. for 30 minutes, and then filtered under pressure to remove insoluble solids, and concentrated under reduced pressure to obtain 41.7 g of a white solid. The obtained solid was sampled and analyzed by ICP atomic emission spectrometry, and it was confirmed that the ammonium cations had been exchanged for lithium cations. Furthermore, 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that the compound was a fluorine-containing cyclic sulfonimide lithium salt represented by the following formula (compound (1-2), purity 99.1%, yield 98.2%). Compound (1-2) 19 F-NMR: δ(ppm)-115.4(4F)

[0380] [Example IV-4] Acetonitrile (4.1 g), water (20.9 g), and FOSCFCOH (compound (3-1), 10.0 g, 56.2 mmol) were used (δ / γ=2.5), and the current application time was set to 1 hour. Except for this, the same procedure as in Example IV-1 was carried out. After the current application was completed, stirring was stopped and the reaction liquid separated into two phases. The lower phase was separated to obtain 4.8 g of liquid. The obtained liquid was sampled, 19 Measurement by F-NMR revealed that the product was FO2SCF2CF2SO2F (compound (4-1), purity 91.0%, yield 58.5%).

[0381] [Example IV-52] A current was applied in the same manner as in Example IV-1, except that acetonitrile (5.0 g), water (25.0 g), and FOSCFCOH (compound (3-1), 5.0 g, 28.1 mmol) were used (δ / γ=6.0) and the current application time was 0.5 hours. After the current application was completed, stirring was stopped and the reaction liquid separated into two phases. The lower phase was separated to obtain 2.2 g of liquid. The obtained liquid was sampled, 19 Measurement by F-NMR revealed that the product was FO2SCF2CF2SO2F (compound (4-1), purity 89.1%, yield 51.5%).

[0382] [Example IV-6] Except for using acetonitrile (4.0 g), water (20.0 g), and FOSCFCOH (compound (3-1), 15.0 g, 84.2 mmol), the current was applied in the same manner as in Example IV-1 (δ / γ=1.6). After the current was applied, the stirring was stopped and the reaction liquid separated into two phases. The lower phase was separated to obtain 8.3 g of liquid. The obtained liquid was sampled, 19 Measurement by F-NMR revealed that the product was FO2SCF2CF2SO2F (compound (4-1), purity 91.1%, yield 67.5%).

[0383] [Example IV-7] A stirrer, acetonitrile (4.5 g), and water (22.5 g) were added to a Schlenk flask with an external dimension of 30 mm in diameter, 170 mm in height, and a capacity of 50 mL under a nitrogen atmosphere, and then the flask was cooled to 0°C, and FO2SCF2CO2H (compound (4-1), 30.0 g, 168.5 mmol) was added. Platinum plate electrodes (13 mm x 50 mm) were placed as the anode and cathode with an interval of 3 mm and immersed in the solution. A current of 1.5 A (231 mA / cm2) was applied to the electrodes while stirring was maintained under cooling at 0°C. 2 ) for 3 hours (1F / mol). After the current was applied, stirring was stopped and the reaction solution separated into two phases. Analysis of the upper layer revealed that HCF2SO2F (compound (5-1)) was produced in a yield of 0.1%, HO2CCF2SO3H in a yield of 0.7%, and FO2SCF2CO2H (compound (3-1)) remained at 9%. Analysis of the lower phase revealed that FO2SCF2CF2SO2F (compound (4-1)) was produced in a yield of 72%, and a trace amount of HCF2SO2F (compound (5-1)) was produced. The current efficiency was 72%.

[0384] [Example IV-8] (Cyclization process) A 3L autoclave was cooled to -78°C, and ammonia gas (250g, 14.68mol) and tetrahydrofuran (250mL) were added. The temperature inside the autoclave was kept below -55°C, and a solution of FOSCFCFSOF (compound (4-1), 208g, 0.71mol) obtained by the electrolytic coupling reaction in Example IV-3 in tetrahydrofuran (250.0mL) was added dropwise. After the dropwise addition, the mixture was stirred overnight at room temperature. Then, while maintaining stirring, the internal pressure was returned to normal pressure, and argon was blown into the autoclave at a rate of 0.5L / min for 1.5 hours to discharge ammonia. The reaction solution was filtered to remove the white solid, which was then washed several times with tetrahydrofuran. The obtained filtrate was transferred to a 3L flask, concentrated under reduced pressure, and further vacuum dried at 40°C for 12 hours to obtain 188.0g of a solid. The obtained solid was sampled, 19 F-NMR analysis revealed the following structural formula: [ka] It was confirmed that it was a fluorine-containing cyclic sulfonylimide ammonium salt represented by (Compound (1-N-2), 0.7 mol, yield 98%).

[0385] (Cation exchange step) In a 1 L three-necked flask, under a nitrogen atmosphere, a stir bar, tetrahydrofuran (450 mL), the fluorine-containing cyclic sulfonylimide ammonium salt obtained in the cyclization step (Compound (1-N-2), 187.0 g, 0.69 mol), and lithium hydroxide monohydrate (32.2 g, 0.77 mol) were added, and the mixture was stirred at 70 °C for 4 hours. After the obtained reaction solution was concentrated under reduced pressure, ion-exchanged water (500 mL) and activated carbon (65.8 g) were added, and the mixture was stirred at 105 °C for 3 hours. After the obtained reaction solution was filtered under pressure to remove insoluble solids, it was concentrated under reduced pressure to obtain a solid (205.8 g). Tetrahydrofuran (1 L) was added to the obtained off-white solid, and after stirring at 50 °C for 30 minutes, insoluble solids were removed by pressure filtration, concentrated under reduced pressure, and vacuum dried at 70 °C for 16 hours and at 90 °C for 10 hours to obtain 170.3 g of a light brown solid. When the obtained solid was sampled and analyzed by ICP emission spectrometry, it was confirmed that the ammonium cation was exchanged with the lithium cation. Furthermore, 19 When analyzed by 19F-NMR, the following structural formula:

Chemical formula

[0386] <V. Crystallization> <Analysis method> The analysis methods used in the examples and comparative examples were as follows.

[0387] (Nuclear magnetic resonance analysis (NMR): 1 1H-NMR, 19 Molecular structure analysis by 19F-NMR) For the products obtained in the examples and comparative examples, 1 1H-NMR (400 MHz), 19Molecular structure analysis was carried out using F-NMR (376 MHz) under the following measurement conditions. [Measurement conditions] Measurement equipment: JNM-ECZ400S nuclear magnetic resonance equipment (manufactured by JEOL Ltd.) Observation kernel: 1 H or 19 F Solvent: deuterated chloroform, deuterated dimethyl sulfoxide Reference material: Tetramethylsilane ( 1 H, 0.00 ppm), trichlorofluoromethane ( 19 F, 0.00 ppm) Reference substance concentration: 5% by mass Measurement sample concentration: 20% by mass Pulse width: 6.5μsec Wait time: 2 seconds Number of times accumulated: 8 times ( 1 H) or 1024 times ( 19 F). In the following examples, 19 In the spectrum obtained by F-NMR measurement, the sum of the integral values ​​of the peaks of the fluorine-containing cyclic sulfonylimide salt is represented as T1, the sum of the integral values ​​of the peaks of impurities that are characteristically present as a single or multiple doublet peaks in the region of -115 ppm to -125 ppm is represented as T2, and the ratio of T1 to T2 is represented as T1 / T2, which is used as an index of the purity of the fluorine-containing cyclic sulfonylimide. 19 The peaks of the fluorine-containing cyclic sulfonylimide salt and impurities in F-NMR may vary in chemical shift value by about ±5 ppm depending on the purity, the amount of remaining solvent, the measurement conditions, etc. The fluorine-containing cyclic sulfonylimide salt according to the present invention is not limited by the misattribution associated with such fluctuations in chemical shift value.

[0388] [Example V-1] According to the method described in Examples [Example 2] and [Example 4] to [Example 6] of Patent Document 2 (WO 2006 / 106960), commercially available 2,2-difluoro-2-fluorosulfonylacetic acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was used as a raw material, and a compound having the following structural formula: [ka] A fluorine-containing cyclic sulfonimide lithium salt (compound (1-2)) represented by the formula was synthesized. 10 g of the synthesized compound (1-2) and 27 g of tert-butyl methyl ether were weighed into a 100 mL eggplant flask equipped with a stirrer, and the flask was sealed and stirred for 30 minutes. The resulting mixture was filtered under reduced pressure and cooled in a freezer at -20°C for 30 minutes, resulting in colorless crystals. The liquid was removed by decantation, and then tert-butyl methyl ether at -35°C was added and mixed with a medicine spoon to wash the crystals, and the liquid was removed by decantation. The obtained crystals were dried under reduced pressure for 3 hours at 60°C and 40 hPa without stirring. The mass of the crystals after drying was 4.9 g, and the yield based on the amount used was 49%. 19 In F-NMR, the peak of compound (1-2) (δ(ppm)-110.0(4F)) and the peak of an impurity seen as a single doublet at -117.2 ppm had a T1 / T2 of 3170. Benzotrifluoride was used as the internal standard. 1 From the measurement of H-NMR, the amount of remaining tert-butyl methyl ether was 0.72 mass%, and from these results, the purity of compound (1-2) was 99.2 mass%. The obtained dried crystals could be easily taken out of the eggplant flask in their entirety by crushing with a medicine spoon.

[0389] [Comparative example V-1] Compound (1-2) was synthesized in the same manner as in Example V-1, but was not subsequently purified by crystallization. 19In F-NMR, the sum of the integrals of the peak of compound (1-2) (δ (ppm) -115.4 (4F)) and the peaks of impurities seen as multiple doublets in the region of -122 ppm to -125 ppm had a T1 / T2 of 215, indicating low purity, and the powder obtained after crushing and drying was colored brown.

[0390] [Comparative example V-2] Compound (1-2) was synthesized in the same manner as in Example V-1. Next, 1 g of the synthesized compound (1-2) and 2 g of acetone (boiling point 56°C) were weighed into a 20 mL eggplant flask, and the flask was agitated for 30 minutes with a stopper attached. The mixture was cooled at -50°C overnight, but no crystals were formed, and high purification was not possible. When the contents were dried under reduced pressure for 3 hours at 60°C and 10 hPa for recovery, only a part of the wall of the contents solidified, and a highly viscous liquid remained at the bottom, making it impossible to recover it as a solid with a medicine spoon. The reason why a large amount of solvent remained even when acetone with a low boiling point was used is thought to be that the high affinity between acetone and lithium inhibited the distillation of acetone.

[0391] [Comparative example V-3] Compound (1-2) was synthesized in the same manner as in Example V-1. Next, 1 g of the synthesized compound (1-2) and 2 g of dimethyl carbonate were weighed into a 50 mL eggplant flask, and the flask was sealed and stirred for 30 minutes. After filtering the mixture, 20 g of cyclohexane was added to the resulting liquid, and the liquid separated into two phases, with no crystals forming. The phase-separated liquid was cooled overnight at -20°C, but no crystals of compound (1-2) were formed, and high purification was not possible. This is thought to be because crystallization was suppressed due to the high affinity between dimethyl carbonate and lithium.

[0392] [Example V-2] Compound (1-2) was synthesized in the same manner as in Example V-1. Next, 10 g of the synthesized compound (1-2) and 20 g of dimethyl carbonate were weighed in a 200 mL eggplant flask, and the flask was sealed and stirred for 30 minutes. After filtering the mixture, the liquid was cooled at -50°C overnight, but no crystals were formed. When the mixture was dried under reduced pressure for 10 hours at 100°C and 5 hPa for recovery, the entire mixture became a cloudy gel-like substance, and further drying turned it into a highly viscous solid. 27 g of tert-butyl methyl ether was added and dissolved therein, and the mixture was cooled at -50°C overnight, resulting in colorless crystals. The liquid portion was removed by decantation, and then tert-butyl methyl ether at -35°C was added and mixed with a medicine spoon to wash the crystals, and the liquid portion was removed by decantation. The obtained crystals were dried under reduced pressure for 3 hours at 60°C and 40 hPa without stirring. An attempt was made to crush the resulting crystals with a spoon to recover them, but they were noticeably stuck to the bottom of the eggplant flask, and only 2.7 g of crystals (27% yield) were obtained by crushing with a spoon. The loss due to adhesion was 2.0 g. It is believed that the remaining dimethyl carbonate, which has a high affinity for lithium, caused the crystals to partially dissolve during drying, and they stuck to the eggplant flask wall. Since it was expected that the sample would be nonuniform due to the crystals sticking to each other, the recovered crystals were further dried at 100°C and 20 hPa for 3 hours, and then crushed with a pestle, ultimately obtaining 2.4 g of crystals. 19 The T1 / T2 ratio measured by F-NMR was 1550. Benzotrifluoride was used as the internal standard. 1 H-NMR measurement revealed that the remaining amount of tert-butyl methyl ether was 0.29% by mass, and the remaining amount of dimethyl carbonate was 0.13% by mass. These results showed that the purity of compound (1-2) was 99.5% by mass.

[0393] [Comparative Example V-4] Compound (1-2) was synthesized in the same manner as in Example V-1. Next, 1.0 g of the synthesized compound (1-2) and 1.3 g of tetrahydrofuran (boiling point 65°C) were weighed into a 20 mL eggplant flask, and the flask was agitated for 30 minutes with a stopper attached. The mixture was cooled at -50°C overnight, but no crystals were formed, and high purity could not be achieved. When the mixture was dried under reduced pressure for 3 hours at 60°C and 10 hPa for recovery, only a part of the wall of the contents solidified, and a highly viscous liquid remained at the bottom, making it impossible to recover it as a solid with a medicine spoon. Even when tetrahydrofuran, a low boiling point ether solvent, was used, a large amount of solvent remained, which is thought to be due to the strong coordination force to lithium due to the cyclic structure of tetrahydrofuran, which inhibited the distillation of tetrahydrofuran.

[0394] [Example V-5] The synthesis, crystallization and drying of compound (1-2) were carried out in the same manner as in Example V-1, and 4.9 g of crystals were obtained. Next, 30 mL of 1,1,1,2,2,3,4,5,5,5-decafluoropentane was added and the crystals were washed by mixing with a medicine spoon, and then dried for 7 hours under conditions of 100°C and 15 hPa. This washing and drying operation was repeated a total of 5 times, and finally 4.6 g of crystals were obtained. 19 The T1 / T2 ratio measured by F-NMR was 3355. Benzotrifluoride was used as the internal standard. 1 From the measurement of H-NMR, the amount of remaining tert-butyl methyl ether was 0.072% by mass, and from these results, the purity of compound (1-2) was 99.9% by mass. The obtained dried crystals could be easily taken out of the eggplant flask in their entirety by crushing them with a medicine spoon. [Industrial Applicability]

[0395] Since the nonaqueous electrolyte within the scope of the constituent requirements of the present invention can be used in batteries that require improved high-temperature durability and reduced metal corrosion, the nonaqueous secondary battery using the nonaqueous electrolyte of the present invention is expected to be used as, for example, a rechargeable battery for portable devices such as mobile phones, portable audio devices, personal computers, and IC (Integrated Circuit) tags; a rechargeable battery for automobiles such as hybrid automobiles, plug-in hybrid automobiles, and electric automobiles; a low-voltage power source such as a 12V class power source, a 24V class power source, and a 48V class power source; a residential power storage system, an IoT device, etc. In addition, the nonaqueous secondary battery using the nonaqueous electrolyte of the present invention can also be used in cold regions and outdoor applications in summer.

[0396] The fluorine-containing cyclic sulfonylimide salt (1A) according to the present invention has high heat resistance and can be used over a wide temperature range, and therefore can be suitably used as an antistatic agent, an ion-conducting material such as an organic electrolyte, or a flame retardant.

[0397] The production method of the present invention makes it possible to produce bis(fluorosulfonyl) compounds, which are raw materials for surfactants, antistatic agents, electrolytes, ionic liquids, catalysts, etc., while reducing the content of fluorosulfonyl group-containing compounds, which are by-products.

[0398] The production method according to the present invention makes it possible to stably produce, in high yield, bis(fluorosulfonyl) compounds that are used as raw materials for surfactants, antistatic agents, electrolytes, ionic liquids, catalysts, and the like.

[0399] The production method according to the present invention makes it possible to produce a fluorine-containing cyclic sulfonylimide salt with a small amount of residual solvent and fluorine-based impurities with high efficiency. The reduction in the amount of residual solvent allows production with simpler equipment, at lower cost, and with less thermal history. Furthermore, the reduction in the amount of impurities makes it possible to suppress coloration. Therefore, the fluorine-containing cyclic sulfonylimide salt obtained by the production method according to the present invention can be suitably used as an ion-conducting material, an antistatic agent, a flame retardant, etc. [Explanation of symbols]

[0400] 1 Reaction vessel 2 Pair of electrodes 3 Aqueous phase (upper layer) 4 Organic phase (lower layer) TL Height (distance) from the bottom of the reaction vessel to the liquid level of the reaction solution TE Height (distance) from the bottom of the reaction vessel to the top of the electrode (highest position) TE' Height (distance) from the bottom of the reaction vessel to the bottom of the electrode (lowest position) TS Height (distance) from the bottom of the reaction vessel to the interface between the organic and aqueous phases

[0401] 100 Nonaqueous secondary battery 110 Battery housing 120 Space in battery housing 130 Positive electrode lead body 140 Negative electrode lead body 150 positive electrode 160 negative electrode 170 Separator

Claims

1. The following general formula (1A): 【Chemistry 1】 In the formula, R may be the same or different and is a fluorine atom or a trifluoromethyl group, n is an integer of 1 to 4, and M 1 is Li, Na, K, or NH 4 A fluorine-containing cyclic sulfonylimide salt composition comprising a fluorine-containing cyclic sulfonylimide salt represented by the formula A fluorine-containing cyclic sulfonylimide salt composition, characterized in that when heated in a nitrogen stream from 100°C at a heating rate of 10°C / min, the temperature at which a mass loss rate becomes 2% by mass is 385°C or higher.

2. The following general formula (2): H(CR 2 ) m -SO 2 NHM 2 (2) In the formula, R may be the same or different and is a fluorine atom or a trifluoromethyl group; M 2 is Li, Na, K, H or NH 4 and m is 1 or 2. The fluorine-containing cyclic sulfonylimide salt composition according to claim 1, containing 5,000 ppm by mass or less of a fluorine-containing sulfonamide compound represented by the following formula:

3. The fluorine-containing cyclic sulfonylimide salt composition according to claim 2, wherein in said general formula (1A), n is 2.

4. The fluorine-containing cyclic sulfonylimide salt composition according to claim 2 or 3, wherein in said general formulae (1A) and (2), R is a fluorine atom.

5. In the general formula (1A), M 1 is Li, and in the general formula (2), M 2 The fluorine-containing cyclic sulfonylimide salt composition according to any one of claims 2 to 4, wherein is Li.

6. The fluorine-containing cyclic sulfonylimide salt is represented by the following formula: 【Chemistry 2】 The fluorine-containing cyclic sulfonylimide salt composition according to any one of claims 1 to 5, represented by:

7. The following general formula (3): MO 2 C-(CR 2 ) m -SO 2 F (3) In the formula, R may be the same or different and is a fluorine atom or a trifluoromethyl group, m is 1 or 2, and M is H, Li, Na, K, or NH 4 The compound represented by the general formula (1A): 【Chemistry 3】 In the formula, R may be the same or different and is a fluorine atom or a trifluoromethyl group, n is an integer of 1 to 4, and M 1 is Li, Na or K}, the method for producing a fluorine-containing cyclic sulfonylimide salt represented by the following general formula (5): H-(CR 2 ) m -SO 2 F (5) {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2}, and the amount of the fluorosulfonyl group-containing compound represented by the formula (1) is reduced to 0.1 mass % or less in the reaction solution in the electrolytic coupling reaction step.

8. The following general formula (3): MO 2 C-(CR 2 ) m -SO 2 F (3) In the formula, R may be the same or different and is a fluorine atom or a trifluoromethyl group, m is 1 or 2, and M is H, Li, Na, K, or NH 4 The compound represented by the general formula (1A): 【Chemistry 4】 In the formula, R may be the same or different and is a fluorine atom or a trifluoromethyl group, n is an integer of 1 to 4, and M 1 is Li, Na or K}, the method comprising a crystallization step of dissolving the fluorine-containing cyclic sulfonylimide salt obtained after the cation exchange step in a monodentate chain ether solvent and then crystallizing the solution to obtain a purified fluorine-containing cyclic sulfonylimide salt.

9. The method according to claim 8, wherein the monodentate chain ether solvent used in the crystallization is at least one solvent selected from the group consisting of ethyl ether, propyl methyl ether, propyl ethyl ether, propyl ether, isopropyl methyl ether, isopropyl ethyl ether, isopropyl ether, butyl methyl ether, butyl ethyl ether, isobutyl methyl ether, isobutyl ethyl ether, sec-butyl methyl ether, sec-butyl ethyl ether, tert-butyl methyl ether, tert-butyl ethyl ether, pentyl methyl ether, isopentyl methyl ether, sec-pentyl methyl ether, tert-pentyl methyl ether, neopentyl methyl ether, and cyclopentyl methyl ether.

10. The method according to claim 8 or 9, wherein n in the general formula (1A) is 2.

11. The method according to any one of claims 8 to 10, wherein R in the general formula (1A) is F.

12. M in the general formula (1A) 1 The method according to any one of claims 8 to 11, wherein is Li.

13. The method according to any one of claims 7 to 12, wherein in the electrolytic coupling reaction step, the fluorosulfonyl group-containing carboxylic acid compound represented by the general formula (3) is subjected to an electrolytic coupling reaction in the presence of a mixed solvent of water and a nitrile group-containing solvent, in which the ratio (β / α) of the mass of water (α) to the mass of the nitrile group-containing solvent (β) is 0.80 or less.

14. The method according to claim 13, wherein the ratio (β / α) of the mass (α) of water to the mass (β) of the nitrile group-containing solvent is 0.75 or less.

15. In the electrolytic coupling reaction step, the fluorosulfonyl group-containing carboxylic acid compound represented by the general formula (3) is subjected to an electrolytic coupling reaction in a reaction vessel in the presence of a mixed solvent of water and a nitrile group-containing solvent, The method according to any one of claims 7 to 14, wherein during the reaction, a height (distance) TL from the bottom of the reaction vessel to the liquid level of the reaction liquid and a height (distance) TE from the bottom of the reaction vessel to the upper part (highest position) of the electrode satisfy the relationship TL>TE, and after the reaction, a height (distance) TS from the bottom of the reaction vessel to the interface between the organic phase and the aqueous phase and a height (distance) TE' from the bottom of the reaction vessel to the lower part (lowest position) of the electrode satisfy the relationship TE'>TS.

16. The method according to claim 15, wherein the relationship between the TE' and the TS is TE'×0.6>TS.

17. The method according to any one of claims 13 to 16, wherein the content of alkali metals in the reaction solution in the electrolytic coupling reaction is 2000 ppm by mass or less.

18. In the electrolytic coupling reaction step, the production molar ratio of the compound represented by the general formula (5) is the same as or similar to the following general formula (4): FO 2 S-(CR 2 ) m -SO 2 F (4) The method according to any one of claims 13 to 17, wherein the amount of the fluorosulfonyl group per mole of the bis(fluorosulfonyl) compound (4) represented by the formula: {wherein R may be the same or different and is a fluorine atom or a trifluoromethyl group, and m is 1 or 2} is 0.01 or less relative to 1 mole of the produced amount of the bis(fluorosulfonyl) compound (4).

19. The method according to any one of claims 13 to 18, characterized in that in the electrolytic coupling reaction step, the fluorosulfonyl group-containing carboxylic acid compound represented by the general formula (3) is subjected to an electrolytic coupling reaction in the presence of a mixed solvent of water and a nitrile group-containing solvent, and the ratio (δ / γ) of the mass (γ) of the fluorosulfonyl group-containing carboxylic acid compound to the mass (δ) of the mixed solvent is 1.5 or less.

20. The method according to any one of claims 13 to 19, wherein in the electrolytic coupling reaction, the plate gap between the anode and the cathode is 0.001 mm to 9.9 mm.

21. The method according to claim 19 or 20, wherein the yield of the compound (4) in the electrolytic coupling reaction is 70% or more.

22. The method according to any one of claims 13 to 21, wherein the nitrile group-containing solvent is at least one selected from the group consisting of acetonitrile, propionitrile, butyronitrile, and benzonitrile.

23. 23. The method of claim 22, wherein the nitrile group-containing solvent is acetonitrile.

24. The method according to any one of claims 13 to 23, wherein the electrolytic coupling reaction is carried out at a reaction temperature in the range of -35°C or more and 10°C or less.

Citation Information

Patent Citations

  • Process for producing disulfonyl fluoride compound

    WO2006106960A1

  • Method for production of purified ammonium salt of fluorinated bis-sulfonylimide

    WO2009025246A1

  • Electrolyte solution for electrical energy storage devices, and electrical energy storage device

    WO2010110388A1

  • Nonaqueous electrolyte solution and nonaqueous secondary battery

    WO2020262670A1

  • Nonaqueous secondary battery

    JP2008021517A